Klasik Dönem İbâdî Fıkıh Literatürü - Göksün, Ahmet Faruk (BEÜ İlahiyat Fakültesi Dergisi, 2022)
İslam tarihinde ortaya çıkan ilk mezheplerden birisi olan İbâdiyye mezhebi, ılımlı görüşleri dolayısıyla kısa zamanda diğer Hâricî fırkalardan ayrılmış ve günümüze kadar yaşamaya devam etmiştir. İtikâdî olduğu kadar fıkhî bir boyuta da sahip olan mezhep, hareketin fikrî kurucusu sayılan Câbir b. Zeyd (öl. 93) döneminden itibaren oluşmaya başlamış olan geniş bir fıkıh literatürüne sahiptir. Bu literatür günümüzde dahi devam etmektedir. Bu makalede İbâdî fıkhının kuruluş ve teşekkül dönemi olarak nitelendirilebilecek dönemlerde yaşamış İbâdî fukaha ve onların kaleme aldıkları fıkıh eserleri ele alınacaktır. Çalışmayı özgün kılan ise ülkemizde çok kısıtlı miktarda yapılmış olan İbâdî fıkhına yönelik çalışmaların dahi hiç temas etmediği bir nokta olan İbâdî fıkıh literatürünü incelemesidir. Nitekim ülkemizde İbâdî fıkhına yönelik yapılan çalışmalar ya fıkıh usulü ya da füru fıkıh üzerinden bu mezhebi incelemiş, literatürüne ise değinmemiştir. Sürekli itikadi yönüyle ön plana çıkan İbâdiyye mezhebinin fıkhî bir yönünün de olduğunu ve azımsanmayacak derecede bir fıkıh literatürünün bulunduğunu göstermek bu çalışmanın amaçlarındandır. Bu amaçla makalede mezhebin kuruluş dönemi ve hicrî altıncı asrın yarısında sonlanan teşekkül dönemini kapsayan süreçteki İbâdî fıkıh literatürüne temas edilecek ve bu dönemlere yönelik değerlendirmelere yer verilecektir. Ülkemizde bu alanda bir çalışma olmadığı gibi çalışmada zikredilen İbâdî fıkıh eserlerinin bir kısmı ülkemizde ulaşılabilir durumda değildir. Bu da çalışmanın önemini artırmaktadır.

المذاهب الإسلامية في الإيالة التونسية وعلاقتها بالسلطة العثمانية خلال القرن 16م - Şerifoğlu, Metin (Çukurova Üniversitesi İlahiyat Fakültesi Dergisi (ÇÜİFD), 2022)
يتناول هذا البحث مسألة المذاهب الإسلامية في البلاد التونسية وعلاقتها بالدولة العثمانية خلال القرن 16م. ذلك أن المسألة المذهبية عريقة في البلاد التونسية. حيث عرفت تونس عبر تاريخها الإسلامي العديد من المذاهب الإسلامية، منها السنة والشيعة والخوارج. وقد ارتبط انتشار هذه المذاهب بالتطورات السياسية التي شهدتها تونس من الفتح الإسلامي إلى حدود العهد العثماني. كما ظلت في تونس ثلاثة مذاهب إلى يومنا هذا، وهي المالكية والحنفية والإباضية. أما بقية المذاهب فلم يعد لها وجود يذكر. وقد بقي المذهب المالكي أكثر انتشارا في تونس وفي شمال إفريقيا. وعندما دخلت تونس تحت الحكم العثماني عاد المذهب الحنفي إلى الانتشار من جديد، وأصبح المذهب الرسمي للدولة. وقد انتهج العثمانيون سياسة متسامحة مع كل المذاهب في تونس. وسنقوم في هذا البحث بتحليل ثلاثة مباحث هي: أولا أهم المذاهب الإسلامية التي وجدت في تونس قبل الدخول العثماني، ثانيا الدخول العثماني إلى تونس وانعكاساته على الخارطة المذهبية فيها، ثالثا المؤسسات التي أقامها العثمانيون في تونس ودور المذاهب الدينية فيها

Harici Anlayışta Birlikte Yaşama ve İbadi Alim Es-Siyabi’nin Bakışı - Kıyıcı, Burhaneddin (Genç Mütefekkirler Dergisi, 2022)
Hâricilerin ortaya çıkma süreçlerinde insanlar arasında ve toplumda bir ötekileştirme olduğu apaçıktır. Bedevî yaşam tarzlarına çok sıkı bağlı olan Hâriciler, kendilerini korumaya almaları nedeniyle İslâm toplumuna uymak ve birlikte yaşamak yerine, toplumdan uzaklaşarak insanları kategorize etmiş, ferdi ve toplumu tanımlamaya çalışarak ayrışmışlardır. Bu çıkmazı gören İbâdîler her ne kadar ılımlı bir tavır alma gayretine girseler de temelde ki hâricî ruhu pek aşamamışlardır. Büyük günâh işleyenler hakkındaki sert tutumdan biraz daha yumuşak tutuma yönelseler de kendi toplumlarını korumayı bir imân esası olarak ele almışlardır. Kitmân, tevellâ ve teberrî kavramları çerçevesinde kapalı bir toplumsal yapı oluşturmuşlardır. Bundan dolayı hala diğer Müslümân toplumlarla açık irtibata girmemektedirler. Bu ilkeler altında bulunmakla birlikte es-Siyâbî’nin hürriyetlere saygılı davranmak ve farklı görüşleri kıyaslayarak onların en güzelini seçip uymak için dinlemek, zorbalıktan kaçınmak, bilgi edinmede, fikirlerin değiştirilmesinde toplumsal ve insani konularda işbirliğine ihtimam göstermek, farklı görüşleri kıyaslayarak onların en güzelini seçip uymak, gönüllere seslenme ve bir başka insana öfkeyi çirkin görmekle birlik olmayı ahlâkî bir ihtiyaç görmesi özünde büyük bir değişimi göstermektedir. Kapalı bir toplum olmanın yanı sıra toplumsal yapıyı korumak için çok sert kurallar uygulayan bir toplum ve inancın bu değişimi yakalama çabası önem arz etmektedir. Bu bakış açısı geçmişi değerlendirmeyi de yumuşatmış ve günümüzde diğer toplumlarla kendi ilkelerini ve değerlerini hassasiyetle koruyarak yakınlaşmayı sağlayabilme ümidini artırmıştır. Mezhepleri farklı olsa da her müslümânın cenazesinin kılınmasını caiz görmek ve ehli kıbleden hiçbir kimsenin lanetlenmesini helâl ve câiz görmemek, Allah’ı birleyenin kanı, malı ve ırzına saldırıyı haram kabul ederek Allah tüm Müslümânlar arasında kardeşlik ve yardımlaşmayı zorunlu yapmasını esas kabul etmek çıkış noktasından günümüze yansıyan değişimi göstermektedir. es-Siyâbî’nin ilkeler geliştirmesi hem Müslümân toplumlarla hem de dünya halklarıyla birlikte yaşama için niyet ve çabalarının olduğunu göstermektedir. es-Siyâbî’nin ehl-i kıbleden hiçbir kimsenin lanetlenmesini helâl ve câiz görmemesi bunun en kuvvetli işaretidir.

İbâdîlikte Sivil Yönetim Teşkilatı: Azzâbe - Benras, Mahmoud (Rusuh Uşak Üniversitesi İslami İlimler Fakültesi Dergisi, 2022)
İbâdiyye, hicri birinci yüzyıla kadar dayanan ve Büyük Fitne Olayları diye bilinen hadiseden sonra ortaya çıkan siyasi-itikadi bir gruptur. Bu grup ilk dönemde Muhakkime-i Ula grubunun içerisinde yer alırken zamanla siyasi ve düşünce yapısı itibariyle onlardan ayrıldı. Diğer Haricî gruplar erken dönemden itibaren tarih sahnesinden silinmelerine rağmen İbâdîler bugüne kadar varlıklarını sürdürmeyi başarmışlardır. Ancak hâlâ birçok araştırmacı, İbâdîlerin Haricilerin bir kolu olarak varlıklarını sürdürdüklerini ifade veya ima eden yazılar kaleme almaktadır. Bu makalede İbâdîler tarafından ortaya atılan ve bir sosyal ve idari yapı olarak geliştirdikleri yönetim sistemini incelemeye çalışacağız. Bu sistemde, bir imamın, kralın veya bireysel bir kişinin yönettiği bir sistem değil, idarenin bir grubun elinde olduğu yönetim şekli işlemektedir. Bu sistemin adı Azzâbe sistemidir. Özellikle Kuzey Afrika'da devlet başkanı açısından zuhûr (açık imamet), kitman (gizli imamet), savunma ve şira' şeklinde dört yönetim şekli mevcutken mezhebin yani yönetilenlerin yönetilmesi ayrı bir nizamla yapılandırılmıştır. Azzâbe denilen bu sistem alışılmışın dışında bir yönetim şekli olup, Kuzey Afrika bölgesindeki İbâdi varlığını bugüne kadar sürdüren ana unsurlardan birisidir.

İbadi̇yye Mezhebi̇ Ve Gi̇zli̇li̇k Düşüncesi̇ (taki̇yye) - Benras, Mahmoud (Kilis 7 Aralık Üniversitesi İlahiyat Fakültesi Dergisi, 2022)
Hariciyye’nin bir alt kolu olan İbadiye, temelde bazı sosyo-politik sebeplerle kendini yenileyerek günümüze kadar varlığını sürdürebilen az sayıdaki İslâm mezheplerinden biridir. Günümüzde İbadiyye mezhebi doğuda Umman Sultanlığı, batıda Kuzey Afrika ve Tanzanya gibi farklı coğrafyalara yayılmış durumdadır. Orantısal olarak değerlendirildiğinde İbadiler ile ilgili yapılan araştırmaların diğer mevcut ve mensubu kalmamış mezheplere nispetle daha az olduğu görülmektedir. Bu durum mezhebin sahada yeteri kadar bilinmemesine hatta yanlış bazı değerlendirmelerde bulunulmasına sebep olmaktadır. İbadiyye, hicri birinci yüzyılda meydana gelen ve özellikle Büyük Fitne olayları diye anılan Sıffin Savaşı ve sonrasındaki gelişmelere bağlı olarak ortaya çıkan dinî bir gruptur. Bu grup ilk dönemde Haricilerin yanında yer alırken süreç içerisinde fikren ve siyaseten onlardan ayrılmıştır. Hariciler erken dönemden itibaren tarih sahnesinden silinmelerine rağmen İbadiler günümüze değin varlıklarını sürdürmeyi başarmışlardır. Çoğu araştırmacı, İbadilerin hâlâ Haricilerin bir kolu olarak varlıklarını sürdürdüklerini düşünmektedir. Dünyada birçok dini fırka ve mezhep açıktan veya saklı faaliyet gösterme fikrini benimsemiştir. Bu husus, ahlakî açıdan olumsuz bir durum olarak görünse de benzer nitelikler Şiî, Batınî vb. diğer Müslüman gruplar arasında da yaygın olarak mevcuttur. Dini akım yahut grupların, mensubu bulunduğu dinin diğer mensuplarından kendilerini farklı görmeleri hatta diğer akım veya mezhep müntesiplerini ötekileştirme süreçleri, kimi bilginler tarafından bir tür gerçekten uzaklaşma veya yalanı ve ikiyüzlülüğü meşru kabul etme olarak nitelendirilmektedir. Aynı zamanda bu durum çevresindekileri bir tür aldatma, kandırma ile neticeleneceği için bir fırkaya veya mezhebe intisabın zorunlu bir gereği olarak da değerlendirilemeyeceği yorumu yapılmaktadır. Öte yandan takiyye olgusu dinî açıdan olumlu bir arka plana sahiptir. Örneğin takiyye sayesinde din, dolayısıyla da insan ve toplum birtakım tehdit ve tehlikelerden korunabilir. Ancak bu müspet olgunun yalan ve ikiyüzlülüğe bulaştığı ithamlarına muhatap olması, dinin maksadı dışında farklı hedefler için kullanıldığını göstermektedir. Dinde takiyyenin hedefi insanı, toplumu ve dini korumaktan ve ahlaki olarak geliştirmekten öte bir şey olduğu söylenemez. Bazı İslam mezhepleri takiyyeyi anılan bağlam içinde makul bir seviyede ele alıp uygularken, bazıları da ifrat derecesinde aşırılığa kaçmaktadırlar. Bu çalışmada İbâdiyye mezhebinin siyasi düşüncesindeki temel meselelerinden olan takiyye konusundaki yaklaşımları başta olmak üzere onların takiyye yapıp yapmadıklarını, imamet ve yönetim konularındaki bakış açılarını ve diğer sünnî veya sünnî olmayan mezheplerle karşılaştırmalı olarak ele alacağız. İbâdiyye’nin bu güne kadar varlığını sürdürebilmesinin başlıca nedenleri arasında takiyye yapmış olmaları da söylenebilir. Öyle ki, tarih boyunca birçok kültürel ve askeri saldırıya maruz kalmasına rağmen muhtelif coğrafyalarda kesintisiz bir şekilde yaşayabilmişlerdir. Bazı dönemlerde diğer Müslüman gruplardan kendini izole ederek yaşasa da geçmişte olduğu gibi bugün de diğer mezhep müntesipleriyle barış içinde bir arada yaşamaktadır. İlaveten aşırılıkçı bir siyasi ideolojiye sahip olan Hariciyye mezhebine bağlı olmasına rağmen İbâdîler, tarihi süreçte düşünce yapılarında ve yaklaşım tarzlarında kısmen ılımlılık havasına büründükleri görülmüştür. Kısaca İbâdîler, Haricilerle tarihsel birlikteliklerine rağmen, özellikle itikadi ve siyasî düşüncelerini hayata geçirmede Haricilerden ayrılmışlardır. Bununla birlikte İbâdî siyasî düşüncesi birtakım özelliklerle ayırt edilir ve bunların en önemlileri şunlardır: Birincisi: İbâdî siyasî düşüncesi zahire dayalıdır. Yani içinde Bâtınî yahut ezoterik unsurları taşımayan açık bir düşüncedir ve hicretin birinci ve ikinci asırlarında ortaya çıktığı andan itibaren Haricî düşünce ile benzerlikler taşısa da pek çok temel noktada farklıdır. Öte yandan siyasi düşüncede İbâdîler ile Haricilerin birleştirilmesi de yanlıştır. İkincisi: İbâdîler, mutedil sayılan ve Ehl-i sünnet’in düşüncesine yakın kabul edilebilecek İslâmî bir gruptur. Çünkü muhaliflerini, Haricilerde olduğu gibi kâfir ve gayrimüslim saymazlar, kanaatimizce İbâdiyye mezhebinin günümüze kadar varlığını sürdürmesinin temel sebebi budur. Zira İslam tarihinde aşırılıkçı yaklaşıma sahip İslâm mezheplerinin çoğu zamanla yok olmuştur. Üçüncüsü: İbadilerin Takiyye fikrini ölçülü kullandıklarını ve onu dinin esaslarından biri olarak da görmediklerini ifade etmek gerekir. Aksine onlara göre takıyye dini, bireyi ve toplumu korumayı amaçlayan, bir olgudur.

المكتبات العائليّة الخاصّة بجزية جربة المكتبة البارونيّة أنموذجاً - بن يوسف, سعيد (فنون الخط: ذاكرة مشتركة وتراث حي وفن متنوع, 2022)
OCLC: 1549664612

The excavations: Schnitt 8 – ein heiligtum der isis? - Apatsidis, Marina; Köppe, Alexander; Ritter, Stefan; Scheding, Paul (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2017, 2022)
Number: 43
Keywords: Archéologie – Djerba

Les mosaïques romaines de Meninx - Arndt, Robert C. (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

The excavations: Trench 5 – a late roman domestic building - Arndt, Robert C.; Kerschbaum, Saskia (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

The excavations: Trench 4 – early punic occupation and roman forum - Arndt, Robert C.; Stoeßel, Linda; Gabler, Lena; Aoudi, Mekki (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2016, 2022)
Number: 43
Keywords: Archéologie – Djerba

The quarries - Beck, Dennis Mario (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

La céramique - Ben Tahar, Sami; Mansel, Karin; Mukai, Tomoo (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Liste des datations des unités stratigraphiques (SE) de Meninx 2017–2018 - Ben Tahar, Sami; Mansel, Karin; Mukai, Tomoo; Assirelli, Francesca; Mancini, Bianca (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2015, 2022)
Number: 43
Keywords: Archéologie – Djerba

Appendix: The radiocarbon analyses - Dinies, Michèle; Fiederling, Max (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Crop cultivation and land-use on djerba from phoenician times to late antiquity (4th cent. B.C.–6th cent. a.D.): a synthesis of first archaeobotanical investigations - Dinies, Michèle; Podsiadlowski, Viola; Neef, Reinder (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Ceramics and other finds from the underwater archaeological investigations - Fiederling, Max (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

The underwater archaeological investigations (with trenches 10–12) - Fiederling, Max; Pflederer, Tobias; Gadhoum, Ahmed (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2018, 2022)
Number: 43
Keywords: Archéologie – Djerba

Ein marmorkopf des antoninus pius aus meninx - Gabler, Lena (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

The coin finds - Kerschbaum, Saskia (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Fragmentierte Skulptur: ein monumentaler Kopf des Serapis vom antiken Forum - Kovacs, Martin; Lipps, Johannes (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

The Excavations: Secteur 2 – Une maison punique et son occupation jusqu’à la fin de l’Antiquité - Lamare, Nicolas (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

The Excavations: Secteur 9 – Des citernes publiques et un complexe industriel - Lamare, Nicolas (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

The excavations: Schnitt 3 – ein thermengebäude am forum - Lehnert, Christoph; Ritter, Stefan (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Architekturhistorische untersuchungen in meninx – die bauteile im pavillon - Lipps, Johannes (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Die funde: Einführung - Mansel, Karin (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Kleinfunde aus metall, bein und stein - Ortisi, Salvatore (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Wandmalerei und bemalter Stuck aus Meninx - Ritter, Stefan; Scheding, Paul; Kranz, Sebastian (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Le terracotte architettoniche: antefisse italiche e locali dal Foro - Scheding, Paul (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Die glasfunde aus meninx - Schmittner, Stephanie (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Römische statuetten aus den thermen (schnitt 3) - Schöpflin, Bartlin (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

The excavations: Trench 1 – a main road through meninx in the area of the macellum - Sheldrick, Nichole (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

The excavations: Trenches 7 and 13 – a cross-section of meninx’s urban core - Sheldrick, Nichole (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

The excavations: Schnitt 6 – die forumsbasilika - Stoeßel, Linda (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Ton-model in form eines equiden - Thois, Julia (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Archaezoology in meninx: Palaeoeconomy between local economic structure and supra-regional network - Trixl, Simon; Peters, Joris (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Fish exploitation at meninx - Van Neer, Wim; Wouters, Wim; Trixl, Simon (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

Der nördliche zisternenkomplex – bauforscherische untersuchung der freiliegenden strukturen - Wolf, Kilian (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Number: 43
Keywords: Archéologie – Djerba

The Urban History of Meninx: A Synthesis of our Results - Ritter, Stefan; Ben Tahar, Sami (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie – Djerba

The Urban Layout: Results of the Magnetometer Survey - Fassbinder, Jörg W. E.; Ritter, Stefan (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie – Djerba

The Database Management - Scheding, Paul; Watson, Juliane (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie – Djerba

Archaeological Geophysics - Fassbinder, Jörg W. E. (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie – Djerba

Engineering Geodesy in Meninx - Weinhuber, Agnes (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie – Djerba

Introduction: The History of Research on Meninx and our Objectives - Ritter, Stefan; Ben Tahar, Sami (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie – Djerba

La Régence de Tunis au XVIIIe siècle: le mémoire de Guy de Villeneuve - Villeneuve, Guy de (L'Harmattan, 2022)
Keywords: Artisanat – Djerba; Commerce – Djerba; Récits de voyage – Djerba

‘Ridiculous Falsehoods’: Archival Sources on Women in Nineteenth-Century Oman - Curstaidh, Reid (Qatar Digital Library, 2022)
Archival records on the Qatar Digital Library can help to challenge traditional assumptions and paint a fuller picture regarding the role of women in nineteenth-century Oman.

Comment rester zénète sans le savoir ? Ferment d'une berbérité non revendiquée - Planeix, Ariel (Comment peut-on être Berbère ? amnésie, renaissance, soulèvements, 2022)
Keywords: Zkaras – Maroc

نماذج من تقارير الوكيل التونسي أحمد المهدوي ومراسلاته حول الأوضاع الادارية والاقتصادية والتركات التونسية ببنغازي 1875-1879م - العلام, هدى عبدالرحمن (مجلة العلوم الإنسانية (جامعة سبها), 2022)
فرضت الطبيعة الجغرافية لمنطقة برقة ، فضلاً عن جهود الحركة السنوسية في تيسيرها  لطريق تجاري آمن مع بلاد السودان ، ومتزامن مع الخبرة التراكمية لغالبية مكونات مجتمعها المنخرط في تلك التجارة . فكان الطريق التجاري الشرقي الذي يبدأ من بنغازي عبر جالو وأوجلة والكفرة إلى أبشة بوادي (في تشاد الحالية) هو الطريق المقصود. ناهيك استمرار تبادل السلع المحلية والعربية والدولية بين الجانبين عبره. وعليه كانت متصرفية بنغازي محط أنظار التجار المحليين من ولاية طرابلس الغرب وتجار تونس الذين دللت عنهم عينة من الوثائق البكر غير المنشورة عثرنا عليها في الأرشيف الوطني التونسي. فهذه العينة من الوثائق خاصة في ملف الوكيل أحمد بن محمد المهدوي وكيل الدولة التونسية في بنغازي.        يقوم موضوع هذا البحث على تخصيص عمل الوكيل التونسي أحمد بن محمد المهدوي  في بنغازي ، وتحليل ما ورد في تقاريره ومراسلاته غير المنشورة حول الاوضاع الإدارية والاقتصادية والصحية. فضلاً عن التركات التونسية في بنغازي باعتبارها تركات لتجار تونس من جربة وصفاقس ممن امتهنوا التجارة مع واداي ، والرحالة الأوروبيين الذين مروا من هذا الطريق للوصول عبره إلى واداي. فأهمية هذه التجارة وقيمة تركات تجار تونس قد أوجدت منازعات بين وكيل الدولة التونسية مع صندوق الايتام وبيت مال الولاية الطرابلسية ومتصرفية بنغازي في ضم تلك التركات لها من عدمه. أما عن أهمية هذا البحث فهو يُرَكَّز على دراسة مجال العلاقات الطرابلسية البرقاوية التونسية في سبعينات القرن التاسع عشر.

اشكاليات تنمية مدينة ستون تاون في زنجبار تنزانيا تجربة اليونسكو وتحدياتها في الفترة من 2000-2016 - حسين, احمد عبد الدايم محمد (مجلة دراسات افريقية, 2022)
يعد موضوع « اشكاليات تنمية مدينة ستون تاون في زنجبار تن ا زنيا.. تجربة اليونسكو وتحدياتها في الفترة من 2000 - « 2016 جديدا في طرحه، فلم تكن هناك أي د ا رسات سابقة تناقش مسألة تنمية هذه المدينة واشكاليات تجربة منظمة اليونسكو في تطويرها. فبالنظر لتلك الوثائق الصادرة عن لجنة الت ا رث العالمي ومناقشاتها لتحديات التنمية في مدينة ستون تاون، نجد أنَّ شكاوى اليونسكو تنحصر في عدم قيام الحكومة التن ا زنية بواجباتها المتفق عليها سلفًا، بسوء حفظ المباني التاريخية، وعدم إخاء المعرض منها لخطر الانهيار، وعدم معالجة حركة المرور. ناهيك عن عدم فعالية هيئة م ا رقبة التنمية الحضرية في تحسين آليات التصاريح وتعزيز الرقابة على الممتلكات وفي المنطقة العازلة. فضاً عن وجود تعارض بين سلطة مدينة ستون تاون ومجلس بلدية زنجبار. وجاء اعت ا رف حكومة تن ا زنيا عام 2017 بعدم كفاية الموارد البشرية والمالية وبن ا زعات السلطات الإدارية المختلفة، وعدم تنفيذ م ا رقبة عملية التنمية، ليشكل بيت القصيد في تحديات التنمية التي تطلبها تن ا زنيا. وعلى هذا يهدف الموضوع إلى رصد خطة التنمية المستدامة لمدينة ستون تاون واشكالياتها، والمعوقات التي أخرت اليونسكو في إنجاح تجربتها. مستفسرة عن الأسباب الحقيقية التي عطلت المشروع؟ وكيف يمكن تلافيها في المستقبل؟ وفي هذا الإطار قسمت الد ا رسة إلى أربعة محاور رئيسة:-أولً- الخلفية التاريخية لمسار التنمية فيستون تاون في المدة من 1923 - 1999 .ثانيًا- ملف تنمية ستون تاون

الموضوعات الشعرية في شعر الخوارج - الجباري, خبات نجاة محمد محمد (مجلة جامعة كركوك للدراسات الانسانية, 2022)
تهدف هذه الدراسة إلى تسليط الضوء على سبب تسمية الخوارج بهذا الاسم وكذلك الوقوف على أبرز موضوعاتهم الشعرية التي برعوا فيها دون غيرها وسبب تأكيدهم على هذه الموضوعات دون غيرها، لذا قسم البحث إلى مبحثين أساسيين مبحث أول في رصد موضوعات تفرد بها شعراء خوارج ومبحث ثانٍ في الموضوعات والأغراض التقليدية، وكذلك تسليط الضوء على بعض التغيرات في مقدمات القصائد عندهم وعدم الاهتمام بها، كما أن شعرهم مال إلى القصر في الأبيات، كما وتهدف الدراسة إلى اثبات أن جل الموضوعات الشعرية قد بدت عليهما تغيرات واضحة عند الخوارج ورصد هذا الأمر، وجعل المنظوم الشعري بموضوعاتها كافة في سبيل الدعوة الخارجية فقط، وكان من نتيجة ذلك ابتعادهم عن بعض الموضوعات التي لا تخدم قضيتهم ولا تتماشى مع دعوتهم كشعر العصبية القبلية والنقائض بالرغم من انتشارهما في العصر الأموي بكثرة، وبذا أصبح شعرهم كلاً واحداً متشابهاً لأنه يصب في خدمة قضية واحدة وفكرة موحدة، ألا وهي إعلاء عقيدة الخوارج التي يؤمنون بها .
Keywords: Poésie kharijite

الحياة السياسية في الجزيرة الفراتية خلال العصر العباسي الاول ( حركات الخوارج انموذجاً ) - السامرائي, عمر ساجد مخلف; اسماعيل, لقاء خليل (دراسات موصلية, 2022)
ان السياسة التي اتبعتها الدولة العباسية منذ الوهلة الاولى في حروبهم مع الدولة الاموية واتباعهم الشدة والقسوة في القضاء عليها كان لها الأثر السلبي على البيت العباسي خاصةً في الجزيرة الفراتية، الامر الذي…
Keywords: Kharijisme

أساليب الدولة الأموية في مواجهة فرقة الخوارج - السلطاني, حيدر عامر هاشم (مجلة كلية التربية الأساسية للعلوم التربوية والإنسانية, 2022)
الموضوعات الشعرية في شعر الخوارج
Keywords: Kharijisme

دور بنو مازن في الخوارج من سنة ٦١ه - ٧٩ /٦٨٠-٦٩٢م - كاظم, عدنان خلف; مسير, ايمان نومان (مجلة ديالى للبحوث الانسانية, 2022)
جاءت دراستنا حول موضوع بنو مازن ودورهم في الخوارج ، وهم فرقه دينية خرجت على الامام علي بن ابي طالبt بعدة قبوله التحكيم في معركه الصفين وقاتلهم اشد قتال في واقعه النهروان سنه ٣٨ ه. ولقد كان لبني مازن دور…
Keywords: Kharijisme

إصلاح خطاب السلطة للجماعات المتطرفة في ضوء مناظرة ابن عباس للخوارج - كاظم, ليث مزاحم خضير (مجلة حمورابي للدراسات, 2022)
تعد كثير من الجماعات المتطرفة اليوم امتداداً لتجربة الخوارج وتصوراتهم عن الدين والدولة والمجتمع ونظام الحكم، وعلى الرغم من التباينات الملحوظة بين الخوارج المبكرين والمعاصرين؛ فإن وجوه التشابه المفاهيمي…
Keywords: Kharijisme

التعايش الديني في تونس: الإباضيّة واليهوديّة في الجنوب الشرقي نموذجا - بنجدو, عبد الستار (ندوة المدينة: الدورة الثانية الإنسان والأديان, 2022)

العادات الغذائية أثناء طقوس العبور في جزيرة جربة: الزواج التقليدي نموذجا - بن صالح, عماد (التغذية في تونس والمغرب: مقاربات أنثروبولوجية : الجزء الثاني من أوراق الندوة العلمية "الأطعمة والإطعام والتراث الغذائي : مقاربات متعددة الاختصاصات"، 11 و12 جانفي 2022، المنستير-تونس, 2022)
Keywords: Moeurs et coutumes – Djerba

Not a Happy History — Italy & Libya - Wright, John (The Maghreb Review, 2022)
Italy “ruled” Libya for 32 years (1911–43), and both still largely resent the experience. Italy, “the least of the Great Powers”, lacked the necessary capacity and experience to conquer and rule foreign colonies, particularly one as poor and unpromising as Turkish North Africa — the “Crate of Sand”. And Libyans, far from welcoming Italians as “liberators from Turkish oppression” defended their own for years of violent “anti-colonial struggle”, and particularly against Italian fascist ideology. Episodes and personalities from that conflict have since been appropriated by successive Libyan regimes to enhance their own historical legitimacy and contemporary credibility, while some modern Italian historians have also manipulated Italo-Libyan historical memories. Italy’s passive acceptance of the resultant historical “guilt” seems partly intended to ensure continuing access to Libyan resources, as well as better management of the flow of African migrants across the central Mediterranean.
Keywords: Invasion italienne – Libye

Conquering Libya (1911–1932): A Crusade? - Cresti, Federico (The Maghreb Review, 2022)
When the Italian government decided to conquer Libya, the military expeditionary force was instructed to avoid any action that could be interpreted as an affront to the religion of the population. However, in the course of military operations, several Muslim religious buildings were damaged or destroyed and Ottoman propaganda presented the aggression as a Christian attack on Islam. The resistance against the occupation soon took on the characteristics of holy war, its main leaders raising the banner of the jihād.
Keywords: Invasion italienne – Libye

Mitochondrial DNA Variation in Southern Tunisian Populations - Capocasa, Marco; Battaggia, Cinzia; Cancellieri, Emanuele; Lisi, Alessandro; Polimanti, Mattia; Boukhchim, Nouri; Bisol, Giovanni Destro; Lernia, Savino di; Anagnostou, Paolo (Human Biology, 2022)
Due to its complex history of migrations and colonization of African, European, and Asian people, the Tunisian territory is an ideal area to study the effects of cultural change on the genetic structure of human populations. This study investigated genetic variation in the mitochondrial DNA of Tunisian populations to detect the possible impact of recent historical events on their gene pool. Two Arab and three Berber communities were analyzed using a comparison data set of 45 other populations comprising African, Arabian, Asian, European, and Near Eastern groups. Results were compared with those produced using a large panel of autosomal single-nucleotide polymorphisms. We observed a slight but important difference between the populations that inhabit the southern and central-northern areas of Tunisia. Furthermore, robust signatures of genetic isolation were detected in two Berber populations (Nouvelle Zraoua and Tamezret) and in the R’Baya people, a seminomadic Arab group. This investigation suggests that the genetic structure of investigated southern Tunisian populations retains signatures of historical events that occurred between the 7th and 17th centuries, particularly the trans-Saharan slave trade and the emigration of Berbers in remote areas of the south during the Arab conquest.
Keywords: Biologie – Tunisie

Le fort, Borj El Kébir le fort espagnol, Borj Ghazi Mustapha Sidi Saad - Gritli Gaddour, Maherzia (Al-Jazira | الجزيرة, 2022)
Keywords: Ghazi Mustafa; Burj (Houmt-Souk; Djerba); Moeurs et coutumes – Djerba

Territoire et patrimonialisation en Tunisie: enjeux de pouvoir ? - Bielawski, Mathilde (Université de Lyon, 2022)
Le présent travail de recherche se veut être une étude critique du « patrimoine culturel tunisien » en contexte « post-printemps arabe ». L’objectif est d’enrichir les connaissances sur le domaine de la conservation et de la gestion du patrimoine en Tunisie. C’est afin de mieux comprendre le contexte actuel dans ce domaine que la réflexion s’oriente autour de l’articulation des pouvoirs nationaux (institutions étatiques) et d’une nouvelle « société civile postrévolutionnaire » — notamment à travers les associations dites « de sauvegarde du patrimoine » — comme nouveaux enjeux des pays en transitions et mutations politiques et économiques. Cette étude anthropologique s’est déroulée de 2014 à 2020. Elle s’est concentrée sur le suivi du processus d’inscription de l’île de Djerba en Tunisie sur la Liste du patrimoine mondial de l’Unesco, afin d’amener à comprendre les enjeux de gouvernance territoriale en contexte « postrévolutionnaire ». Les enquêtes réalisées entre Tunis la capitale et l’île de Djerba au sud du pays, se sont intéressée aux relations entretenues entre les institutions d’État responsables du dossier et l’Association de Sauvegarde de l’Île de Djerba (Assidje), partenaire de l’État tunisien sur ce projet. Cela a permis d’étudier un « patrimoine culturel » en train de se « fabriquer » et d’en saisir les enjeux de gouvernance territoriale qui y sont liés. The research area of this work is the critical heritage study of “Tunisian cultural heritage” in the “post-Arab Spring” context. The objective is to contribute to the knowledge of the field of conservation and management of cultural heritage in Tunisia. To better understand the current context in this field, the study focuses on the articulation of national powers (state institutions) and a new “post-revolutionary civil society” - in particular through the so-called “heritage preservation associations” - as new challenges for countries undergoing political and economic transitions and changes. This anthropology study took place from 2014 to 2020. It focused on the monitoring of the process of inscription of Djerba island in Tunisia on the Unesco World Heritage List, to understand the issues of territorial governance in a “post-revolutionary” context. The investigations carried out between the capital Tunis and Djerba island in the south of the country, focused on the relations maintained between the State institutions in charge of the case and the Association for the Safeguarding of Djerba Island (Assidje), a partner of the Tunisian State on this project. This allowed us to analyse a “cultural heritage” in the process of being “made” and to understand the issues of territorial governance that are linked to it. يضع هذا البحث في صلب اهتمامه قراءة نقدية للتراث الثقافي التونسي ما بعد الربيع العربي. يهدف هذا البحث ايضا الى اغناء مجال المعرفة حول المحافظة على التراث الثقافي في تونس وتدبيره. ولهذا الغرض، ارتأينا دراسة مؤسسات الدولة و جمعيات المجتمع المدني التي تعنى بالمحافظة على التراث كمعيار لدولة في وضعية انتقالية ومن اجل انجاح هاته الدراسة، تم الاعتماد على منهجية انتروبولوجية و دراسة ميدانية ما بين 2014 و 2020 هدفها تتبع عملية تسجيل جزيرة جربة في تونس في قائمة التراث العالمي لليونسكو، من أجل فهم تحديات الحكم الإقليمي في سياق "ما بعد الثورة". اهتمت الدراسات الاستقصائية المنجزة بين العاصمة تونس وجزيرة جربة جنوب البلاد بدراسة العلاقة بين مؤسسات الدولة الساهرة على الملف وجمعية المحافظة على جزيرة جربة، شريك الدولة التونسية في هذا الملف. هذا يسمح لنا بدراسة التراث الثقافي في عملية "صنعه" وفهم التحديات ذات الصلة بالحكامة المحلية
Keywords: Monuments – conservation – Djerba

La pêche: un modèle de gestion des ressources maritimes - Ben Tahar, Sami (Djerba à la carte, 2022)
Keywords: Pêche – Djerba

L'artisanat et le savoir-faire: la créativité djerbienne - Ben Tahar, Sami (Djerba à la carte, 2022)
Keywords: Artisanat – Djerba

Souks et marchés: la vie d'antan - Ben Tahar, Sami (Djerba à la carte, 2022)
Keywords: Commerce – Djerba

Architecture coloniale: entre modernité et modestie - Ben Tahar, Sami (Djerba à la carte, 2022)
Keywords: Architecture – Djerba

Musulmans, juifs et chrétiens: l'heureuse cohabitation - Prevost, Virginie (Djerba à la carte, 2022)
Keywords: Tolérance religieuse – Djerba

Djerba: île protégée - Barbou, Moncef (Djerba à la carte, 2022)

Histoire générale de Djerba - Ben Tahar, Sami (Djerba à la carte, 2022)
Keywords: Djerba – Histoire

Vivre à Djerba: paysage et habitation, évolution de l'organisation de l'espace djerbien à travers les époques - Barbou, Moncef (Djerba à la carte, 2022)
Keywords: Urbanisme – Djerba

Introduction - Sellami, Samir (Djerba à la carte, 2022)

Préface - Trabelsi, René (Djerba à la carte, 2022)

Djerba à la carte - Sellami, Samir (Fondation Tunisie pour le développement, 2022)

دلالة النهي على فساد المنهي عنه عند الأصوليين وتطبيقاتها الفقهية عند الإمام السالمي (ت : 1332هــ) - الحبسي, مروان بن محمد بن سرحان (كلية العلوم الشرعية, 2022)

الشخصية المتوازنة في السنة النبوية من خلال مسند الإمام الربيع بين حبيب (ت: 175هـ) - الغماري, سيف بن علي بن سعيد (كلية العلوم الشرعية, 2022)

القواعد والضوابط الفقهية وتطبيقاتها عند الإباضية من خلال مدونة أبي غانم الخراساني ق (2هـ) - المقيمية, راية بنت حمود بن سبيت (كلية العلوم الشرعية, 2022)
Keywords: Fiqh – Libye – 8e siècle

نخبة المتين من أصول تبغورين لعمرو بن رمضان التلاتي الجربي (ت: 1187 هـ) دراسة وتحقيقا - سليمان, حنان بنت عبد العزيز (كلية العلوم الشرعية, 2022)

الإصلاح المجتمعي وأثره على الدعوة من خلال جواهر التفسير لسماحة الشيخ أحمد الخليلي - الرواحي, إسحاق بن عبد الله بن خميس (كلية العلوم الشرعية, 2022)

The libraries of Nafusa Documentation and digitization of the written material heritage in the Jebel Nafusa, Libya - Mazawi, Ali; Tounsi, Slimane; Love Jr, Paul M. (2022)
In collaboration with the Centre for Studies and Research on Ibadism (Ibadica), Slimane Tounsi, President of Ibadica, Ali Mazawi, Coordinator of “The Libraries of Nafusa” project in Libya, and Paul Love, Professor of History and Academic Coordinator of “The Libraries of Nafusa" project, will offer a description of the planning, implementation, and future aims of the pilot project "The Libraries of Nafusa" (2021–2022), which sought to document and to digitize written material heritage in the Jebel Nafusa in Libya. “The Libraries of Nafusa” was a pilot project (2021–2022) to document and to digitize written material culture in the Jebel Nafusa region of Libya. It was led by the Ibadica, Centre for Studies and Research on Ibadism, in France and the Fassato Foundation in Libya, with financial support from the Gerda Henkel Stiftung “Patrimonies” funding program in Germany. The administrative team reflects the international nature of the project, with members based in Algeria, France, Morocco, Tunisia, and the United States.
The Islamic Manuscript Association
Keywords: Bibliothèques – Djebel Nefousa; Manuscrits – Djebel Nefousa

دراسات في المذهب الإباضي وبعض أعلامه - الرزيقي, جمعة محمود (دار تيرا للطباعة والنشر والتوزيع, 2022)

العرف في المجتمع المزابي بقصر غرداية - بوحديبة, عزيزة بنت عيسى (جمعية الإصلاح, 2022)
Keywords: Droit coutumier – Mzab; Moeurs et coutumes – Mzab

تخريج الفروع على الأصول عند السالمي (1284-1332 هـ) العام والتخصيص أنموذجا - حاجي, عيسى إبراهيم (جامعة السلطان قابوس كلية التربية, 2022)

الشورى عند الإباضية " تنظيرا و تطبيقا " - البحرية, جواهر بنت عبد الله بن سعيد بن عبد الله (كلية العلوم الشرعية, 2022)
Keywords: Idées politiques – Ibadisme

اوران: مشروع مقترح لتنظيم الكفارات وتعزيز التكافل الاجتماعي - بن يحى, علي صالح; بابا وموسى, محمد أحمد (دار نزهة الآلباب, 2022)
Keywords: Développement durable – Mzab

‏المرأة عند الشيخ لطفيش بين تحديات الماضي وأشكالات الحاضر - بضليس, ليلى بنت عمر (المؤلفة, 2022)

تينفاس ن آت مزاب = قصص مزابية = Contes M'zabites: 12 قصة من التراث المزابي - العلواني, مصطفى بن كاسي (دار نزهة الآلباب, 2022)
Keywords: Littérature – Mzab

أسرداس وورغ: الجندي الذهبي الشيخ الأخضر بن أحمد قارة رحمه الله 1918-2020 - ترشين, صالح بن عمر (جمعية التراث, 2022)
Keywords: Biographies – Mzab – 20e siècle

الآراء الأصولية لعامر بن علي الشماخي (ت: 792هـ/1389م) من خلال كتاب الإيضاح باب العبادات - تجرونة, صفية بنت ابراهيم (جمعية الإصلاح, 2022)
Keywords: Fiqh – Libye – 14e siècle

شذرات إسلامية: ‏كتاب الطهارات: الباب الأول الوضوء - الصوافي, حمود بن حميد (2022)

شذرات إسلامية: ‏كتاب الطهارات الباب الرابع النجسات والطرق إزالتها - الصوافي, حمود بن حميد (154, 2022)

شذرات إسلامية: ‏كتاب الطهارات الباب الثاني الغسل من الجنابة الباب الثالث التيمم - الصوافي, حمود بن حميد (2022)

‏الشيخ إبراهيم بن بكر حفار من خلال تراجم الثلاث - أبو اليقظان, إبراهيم بن عيسى; طلاي, إبراهيم بن محمد; الداغور, إبراهيم بن صالح (مؤسسة الشيخ عمي سعيد, 2022)

‏الشيخ إبراهيم بن بكر حفار حياته وأثاره (1890-1954): مقتبس من مذكرات تخرج ليسانس علوم الشرعية من معهد عمي سعيد للدراسات الإسلامية والحضارية - بن عدون, أحمد بن محمد; عبد الرحمن, بكير بن محمد (مؤسسة الشيخ عمي سعيد, 2022)

‏المدرسة القرآنية ببلدة آت مليشت (مليكة العليا): من سنة 1340هـ/1922م إلى سنة 1356هـ/1938م ‏مسيرة علمية وجهود مباركة - باعمارة, سليمان بن أحمد; باعمارة, بكير بن سليمان (‏مكتبة السلف, 2022)

مسرح في منطقة تربلا في جربة، منطقة تحميها اتفقاية رمسار - الرزقي, أيمن (2022)
مسرح في منطقة تربلا في جربة، منطقة تحميها اتفقاية رمسار. اليوم نضحيو بالبيئة على خاتر الثقافة و الا نحافظو عليهم الاثنين. ايمن رزڨي من نواة يجي بحذانا بش...
Keywords: Crises environnementales – Djerba; Vie culturelle – Djerba

A Paradoxical Pilgrimage. The Ghriba Synagogue in Djerba - Albera, Dionigi; Pénicaud, Manoël (Religiographies, 2022)
In North Africa, the long-term coexistence between Jews and Muslims generated many interfaith crossings. It was not uncommon for the followers of one religion to visit a shrine of the other, in order to obtain baraka (divine grace). This phenomenon has mostly disappeared throughout the Maghreb, but it persists on the island of Djerba (southern Tunisia), where over a thousand Jews are still living. Every year, for the Jewish holiday of Lag Ba’Omer, a pilgrimage gathers together thousands of Jewish pilgrims in the Ghriba synagogue. Many come from abroad, notably from France and Israel, where many Tunisian Jews migrated after the mid-20th century. Some Muslims also participate at different moments of the pilgrimage. Based on historical research and on ethnographic work carried out in 2014 and 2022, this article elucidates a series of paradoxes that make the singularity of this holy place. Here the interactions between Jews and Muslims at the shrine are characterized by an intense conviviality. Yet, during the last decades this site has been affected by tangible eruptions of bloody violence by Islamist terrorists. The structure of the pilgrimage seems to rest on a delicate balance between local and external forces. More generally, the Ghriba pilgrimage is crossed by major political dynamics, and is recurrently affected by the turmoil of the Israeli-Palestinian conflict.
Keywords: Judaïsme – Djerba

Sommet de la cacophonie - Z (Debatunisie, 2022)
Keywords: Crises environnementales – Djerba; Vie culturelle – Djerba

شجرة الثقافة التي تخفي غابة الفساد - الرزقي, أيمن; الكوساني, سيف (نواة, 2022)
شروع ثقافي سياحي خاص ضخم، على أرض رطبة محمية باتفاقية "رامسار" الدولية. كيف تم الأمر؟ وأين حرص الدولة في الحفاظ على المحميات؟ وهل تجيز الثقافة الاعتداء على المحميات الرطبة؟ أم أن المشروع سليم ولا يستدعي احتجاجات نشطاء البيئة؟
Keywords: Crises environnementales – Djerba; Vie culturelle – Djerba

‏ماني لا كانغ = أين نحن؟ - خبزي, موسى بن محمد (جمعية التراث, 2022)

في رحاب السنة: شرح الجامع الصحيح للإمام الربيع بن حبيب - المرموري, الناصر بن محمد (جمعية التراث, 2022)
Keywords: Hadith – Exégèse – Mzab

الأديب الذهبي: المرحوم صالح بن الحاج إبراهيم باجو (١٩٣٠-٢٠١٥م) - ترشين, صالح بن عمر (جمعية التراث, 2022)
Keywords: Biographies – Mzab – 20e siècle

‏خليفة بن عسكر: قائد الجهادين - العزابى, مسعود عيسى (الفسيفساء, 2022)
Keywords: Biographies – Djebel Nefousa – 20e siècle; Invasion italienne – Libye

‏أصول الدين من كتاب التيسير التفسير لقطب الأمة الشيخ الحاج امحمد بن يوسف اطفيش - بافولولو, صالح بن داود (المركز العلمي للدين والشريعة الإسلامية, 2022)

ترجمة وثائق الوجود البرتغالي في منطقة أرخبيل الملايو: قلعة ملقا (١٦٤١ - ١٥١١م) (دراسة في ضوء جهود العُمانيين في ترجمة موسوعة الوثائق البرتغالية إلى اللغة العربية) - أحمد, هدى يعقوب (ترجمة التراث العماني الرؤى والآفاق, 2022)

ترجمة إنتاجات العالِم العُماني ودورها الحضاري (إنتاجات سماحة الشيخ أحمد الخليلي المفتي العام لسلطنة عُمان أنموذجًا) - البوسعيدي, أحمد بن سعيد بن خليفة (ترجمة التراث العماني الرؤى والآفاق, 2022)

الشيخ المترجم سعيد بن عبد اللّٰه بن سيف الحاتمي حياته وآثاره في التأليف والترجمة - الحوقاني, خليل بن محمد بن راشد (ترجمة التراث العماني الرؤى والآفاق, 2022)

جواب مسائل النصارى لابن أبي نبهان رحلتي في البحث عن السائل وعناية المستشرقين بالجواب - الخروصي, أحمد بن سالم بن موسى (ترجمة التراث العماني الرؤى والآفاق, 2022)

صيانة وحفظ التراث الثقافي المادي (إشكاليات الترجمة) - الخروصي, خالد بن سليمان بن سالم (ترجمة التراث العماني الرؤى والآفاق, 2022)

[ما وَصَلَنا مِنْ كِتَاب] مُبْتَدَأ الأَسْفَارِ في بَيَانِ نُبْذَةٍ يَسِيرَةٍ مِنْ لُغَةِ أَهْلِ زِنْجِبَار بالمشهور من اللغة العربية [معجم ثنائيّ اللغة: عربيّ - سواحليّ] صَنْعَة الشيخ العلامة ناصر بن أبي نبهان جاعد بن خميس الخروصي (1262ه) - الرمحي, أحمد بن محمد (ترجمة التراث العماني الرؤى والآفاق, 2022)

مساهمة الشيخ عيسى بن سالم بن محمد الرواحي في الكتابة والترجمة في زنجبار وشرق أفريقيا - الرواحي, محمد بن عيسى بن سالم (ترجمة التراث العماني الرؤى والآفاق, 2022)

المخطوطات غير العربية المحفوظة في الخزائن العمانية: دراسة إحصائية تحليلية - السعدي, فهد بن علي بن هاشل (ترجمة التراث العماني الرؤى والآفاق, 2022)
Keywords: Manuscrits – Oman

الترجمة البريطانية للنصوص العُمانية خلال القرن (١٩م) جسورٌ للتعارف أم أداة للهيمنة ؟ - السعدي, ناصر بن سيف (ترجمة التراث العماني الرؤى والآفاق, 2022)

العوامل التي ساعدت على تطور الترجمة في عمان (1804-1856م) - الشعيلي, محمد بن حمد (ترجمة التراث العماني الرؤى والآفاق, 2022)

أثر اللغة السواحلية في تآليف العُمانيين في المهجر الإفريقي قراءة في مخطوط «كنوز الأسرار في علم الأشجار والأحجار» - العيسري, محمد بن عامر (ترجمة التراث العماني الرؤى والآفاق, 2022)

ترجمة كتاب «مغامر عُماني في أدغال أفريقيا» تجربة ذاتية - المحروقي, محمد بن ناصر (ترجمة التراث العماني الرؤى والآفاق, 2022)

حاجتنا لترجمة تراثنا في عصر التعددية والعولمة - المعولي, زياد بن طالب (ترجمة التراث العماني الرؤى والآفاق, 2022)

العلاقات التاريخية العمانية الصينية دراسة تحليلية في نصوص الحوليات الصينية - الهادي, حبيب بن مرهون (ترجمة التراث العماني الرؤى والآفاق, 2022)
Keywords: Relations – Oman – Chine

أراجيز أحمد بن ماجد السعدي في اللغة الروسية - الهاشمي, سعيد بن محمد (ترجمة التراث العماني الرؤى والآفاق, 2022)
Keywords: Navigation – Oman

الدخيل في معجم المصطلحات البحرية بسلطنة عمان والخليج العربي - بن حمد, علي (ترجمة التراث العماني الرؤى والآفاق, 2022)

دور المستشرقين في ترجمة ونشر التراث العُماني = the role of orientalists in translating and publishing omani heritage - ضيائي, علي أكبر (ترجمة التراث العماني الرؤى والآفاق, 2022)

جهود العُمانيين في ترجمة موسوعة الوثائق البرتغالية (دراسة في ضوء حركة ترجمة التراث العُماني المعاصر، من اللغة البرتغالية إلى اللغة العربية) - علي, محمود محمد (ترجمة التراث العماني الرؤى والآفاق, 2022)

دور الترجمة في التواصل بين الثقافات - عناية, عز الدين (ترجمة التراث العماني الرؤى والآفاق, 2022)

حركة ترجمة معاني القرآن الكريم في آذربيجان في مثال كتاب «كشف الحقائق عن نكت الآيات والدقائق» لمير محمد كريم الباكووي - مصطفاييف, إيلنور (ترجمة التراث العماني الرؤى والآفاق, 2022)

‏واقع الدعوة النسوية في المجتمع الميزابي: هيئة تمسردين نموذجا - دودو, منة بايوب (مؤسسة تاضفي الوقفية ‏لتأطير وتكوينات العلمية, 2022)
Keywords: Moeurs et coutumes – Mzab

‏العدل بين الاولاد في الفقه الإسلامي دراسة فقهية مقارنة - دودو, لالة محمد الهادي (مؤسسة تاضفي الوقفية ‏لتأطير وتكوينات العلمية, 2022)
Keywords: Fiqh

الحقيقة بالوثيقة: عقود وخرائط ووثائق ملكية سيدي بنور : ترتيب زمني يرسم الخريطة العامة للوقف الإباضي الجزائري المزابي بجبل سيدي بنور، بلديتي باب الوادي وبوزريعة، الجزائر العاصمة - بن إبراهيم, عاشور الناصر (جمعية التراث, 2022)
Keywords: Waqf (fondations) – Alger

‏منهج الإباضية في تلقي الدين - بورورو, إبراهيم بن عمر (مؤسسة الشيخ عمي سعيد, 2022)
Keywords: Enseignement – Ibadisme

La vulnérabilité de l’île de Jerba (Tunisie) aux risques littoraux : approche cartographique - Akacha, Zahra (Méditerranée, 2022)
Les côtes basses sont connues pour leur grande vulnérabilité à l’élévation récente du niveau marin et les risques associés. Cette vulnérabilité est souvent accentuée par des enjeux socio- économiques. L’île de Jerba, appartenant à la façade orientale de la Tunisie, fait partie de telles côtes. Trois principaux risques la menacent : l’érosion marine, la submersion marine et la salinisation des terres. La vulnérabilité de l’île à de tels risques a déjà fait l’objet de nombreuses études (APAL, 2012 ; Oueslati et al., 2015 ; Oueslati, 2018). Mais les travaux ont porté surtout sur les côtes sableuses de la façade orientale et ont souvent été ponctuels dans le temps et dans l’espace et se sont intéressés avant tout à la question de l’érosion marine. Ce travail est une tentative de cartographie et d’analyse des risques menaçant l’île dans une conjoncture d’élévation du niveau marin en mettant en exergue la fragilité du cadre naturel. Il aboutit, en s’appuyant sur la méthode multicritères et des observations directes du terrain, à une carte de synthèse de la vulnérabilité de l’ensemble des rivages de l’île.
Keywords: Cartes – Djerba; Géologie – Djerba

Omani presence in East Africa - Popp, Georg (Demax GmbH, 2022)
Keywords: Relations – Oman – Afrique de l'Est

مسند الإمام الربيع بن حبيب الفراهيدي الأزدي (ت 175 هـ/791 م): دراسة تحليلية - السابعي, ناصر بن سليمان (مكتبة خزائن الآثار, 2022)
في الأصل رسالة جامعية (دكتوراه)–جامعة الزيتونة، الجمهورية التونسية،2021
Keywords: Hadith – recueils

La Penisola Omanita tra Preistoria e Protostoria attraverso lo studio di una collezione di manufatti archeologici - Ziglio, Micol (Universita degli Studi di Padova, 2022)
reserved
Keywords: Archéologie – Oman

Gathering Esculent Wild Plants in Dhofar: Prehistoric Practice Continued - El-Mahi, Ali Tigani (أدوماتو, 2022)
Keywords: Archéologie – Oman

Black Lives Matter, a Princess from Zanzibar, Bismarck, and German Memorial Hygiene - Neumann, K. (German Politics and Society, 2022)
Following the surge of the Black Lives Matter movement in the wake of George Floyd’s murder on 25 May 2020, memorials in remembrance of individuals implicated in colonialism or slavery have come under increasing attack. This article discusses and contextualizes challenges in 2020 to the memorialization of Otto von Bismarck (1815–1898) and Emily Ruete née Salama bint Said (1844–1924) in Hamburg, where the legacy of the German colonial past is particularly palpable. The article argues that proposed solutions—be it the demolition of the city’s main Bismarck monument, its restoration and the erection of a counter-memorial adjacent to it, or the un-naming of a street named after Ruete—potentially erase the complexities and contradictions of the lives of historical actors, are often informed by a desire to quarantine the past, and, just as often, fail to engage with its continuation in the present.
Keywords: Bint Said; Salama (1844-1924)

Djerbahood: le musée de street art à ciel ouvert = open-air museum of street art - Ben Cheikh, Mehdi (Albin Michel, 2022)
Keywords: Vie culturelle – Djerba

القنوت والتأمين بعد الفاتحة والرفع في الصلاة من أجوبة الشيخ إبراهيم بن أبي بكر حفار - حفار, إبراهيم بن أبو بكر (المركز العلمي للدين والشريعة الإسلامية, 2022)
Keywords: Fiqh; Fiqh – prières

المدينة الإسلامية في وادي مزاب - زعابة, عمر بن محمد; دودو, مصطفي (دراسات تراثية, 2022)
تتميّز المدن العتيقة في وادي مزاب بنمطها العمراني والمعماري الإسلامي المتميز من حيث وحدتها المتجانسة وتخطيطها المحكم، فكل مدينة قد بنيت على أعلى قمة الجبل لغرض دفاعي محض، يتوسطها المسجد الذي تعلوه مئذنة هرمية الشكل وتلتف حوله منازل تتخللها أزقة ضيقة وملتوية مشكلة بذلك حلقات دائرية حول المسجد، وفي سفح المدينة ساحة السوق للتعاملات التجارية، وكل مدينة محاطة بسور دفاعي تتخللها أبراج للمراقبة تمّ تصميمها وتخطيطها بهذا الوضع للحصانة الدفاعية وأن تكون في مأمن من سيلان الوادي وأن تحافظ على الأراضي الزراعية القليلة، وإنّ القيم الدّينية والفكرية، والطبيعة المناخية والجغرافية التي تتميّز بها منطقة سهل وادي مزاب لها تأثير كبير في تشكّل النسيج العمراني للمنطقة وفي التّصاميم المعماريّة المكوّنة له. العمارة بوادي مزاب تتميّز بعدة خصائص، المتانة والجمال والوظيفية والبساطة والاقتصاد في الوسائل، فليست هناك مدنا مشيّدة بل هناك نظم وأعراف تتّبع وتطبّق، قائمة على التّدرّج في تقسيم المجالات حسب أصنافها وعلى حسب الهيكلة الاجتماعية المتشبّعة بالفكر الإباضي الذي يعتمد أساسا على مبادئ وقيم الدين الإسلامي الحنيف. The ancient cities of valley M’zab are characterized by their distinctive Islamic urban and architectural style in terms of their homogeneous unity and tight planning., Every city has been built on top of the mountain for a purely defensive purpose, The mosque, which is surmounted by a pyramidal minaret, is surrounded by houses with narrow and twisted alleys, creating circular circles around the mosque, And at the foot of the city is the market square for business transactions, Each city is surrounded by a defensive fence interspersed with observation towers designed and planned in this situation for defensive immunity, safe from the flow of the valley and maintaining few agricultural land, Religious and intellectual values, The climatic and geographical nature of the valley M’zab plain area has a significant impact on the composition of the urban fabric of the area and in its architectural designs. Architecture in the M’zab Valley has several characteristics, Durability, beauty, functionality, simplicity and economy in means, There are no cities built, but there are systems and customs that follow and apply, Based on the gradual division of areas by their types and on the social structure saturated with ibadite thought, which is based mainly on the principles and values of the Islamic religion.
Keywords: Urbanisme – Mzab

Patrimoine culturel libyen de l’oralité. Quelques aspects des productions esthétiques aux XIXe et XXe siècles - Di Tolla, Anna Maria (Études et Documents Berbères, 2022)
Le but de cette contribution est de mettre ensemble et valoriser le patrimoine dispersé d’un aspect de la culture immatérielle qui concerne les textes oraux et les contes populaires recueillis sur le terrain et transcrits par les Italiens pendant la colonisation en Libye. Les textes collectés et transcrits concernent la vie quotidienne ou des contes qui représentent les parlers du Djebel Nefoussa. La mise en contact d’un pluralisme linguistique et culturel crée une diversité de processus d’appropriation et de reconfiguration. Le conte apparaît comme un lieu privilégié de dynamiques interculturelles, soulignant soit leur proximité à travers des motifs et des symboles, soit leur diversité patente. Cette étude tente d’analyser, à travers ces textes, comment interprètent les questions d’identité, de rencontre culturelle dans la Libye contemporaine, en situant cette production orale dans le contexte plus large dans laquelle s’enchevêtrent les dimensions locale, nationale et universelle.
Place: Paris
Keywords: Littérature – Djebel Nefousa

واو الاستئناف عند "قُطْب الأئمّة".. دراسة نحوية: واو الاستئناف عند "قُطْب الأئمّة".. دراسة نحوية - الرمحي, أحمد بن محمد (مجلة الآداب والعلوم الاجتماعية, 2022)
الملخص حرف الواو عند النُّحاة من حروف المعاني التي تتنوع دلالتها في السياق العربي، ومن معانيها "الاستئناف"، لكنَّ الشيخ محمد بن يوسف أَطْفَيْش الجزائريّ (1243-1332هـ) المعروف بــ "قُطْب الأئمة" يثير رأيًا في الاستئناف يُخالف ما استقرّ عليه النحو العربي في العصور المتأخرة، وكان لهذا الرأي أثرٌ بارزٌ في آثاره العلمية؛ فقد اعتنى في معالجاته اللغوية للنصوص بتوجيه الواو وغيرها من حروف الاستئناف إلى معنى نحويّ آخر يلائم دلالة سياقها، من هنا يسعى البحث بمنهج وصفي تحليلي إلى دراسة رأي "قُطْب الأئمة" في استئنافيّة الواو، وليستوفي الموضوع حقّه من الدراسة قام البحث على ثلاثة محاور: أولها: الوقوف على (الاستئناف) في علوم اللغة من حيث: مفهومه وأقسامه، وثانيها: تناول (الاستئناف) عند "قطب الأئمة" من حيث: مفهومه، وأنماط تشكُّله، وثالثها: الوقوف على استئنافيّة الواو في سياقات نَصِيَّة ورأي "قطب الأئمة" فيها، وتعود أهمية هذا البحث إلى كَوْنه يكشف عن مغايرةٍ نحويةٍ جديرة بالبحث والنظر، وتتأكَّد هذه الأهمية في الموضوع حين يَمْتَدُّ رأيُ "قُطْب الأئمة" من بُعْده النحوي إلى بُعْده الدلالي، حيث يقع توجيه النصَّ توجيهًا دلاليًّا ولا سيما في سياق النصّ القرآني الكريم. كلمات مفتاحيّة: الواو؛ الاستئناف؛ العطف؛ أطفيش؛ المعنى النَّحْوِي..

Le Palais Ben Ayed de Gammarth - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Le Palais Ben Ayed de Gammarth a été édifié vers 1831, par le Général Mohamed Ben Ayed, envoyé extraordinaire auprès du Roi Louis Philippe de France par le Bey de Tunis Hussein II
Section: Uncategorized
Keywords: Famille Bin Ayyad

Tchakchouka by Lesley Blanch - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Sur la petite île de Djerba, qui ressemble à un jouet, au large des côtes du sud de la Tunisie, se trouve une petite ville, Houmt-Souk,
Section: Uncategorized
Keywords: Alimentation – Djerba; Récits de voyage – Djerba

Carte des Edifices / Terrains Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Cette carte a pour objectif de lister les édifices (et terrains) appartenant ou ayant appartenus à la famille Ben Ayed d'un point de vue historique.
Section: Uncategorized
Keywords: Famille Bin Ayyad

Entretien à Londres avec la Princesse Kheyriye - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Il y a environ deux mois avant que je ne quitte Constantinople" dit-elle. "J'ai découvert que tout ce que je faisais était soigneusement espionné, ma maison
Section: Uncategorized
Keywords: Famille Bin Ayyad

La caserne husseinite ou Saussier - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
La caserne husseinite appelée aussi caserne d'El Gorjani est situé dans le quartier du même nom. Elle est occupée aujourd'hui par la brigade criminelle. Une
Section: Uncategorized
Keywords: Famille Bin Ayyad

La manufacture de draps d'El Battan à Tébourba - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Cette manufacture de draps et d'habillement des troupes a été construite par le Général Mohamed Ben Ayed en 1844 pour diminuer
Section: Uncategorized
Keywords: Famille Bin Ayyad

Six images inédites de Djerba en 1873 - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Découvrez six images inédites de Djerba et son histoire. Il s'agit des plus anciennes illustrations pour certains lieux qui date de 1873.
Section: Uncategorized
Keywords: Architecture – Djerba

Inauguration de la Rue Docteur Hassouna Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
En hommage au professeur Hassouna Ben Ayed, une rue de Tunis à Bab Saadoun, prêt de la faculté de médecine dont il fut le doyen portera désormais son nom.
Section: Uncategorized
Keywords: Famille Bin Ayyad

La branche princière de la famille Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Mohamed Taher, née à Tunis en 1853 de l'alliance du Général Mahmoud et de la dame Daddou Bent Hamda Djilani, épousera la Princesse Roukia Fazil, fille
Section: Uncategorized
Keywords: Famille Bin Ayyad

La fontaine Çengelköy à Istanbul - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Cette fontaine dans l’un des quartiers d’Istanbul a été construite par le Grand Vizir ottoman Youssef Ziyedudinn Pacha en hommage à sa femme décédée, mais quelques années après la mort du Vizir en 1819 l’eau s’arrêta de couler et ne parvenait plus à la fontaine à cause de changement de propriétaire, les habitants et passagers … Continuer la lecture de « La fontaine Çengelköy à Istanbul »
Section: Uncategorized
Keywords: Famille Bin Ayyad

Dans un jardin mauresque - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Cette illustration est une vue prise dans le magnifique jardin du Consul – Général britannique à La Marsa, près de Tunis. La maison de campagne, qui est la résidence principale du consul général britannique dans la régence de Tunis, était à l’origine un palais appartenant au Bey, qui l’a cependant offert en présent au gouvernement … Continuer la lecture de « Dans un jardin mauresque »
Section: Uncategorized
Keywords: Famille Bin Ayyad

Histoire d'un viking ottoman et d'une princesse révoltée - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Ali Nouri Bey, suédois converti, ancien Consul général de Turquie à Rotterdam, qui est actuellement à Londres avec sa femme, la Princesse Hairie Ben-Ayad, est l’un des dirigeants éminents du Parti légitimiste turc. Ce Parti revendique et œuvre pour la réinstallation sur le trône de Turquie le Sultan Murad V, qui serait devenu fou quelque … Continuer la lecture de « Histoire d’un viking ottoman et d’une princesse révoltée »
Section: Uncategorized
Keywords: Famille Bin Ayyad

L'épidémie de peste à Djerba en 1784 - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
La peste toucha en premier lieu Houmt-Souk, précisément Taourit, puis Ajim, ensuite elle se propagea dans toute l'ile en terminant par les villages de
Section: ben ayed
Keywords: Epidémies – Djerba – 1784

Modern Pollen Analysis in the Estuary Habitats along the Coast of Dhofar (Sultanate of Oman) - Bellini, Cristina; Ciani, Francesco; Pignotti, Lia; Baldini, Riccardo Maria; Gonnelli, Tiziana; Mariotti Lippi, Marta (Sustainability, 2022)
A lush vegetation develops around the numerous wadi estuaries interrupting the Dhofari coast in Southern Oman. Many estuaries still house mangroves of Avicennia marina (Forssk.) Vierh., a very fragile ecosystem that is currently under threat in this area. A rather rich flora, strongly affected by the influence of the monsoon, grows in other estuaries. This study concerns the flora and vegetation of these peculiar habitats with special focus on the plants growing on the different substrates. To gain insights into the pollen diffusion and representation of these plants in the current pollen rain, we analyzed surface soil samples. By evaluating their pollen amounts, we related the modern pollen rain to the abundance/coverage of the plant species typical of the different environments. Rather than a punctual indication of the plants growing at a short distance, our pollen records offer a general picture of the flora and vegetation of the area. This information is crucial for the correct interpretation of pollen records from ancient soils, and underlines the utility of pollen analysis for the reconstruction of the vegetation history.
Keywords: Botanique – Oman

New historiographical perspectives on the medieval Saharan space: human dynamics and intra-African and intra-Islamic religious and intellectual exchanges up to the 16th century - Novo, Marta G.; Gómez, María Crego; Patarnello, Claudia (2022)
Keywords: Commerce transsaharien

فقه الماء في المكتبة العُمانية - الأغبري, إسماعيل بن صالح بن إسماعيل (أعمال ندوة تطور العلوم الفقهية: فقه الماء في الشريعة الإسلامية : أحكامه الشرعية، وآفاقه الحضارية، وقضاياه المعاصرة : المنعقدة خلال عام، 1441 هـ-2019 م, 2022)

فقه الماء عند الإباضية - الخليلي, أفلح بن أحمد (أعمال ندوة تطور العلوم الفقهية: فقه الماء في الشريعة الإسلامية : أحكامه الشرعية، وآفاقه الحضارية، وقضاياه المعاصرة : المنعقدة خلال عام، 1441 هـ-2019 م, 2022)

نظام الأفلاج في الفقه الإباضي رؤية فقهية وحضارية - الغاربي, محمد بن راشد (أعمال ندوة تطور العلوم الفقهية: فقه الماء في الشريعة الإسلامية : أحكامه الشرعية، وآفاقه الحضارية، وقضاياه المعاصرة : المنعقدة خلال عام، 1441 هـ-2019 م, 2022)
Keywords: Droit – Oman

استثمار الوقف في عُمان النجاحات والمشكلات - القاسمي, صالح بن ناصر بن محمد (أعمال ندوة تطور العلوم الفقهية: فقه الماء في الشريعة الإسلامية : أحكامه الشرعية، وآفاقه الحضارية، وقضاياه المعاصرة : المنعقدة خلال عام، 1441 هـ-2019 م, 2022)
Keywords: Waqf (fondations) – Oman

نظام الري في فقه المغاربة - باجو, مصطفى بن صالح (أعمال ندوة تطور العلوم الفقهية: فقه الماء في الشريعة الإسلامية : أحكامه الشرعية، وآفاقه الحضارية، وقضاياه المعاصرة : المنعقدة خلال عام، 1441 هـ-2019 م, 2022)

البعد الاقتصادي لمشاكل الماء في ضوء المقاصد الشرعية - تفوشيت, خالد سعيد (أعمال ندوة تطور العلوم الفقهية: فقه الماء في الشريعة الإسلامية : أحكامه الشرعية، وآفاقه الحضارية، وقضاياه المعاصرة : المنعقدة خلال عام، 1441 هـ-2019 م, 2022)

التفسير الفقهي للنزاع حول الماء: دراسة فقهية مقارنة في المذاهب الخمسة - هرموش, محمود مصطفى عبود (أعمال ندوة تطور العلوم الفقهية: فقه الماء في الشريعة الإسلامية : أحكامه الشرعية، وآفاقه الحضارية، وقضاياه المعاصرة : المنعقدة خلال عام، 1441 هـ-2019 م, 2022)

Connectivités djerbiennes : globalisations méditerranéennes des Juifs de Djerba - Albera, Dionigi; Morvan, Yoann (Journal des anthropologues, 2022)
Le workshop international « Connectivités djerbiennes : Globalisations méditerranéennes des Juifs de Djerba » que nous avons co-organisé, initialement prévu en mars 2020 à l'IMéRA à Marseille, s'est finalement tenu en présentiel les 27 et 28 juin 2022. Son objectif était d'inaugurer une recherche collective et pluridisciplinaire menée dans le cadre d'un programme financé par l'A*Midex (Aix-Marseille univ.) en partenariat avec le Centre de recherche français à Jérusalem (CRFJ) et l'Institut de recherche sur le Maghreb contemporain (IRMC) à Tunis. Les difficultés d'organisation d'événements internationaux durant la pandémie COVID-19 ont conduit à reporter cet atelier au terme de ce programme, même si un certain nombre d'événements intermédiaires 3 ont permis de jalonner la mise en dialogue des différentes recherches effectuées par les membres du groupe. Celui-ci se compose d'universitaires français, israéliens et tunisiens, en mesure d'appréhender la diaspora des Juifs de Djerba dans ses points d'ancrages principaux, qui établissent entre eux diverses connectivités, et dessinent de façon originale une globalisation méditerranéenne nourrie d'échanges sud-sud.
Keywords: Judaïsme – Djerba

Each egg, a wish on the Jewish pilgrimage to the strange Tunisian synagogue - Israel, Noticias Aurora; Abel, Pablo (2022)
Each egg, a wish on the Jewish pilgrimage to the strange Tunisian synagogue
Keywords: Judaïsme – Djerba

Actes du colloque international : l'olivier dans la pensée et la culture. Première édition Djerba 30 novembre - 2 décembre 2018 - Ben Salah, Imed (Association Tazzamourt, 2022)
Keywords: A dépouiller

“Useful” Knowledge and Moral Education in Zanzibar Between Colonial and Islamic Reform, 1916–1945 - Bolton, Caitlyn (Islamic Africa, 2022)
The introduction of colonial schooling in Zanzibar was aimed at improving economic productivity, drawing on an exchange of educational theory with the American South to ensure a labor supply for the post-emancipation plantation economy. Yet colonial officials faced a key problem: students did not attend, preferring instead to continue studying in Qur’anic schools, institutions roundly derided by colonial officials. To secure attendance, colonial officials engaged local Muslim leaders to create an Islamic studies syllabus. While reflecting transnational Islamic reformist trends, this syllabus ultimately backfired as local parents protested its lack of moral content. Based on research in the Zanzibar National Archives, this article recounts the tensions and overlap between colonial officials, Islamic leaders connected to transnational discourses of reform, and local Muslim parents over what constitutes truly “useful” knowledge. It argues that colonial education was not particularly successful in forming students into the hard-working agricultural subjects it envisioned. It was successful, however, in orienting public institutions towards economic progress, and shifting public discourses on morality and religion to suit that goal.
Keywords: Vie politique – Zanzibar – 1911-1960

Escape from Zanzibar: Refugees, Documents, and the Indian Ocean Shipping Regime - Limbert, Mandana E. (International Journal of Middle East Studies, 2022)
In January 1964, on the heels of its formal independence from Britain, the East African island of Zanzibar exploded in a violent uprising ousting the Al-Bu Saidi sultan—an Omani by descent—and his primarily “Arab” government. Though early reports of the revolution did not indicate targeted attacks against Arabs, it soon became clear that thousands of Arab-identified residents—settlers—were killed, mostly in rural areas. 1 Others, including some families I came to know during my years in interior Oman, described being separated from their families or being captured and taken to detention camps, where they stayed a week or two before being reunited. Some found their way to these camps in search of relatives, shelter, and food. 2 Decades later, the chaos and violence of that time was recounted to me with unnerving directness. Eventually, thousands of Arabs were deported or fled—to Kenya, Dubai and Abu Dhabi, Egypt, Saudi Arabia, and Muscat and Oman. Muscat, on the coast of Oman, was the seat of the other Al-Bu Saidi sultan—a cousin of the Zanzibar sultan—who had only recently taken control of “Oman proper,” the territory of the Imamate whose ruler was now in exile in Saudi Arabia having been defeated in a war with the Sultan of Muscat. In the meantime, those leaving Zanzibar required ships and documents.

The Re-globalization Process in the Indian Ocean: the Ibadi Press in Zanzibar (al-Sultaniyya) - Nicolini, Beatrice (Chroniques yéménites, 2022)

القيم التنظيمية في المؤسسات الوقفية الإباضية دراسة وصفية لمؤسسة الإمام للبر والإحسان، القرارة، غرداية Organizational values in the Ibadi endowment foundation, Descriptive study of Imam for righteousness and charity – Gherrara, Ghardaia - إباض, بـهون علي; يمينة, مـختار (مجلة الموروث, 2022)
تشخّص هذه الدراسة الوصفية المفردية واقع المعاش للحقل الميداني محلّ دراستنا، حيث قام الباحثان بجـمع البيانات من خلال الأدوات البحثية المعتمدة، كجلسات المقابلة والملاحظة بالمشاركة، وتحليل المحتوى اللوائح والأنظمة الداخلية، وكانت إشكالية الدراسة كالأتي: ما هي القيم التنظيمية في المؤسسة الوقفية؟، وما مصدرها ؟ كيف تتجسّد عملياً في الواقع ؟ ولقد كشف التشخيص الميداني مدى تأثير العقيدة الإسلامية في أسس انطلاق المؤسسة، وقد كانت جلّية في الأنظمة ولوائح من أجل المحافظة والاستمرار على أدوارها التي انطلقت منها، وللكفاءات القائمة على إدارة المؤسسة التأثير البارز على فعالية القيم في أرض الواقع، من أجل سلامة ونجاعة قيمها التنظيمية، فهي متأثرة بطبيعة المؤسسة ونوعية نشاطها، وحجمها، ولخلفيتها ومنطلقاتها الأيديولوجية والثقافية والعلمية والمجتمعية والجغرافية. وقد صغنا الفرض الآتي: يمكن للمنظّمة الواعية بالشريعة ومقاصدها الكونية، أن تجسّد القواعد الفقهية في فلسفتها الإدارية وتصوغها قيم تنظيمية This descriptive study diagnoses the reality of the study, I collected the data through the approved research tools. The problem was: What is the organizational value in the endowment foundation? its source? How it is applied in reality? The real diagnosis reveals the extent of the influence of the Islamic faith on the basics of the foundation’s start, and it was evident in the regulations to preserve its starting roles. The skilled managers have a great impact on the efficacy of values in reality for its organizational safety; affected by the nature of the foundation, the quality of its activity, its size, its background and its ideological, cultural, scientific, societal and geographic backgrounds. We formulated this hypothesis: the aware organization of the faith and its cosmic purposes can apply the jurisprudential rules in its administrative philosophy and formulate organizational values.
Keywords: Waqf (fondations) – Mzab

The sixteenth-century Portuguese Suma Oriental and the Arab pilots: A comparative summa orientalis? - Acevedo, Juan (Proceedings of the Seminar for Arabian Studies, 2022)
Starting from a consideration of Tomé Pires’ 1515 Suma Oriental, this article considers the feasibility, nature, and relevance of a summa orientalis in the form of a Portuguese Early Maritime Corpus. When this corpus is compared with Arabic nautical literature, primarily Ibn Mājid and Sulaymān al-Mahrī, and especially with attention to the technical aspects of their writings, then the desirability of an Indian Ocean Maritime Corpus is envisaged. The centrality and the mediating role of Arab pilots and Arabic nautical literature indicate that the first step is the delimitation of an Arabic Early Maritime Corpus.
Keywords: Navigation – Oman

Quadriliterals and “quinqueliterals” in Omani Mehri - Bendjaballah, Sabrina; Ségéral, Philippe (South Arabia: Old Issues, New Perspectives: Proceedings of the Workshop at the University of Erlangen-Nürnberg on December 19, 2019, 2022)
Keywords: Linguistique – Oman

Black magic and djinn in Omani literature: examining the myths and reality - Hosni, Manar al- (Arab and Muslim Science Fiction: Critical Essays, 2022)
Keywords: Littérature – Oman

From raw materials to finished products: pottery production at Sumhuram (Khor Rori, Sultanate of Oman) - Rizzo, Carlotta; Pagnotta, Stefano; Lezzerini, Marco; Pavan, Alexia; Buono, Giulia (Proceedings of the Seminar for Arabian Studies, 2022)
The aim of this paper is to analyse the dynamics related to the pottery production in Sumhuram, the easternmost port of call between the Red Sea and the Indian continent along the southern coast of Arabia (second century BC–fifth century AD). Being a rich hub of international trade, receiving and redistributing local products and goods from many different areas, Sumhuram was able to provide for its needs through its own agriculture and a number of local activities, as attested by the presence of kilns and furnaces. Previous studies on the topic have suggested a possible connection between local pottery manufacturing in Sumhuram, and the Hadrami tradition, although kilns have not been found until recently. In 2015 archaeological investigations unveiled the first evidence of such a connection with the discovery of a pottery kiln and some production waste inside the city wall, along with the identification of pottery sherds in the area of the kiln. In order to identify their mineralogical and petrographic composition, thin-section analyses were made on a number of selected sherds. The preliminary results demonstrate that the raw materials used are compatible with a local production. This allows us to describe the different phases of the pottery cycle in Sumhuram as well as the structure of the pottery kiln, which represents an uncommon find in the pre-Islamic archaeology of southern Arabia.
Keywords: Archéologie – Oman

Navigating the Gulf: Aḥmad b. Mājid’s poem on Gulf navigation - Staples, Eric (Proceedings of the Seminar for Arabian Studies, 2022)
Aḥmad b. Mājid is the most renowned author of Arabic navigational literature. Although he is reported to have come from the southern Gulf port of Julfar, the vast majority of his work focuses on navigating the Indian Ocean and the Red Sea, and his compositions contain few details relating to Gulf navigation. The one exception is a short, undated poem describing sailing routes in the Gulf. This paper analyses this unique poem and compares the navigational practices it describes with those in his other navigational works in order better to understand the specific characteristics of Gulf and Indian Ocean navigation in the fifteenth century.
Keywords: Navigation – Oman

Cross-cultural maritime technological exchange in the first-millennium Indian Ocean - Vosmer, Tom (Proceedings of the Seminar for Arabian Studies, 2022)
Extensive trade networks in the Indian Ocean generated contact among cultures and spheres of maritime technology across a huge geographical area. Inevitably, these networks resulted not only in exchange of foodstuffs, raw materials, luxury goods, spices, and manufactured goods, but also in cultural and religious concepts and technological knowledge and practices. With the intensity of maritime trade these exchanges engendered the borrowing of shipbuilding designs, materials, and methodologies and generated a certain hybridization of technology, design, and the ways in which ships were conceived. This hybridization is particularly evident in the Belitung and Phanom-Surin ships discovered in Indonesia and Thailand respectively (Flecker 2001; 2008; Jumpron 2019; Wongnai, Jumpron & Premjai 2016). While echoing shipbuilding practices from outside South-East Asia, they also incorporated materials and concepts from South-East Asia, and yet remain distinct from the dominant lashed-lug construction of the region. Using archaeological material from Oman and South-East Asia as well as ethnographic data from the western Indian Ocean, East Africa, India, Oman, Iran, and South-East Asia, this paper explores current archaeological and ethnographic shipbuilding information and raises some questions about the place of Belitung and Phanom-Surin in first-millennium shipbuilding practice.
Keywords: Archéologie – Oman

Revisiting Omani Legacy in Malaya through the Royal Kedah Dress: Reassessment - Mansor Majdin, Mohamad Firdaus; Osman, Rahmah Ahmed H.; Fathil, Fauziah; Yaapar, Md. Salleh; Zuheimi, Saleh al- (Journal of Islamic Thought and Civilization, 2022)
This paper seeks to examine the legacy of the Omani presence in the states of Malaysia, which arguably has made itself apparent in the royal dress of the Kedah Sultanate. This discovery indeed calls for further investigation, especially on how the Omani dress later became a model for Kedah royal dress which is famously known as Baju Muskat. Further analysis is essential to determine to what extent did the Kedah Sultanate adopted the Omani dress of the Muscati style and what aspects of the Kedah royal dress resemble the Omani dress substantially. Preliminary research indicates that there are few similarities that one can find between the Omani dress with that of the Kedah royal dress, which is said to be worn by the latter since the 17th century. Reading through the existing literature in the field also reveals one interesting picture that points to the underrepresentation of Omani individuals, merchants, and scholars in the Malay texts as the former tends to describe them, often as Arab traders, or Persian traders. In short, this paper has attempted to explore and examine the above-mentioned circumstances for a better understanding of the subject matter under study through a method of content analysis. Keywords: Well-being, Happiness, Subsistence, Ethical Principles, Arab-Muslim Thought
Keywords: Relations – Oman – Malaisie

Pronominalization and clitic doubling in Syrian and Omani Arabic - Hallman, Peter; Balushi, Rashid al- (Linguistics, 2022)
Abstract This article treats cliticization of a pronoun to a syntactic host and doubling of the clitic pronoun with a non-pronominal counterpart in Syrian and Omani Arabic. Although the two varieties are closely related and the morphological paradigms they display are very similar, the pronominalization and clitic pronoun doubling patterns they display are quite different. We trace this difference to a basic difference in whether the relevant syntactic processes are sensitive to intervention effects in the two dialects, with the result being that the restrictiveness of pronominalization and clitic pronoun doubling patterns parallel the restrictiveness of basic word order patterns – whether double-object constructions are ‘symmetric’ or ‘asymmetric’ – with Syrian being the more restrictive of the two varieties.
Keywords: Linguistique

The Foundation, Development and Future of the Omani Rentier State: From the Dhofar War to Vision 2040 - Due-Gundersen, Nicolai; Owtram, Francis (Chroniques yéménites, 2022)

Demonstratives in Musandam Arabic: Distinctive Archaisms and Innovations - Anonby, Erik; Bettega, Simone; Procházka, Stephan (Arabica, 2022)
Abstract This study introduces and analyzes proximal and distal singular demonstratives in fourteen varieties of Musandam Arabic, a little-documented dialect group located on Musandam Peninsula in northern Oman and neighbouring areas of the United Arab Emirates. Following an overview of the dialect group in its regional context, the study provides a description of singular demonstratives from the point of view of phono-logy, morphology, and geographical distribution. The study then focuses on two salient features found in several of the varieties under investigation: gender distinction based on consonantal alternation ( d -based masculine forms vs t -based feminine forms); and gemination of the feminine t -element. While the former is attested, albeit rarely, in other Arabic dialects, the latter is unheard of. In the last section of the article, some hypotheses are put forward as to how these forms could have developed from a historical point of view, in light of data from different Arabic and Semitic varieties. While the gemination of the t -element is best regarded as a Musandam-internal innovation, the d : t consonantal alternation reinforces the putative historical link between south-western Arabia and Oman.
Keywords: Linguistique – Oman

Ship graffiti at the Zanzibar Gereza (Old Fort), Stone Town, Unguja, Tanzania - Cooper, John P.; Ghidoni, Alessandro (Azania: Archaeological Research in Africa, 2022)
Keywords: Archéologie – Zanzibar

Dialect Variation among Omani Migrants in Muscat: The Construction of Social Identity through Style Shifting - Ambu-Saidi, Suaad (Language and Identity in the Arab World, 2022)
Keywords: Linguistique – Oman

Science Education in Oman: Taking Oman to Better Future - Ambusaidi, Abdullah K.; Shahat, Mohamed A.; Al Musawi, Ali S. (Science Education in Countries Along the Belt & Road: Future Insights and New Requirements, 2022)
The purpose of the present chapter is to give the reader an overview of the current science education research in Oman. The chapter focuses on three main sections as an overview of the country, an overview of the education development, and the current situation of science education. It addresses the emerging technologies in relation to science education including blended education and e-learning developments. The chapter then discusses the requirements for better implementation of science education along with the future strategies to overcome the challenges and issues that facing science teachers in Oman. It concludes by recommending the importance of making greater efforts to instill the twenty-first-century skills in the future graduates of science to enable them to respond to the requirements of the global economic market.
Keywords: Enseignement – Oman

Ancient Weapons of Oman: Edged Weapons - Clarizia, Vincenzo (Archaeopress, 2022)
Keywords: Archéologie – Oman

Ancient Weapons of Oman : Firearms - Clarizia, Vincenzo (Archaeopress, 2022)
Keywords: Archéologie – Oman

Negotiating placemaking: Public-private spaces and Hinduism in Oman - Mehta, Sandhya Rao (Routledge Handbook on Middle Eastern Diasporas, 2022)
The Gulf Cooperation Council (GCC) countries are all Islamic countries with different public policies and attitudes to the presence of other religions. This has major implications for the Hindu community, often seen as consisting of migrant workers, which normally bases its religiosity on highly public, participatory and performative rituals. This chapter focuses on how the diverse Hindu community in Oman negotiates its religious identity in an Islamic country by strategically using its past mercantile relations with the ruling families, creating and participating in transnational networks, as well as imaginatively using public-private spaces to engage in rituals and festivities and overcome state restrictions. It suggests that the Hindu diaspora in Oman can be problematised as being more than just a minority community with few religious freedoms in a conservatively Muslim nation. Focusing on the Hindu community in Oman adds to emerging studies on diaspora and transnational mobilities, de-essentialising the binary relations of the state with its religious minorities in this part of the world.

Strategic Belonging: Hindu Identity and Performance in Oman - Mehta, Sandhya Rao (Asian Journal of Middle Eastern and Islamic Studies, 2022)
This study focuses on the multiple ways in which the Hindu community in Oman negotiates its religious identity in an Islamic country by strategically using its historic mercantile relations with the ruling families, maximising the use of public-private spaces, and creating and participating in transnational networks as ways to cope with state restrictions. Using Vertovec’s notion of ‘complexifying complex diasporas,’ this study examines how Hindus, while being publicly ‘invisible,’ have been able to possess a continuing cultural platform which is leveraged to acquire opportunities for religious performance. However, challenges to such strategic belonging have been rising rapidly with the rise of right wing Hindu ideology within and outside India. The repercussions of the establishment of a Hindu state in India on its diaspora, particularly in an officially Muslim country, are rife with challenges. Alternative strategies may have to be explored by the community to assert its identity and religious practices, as well as secure its future in Oman.

Persia and Oman: A Historical and Linguistic Intersection - Morano, Roberta (Language and Identity in the Arab World, 2022)

“We Sent Our Sons across the Seven Rivers”: Tracing the Migratory Network and the Risky Migration of Bangladeshi Fishermen to Oman - Percot, Marie (The South Asia to Gulf Migration Governance Complex, 2022)
‘We sent our sons across the seven rivers and we let them go because we need food, because we don’t have enough. Here, they have no work and we have no land. […] If they were getting their fair share, it would be enough for us. If those [Omani] people were thinking that they have crossed so many rivers out of need, they would help them, but they just don’t think about it.’¹ Except for the extensive work by M.M. Rahman, little research until now has been done, especially of a qualitative nature, on the situation of Bangladeshi migrants in
Keywords: Emigration – Bangladesh – Oman

Houseways in Southern Oman - Risse, Marielle (Routledge, 2022)
This book explores how houses are created, maintained and conceptualized in southern Oman. Based on long-term research in the Dhofar region, it draws on anthropology, sociology, urban studies and architectural history. The chapters consider physical and functional aspects, including regulations governing land use, factors in siting houses, architectural styles and norms for interior and exterior decorating. The volume also reflects on cultural expectations regarding how and when rooms are used and issues such as safety, privacy, social connectedness and ease of movement. Houses and residential areas are situated within the fabric of towns, comparison is made with housing in other countries in the Arabian peninsula, and consideration is given to notions of the 'Islamic city' and the 'Islamic house'. The book is valuable reading for scholars interested in the Middle East and the built environment.
Keywords: Développement local – Oman

Assimilating the Heterogeneity of Migrant Populations through a National Past: Transforming a Shiʿa Minority Community in Post-Nationalist Oman - Sachedina, Amal (Anthropological Quarterly, 2022)
Scholarship on the Arab Gulf region often links heritage production with technologies of state pedagogy in its efforts to fix the spatial boundaries of a nation and entrench authoritarian rule. Yet, such a modular explanation ignores pressing questions regarding how statist narratives domesticate heterogeneous populations and regulate social difference. This paper explores the ways in which official accounts of the historical past have interpellated the material traces of diasporic communities, specifically the enclave of a minority community in Oman, the al-Lawati with links to the Sind region of the Indian sub-continent. The Sur al Lawati, a fortified residential enclosure of the Al Lawati community, draws from Gujarati traditional architecture rather than the surrounding Muscat cityscape. The sur (enclosure) has been mobilized as a token of the nation's pluralist history as an Indian Ocean trading power. This is consistent with Oman's expanding culture industry, which since the 1970s has generated history-making practices to sediment a homogenous Arab and general Islamic identity. However, using archival and ethnographic research, I argue that the enclave's material presence has presided over the complexities of a more entangled history in which the boundaries of this community of merchants and retailers have been reconfigured over the course of the 20th century. The very act of incorporating the sur and its residents into the history of a national people is grounded on the one hand in celebrating a cosmopolitan past as a sea-faring nation that traversed the Indian Ocean waters. On the other hand, it is also tethered to a sense of the past shaped by such categories as the "Arab tribe" and a "generic Islam" Both histories become an exercise of selectivity. They involve gaps, disjunctures, and diversity at the core of what passes as a unifying history of a sovereign nation.

The Maritime Silk Road: Implications for Oman’s Foreign Policy - Tekir, Gökhan (Ortadoğu Etütleri, 2022)
This study seeks to analyze the implications of Oman’s participation in the Maritime Silk Road, which is the maritime component of the Belt and Road Initiative, announced in 2013 by the President of the People’s Republic of China, Xi Jinping. Sultan Qaboos has transformed Oman from an isolated and backward country to an active political mediator in the region. Oman’s neutral stance and diplomatic connections with every political actor in the region differentiate Oman from the rest of the Gulf countries. Geographically, Oman is situated in the intersection of the Persian Gulf, the Arabian Sea and the Indian Ocean. Historically, Oman ruled South Asian and East African coasts, extending its influence. The geographical position and historical legacy make Oman as a key country for the Maritime Silk Road. Thus, participation of Oman in the Belt and Road Initiative is invaluable in the eyes of the Chinese policymakers. Omani policymakers, who want to diversify Oman’s economy, welcome Chinese investments. However, increasing Chinese involvement in Oman’s economy might harm Oman’s sovereignty because of Chinese practice of using debts as exerting pressure on the lending states’ sovereignty. Moreover, the intensified competition between the USA and China in the Indian Ocean could compromise Oman’s neutral stance. Yet, Sultan Qaboos’ legacy is followed by Omani policymakers. While benefiting Chinese economic investments, Oman performs balancing acts against China.
Keywords: Vie politique – Oman – 1970-2020

Oman - Wigley, Thomas (Yearbook of Islamic and Middle Eastern Law Online, 2022)
Keywords: Droit – Oman

British Diplomacy in Oman and Bahrain: 50 Years of Change - Worthington, Joe (Routledge, 2022)
This book marks the first comprehensive examination of contemporary British influence in Oman and Bahrain, analysing Britain's legacy since the official withdrawal from the Gulf in 1971.
Keywords: Relations – Oman – Royaume-Uni

Boats, horses, and moorings: maritime activities at al-Balīd in the medieval period - Ghidoni, Alessandro; Pavan, Alexia (Proceedings of the Seminar for Arabian Studies, 2022)
The importance of the medieval city of al-Balīd and its harbour was mentioned in many different sources, and mirrored by a large number of finds and pottery that confirm a primary role of the port as a pivotal hub in Indian Ocean trade during the pre-modern Islamic period (tenth–fifteenth century AD). This paper will examine maritime activities at al-Balīd from a different perspective, combining recent data from the study of ship timbers discovered at the site with the archaeological record, along with evidence of possible harbour facilities. The study of the ship timbers has provided invaluable information about the technology, size, material, type, and function of the watercraft involved in the trade at al-Balīd. The reuse of these timbers in a terrestrial context also alludes to a variety of activities carried out at the site, such as boatbuilding, maintenance, repair, and salvaging. Collectively, this data yields useful insights into the relationship between the different vessels operating at al-Balīd and the structure of the site itself, mainly in connection with one of the most lucrative commercial activities at the port city — the trade of Arabian horses.
Keywords: Navigation – Oman

Storytelling an eco-Islamic future/past: Oral tradition(s), environmentalism and personal responsibility in the Omani public sphere - Curtis, Maria F. (Performing Islam, 2022)
During the global COVID-19 pandemic, the Omani government relied heavily on circulating information and entertainment through multiple forms of social media to keep citizens informed and to promote social distancing. This study explores the 2021 Ramadan Instagram campaign created by Be’ah, the Oman Environmental Services Holding Company, which blended performance genres and Omani traditional storytelling. This case study examines ‘multiplex’ hybrid styles of verbal art that mirrored governmental policy and practice across social media and created a forum where citizens discussed identity, national heritage and what it means to be eco-conscious. A central question in this research concerns the possibilities for social media as a space to communicate, preserve and archive local linguistic diversity and vernacular performative genres.

A Text in the Jibbali/Shehret Dialect of al-Ḥallānīya (Kuria Muria) with a Grammatical Commentary - Castagna, Giuliano (Semitic Dialects and Dialectology Fieldwork—Community—Change, 2022)
Publisher: [object Object]
Keywords: Linguistique – Oman

Operation Intradon in the Musandam,1970-1971: what this counterinsurgency operation says about British military operations in the Arabian Gulf - Yates, Athol; Hughes, Geraint (Small Wars & Insurgencies, 2022)
Keywords: Dhofar

The Omani Prince in the Search for Protectors. Abdulaziz bin Said’s Struggle for Power and Money in the Time of Growing British Dominance in the Indian Ocean Region - Żbik, Sebastian (Journal of Colonialism and Colonial History, 2022)
Abdulaziz Al-Busaidi was the younger son of the Omani ruler Said bin Sultan. He devoted all his life to gain power and secure a source of income for himself. To achieve this, he formed alliances and sought powerful protectors. Among them were the British who supported him for almost fifty years, both as a potential heir to the thrones of Oman and Zanzibar and as a tool in their imperial policy. Although Abdulaziz’ political projects failed because of the British and his inability to cooperate with prospective allies, his actions greatly affected the history of Oman and Zanzibar in the second half of the nineteenth century.
Keywords: Relations – Oman – Royaume-Uni

The Dower (Mahr) and Wedding Ceremony among the Shi‘a of Oman: Religion, Class, and Ethnicity - Shanneik, Yafa; Moors, Annelies; Safar, Jihan (Global dynamics of Shi'a marriages: religion, gender, and belonging, 2022)
"Muslim marriages have been the focus of considerable public debate in Europe and beyond, in Muslim-majority countries as well as in settings where Muslims are a minority. Most academic work has focused on how the majority Sunni Muslims conclude marriages. This volume, in contrast, focuses on Twelver Shi'a Muslims in Iran, Pakistan, Oman, Indonesia, Norway, and the Netherlands. The volume makes an original contribution to understanding the global dynamics of Shi'a marriage practices in a wide range of contexts–not only its geographical spread but also by providing a critical analysis of the socio-economic, religious, ethnic, and political discourses of each context. The book sheds light on new marriage forms presented through a bottom up approach focusing on the lived experiences of Shi'a Muslims negotiating a diverse range of relationships and forms of belonging"–

The Wolf: The Last Remnants of the age of Sail in Southern Oman - Staples, Eric; Weismann, Norbert; Dziamski, Piotr; Ghidoni, Alessandro; Haar, Lilli; Vosmer, Tom (International Journal of Nautical Archaeology, 2022)
This article looks at a specific southern Arabian sailing vessel named the Wolf (al-Dhi’b), in order to better understand the life of a coastal trader on the southern Arabian coast that lived in the last days of commercial sail. Vessels such as the Wolf carried local products such as sardines, abalone and frankincense to northern Oman and Yemen, returning with dates and necessary foodstuffs shipped to Aden from India and East Africa. The article examines the remains of the Wolf, based on data from multiple documentation surveys, in conjunction with information gained from oral history interviews in order to highlight the central role that vessels such as the Wolf played in the maritime economic and social networks of the region.
Keywords: Navigation – Oman

Deconstructing ‘Energy Security’ in Oman: A Journey of Securitisation from 1920 to 2020 - Harub, Lamya (Springer, 2022)
This book makes a substantial and extremely timely, relevant contribution to discussions on energy security in Oman
Keywords: Pétrole – Oman

ترجمة التراث العماني الرؤى والآفاق - فارس, وليد فكري; الزهيمي, صالح بن سليمان; الشيباني, سلطان بن مبارك (ذاكرة عمان, 2022)
Keywords: Sources – Oman

رسالة في علم الرسم - الرقيشي, حمد بن سالم (ذاكرة عمان, 2022)

نشر الورى في خبر إبرا - المسكري, علي بن سالم (ذاكرة عمان, 2022)

النور - الأصم, عثمان بن أبي عبد الله (ذاكرة عمان, 2022)

“Friend to All, Enemy to None”: Oman’s Quiet Diplomacy Since 1970 - Owtram, Francis (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Politique étrangère – Oman – 1970-2020

Omani Peacemaking and Middle East Crises in the 2010s: Sultan Qaboos’ Last Decade - Cole, Juan (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Politique étrangère – Oman – 1970-2020

Greening Oman: Islamic Environmentalism, Sustainable Development, and Post-Oil Futures - Curtis, Maria F. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Développement durable – Oman

Duqm and Salalah: Oman’s Ports and Special Economic Zones - Kinnier, Jeffrey (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Ports – Oman

Muscat and Sultan Qaboos: The Omanization of Muscat and the Muscatization of Oman - Guirado Alonso, Javier (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Beyond the Horizon and Back: The Sultan Qaboos Scholarship - Pritt, Jody (Sultan Qaboos and modern Oman, 1970-2020, 2022)

Public Health and the Omani Renaissance - Foley, Sean (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Literature in Oman During the Reign of Sultan Qaboos - Michalak-Pikulska, Barbara (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Littérature – Oman

Nation and State in Oman: The Initial Impact of 1970 - Peterson, John E. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Constitutional Reforms During the Reign of Sultan Qaboos - Kharusi, Salim al- (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

In the Middle of a Reign - Hoffman, Valerie J. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

The Interpretation of Islam under Sultan Qaboos - Hoffman, Valerie J. (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Ibadisme – Oman

From the First Renaissance to the Second: The Historical and Legal Basis for the Sultanate - Salimi, Abdulrahman al- (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Stamps as Messengers of the Renaissance: The Postal Issues of Oman During the Reign of Sultan Qaboos - Allen, Jr, Calvin H. (Sultan Qaboos and modern Oman, 1970-2020, 2022)

The Multiple Legacies of Sultan Qaboos: Heritage and Omani Nation Building - Penzier-Hightower, Victoria; Worrall, James (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

The Land of Frankincense: Dhofari Sites as National and World Heritage - Lewis, Krista (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Monuments – conservation – Oman

Prehistoric Interactions between Oman and the Indus Civilization: Projecting the Past in the Present - Kenoyer, Jonathan Mark (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Relations – Oman – Inde

The Legacy of Sultan Qaboos: A Historiographical Note - Rabi, Uzi (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Introduction: Sultan Qaboos, Omani Society, and the “Blessed Renaissance”, 1970–2020 - Fromherz, Allen (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Vie politique – Oman – 1970-2020

Flogging, Banning, Lapidation: What Was the Punishment for Fornication and Adultery in Early Islam - Francesca, Ersilia (Jerusalem Studies in Arabic and Islam, 2022)
In the Qurʾān, there are several references to zinā (meaning both fornication and adultery), which stress the social ills that follow from committing such a sin. The Qurʾān makes it clear that those found guilty of zinā, regardless of their marital status, will be liable to receive a punishment of one hundred lashes, whilst slaves, married or unmarried, should receive fifty lashes (Q. 24:2). Nonetheless, the complexities surrounding the issue of adultery, and in particular the issue of its punishment, gave rise to a heated debate in the early Islamic juristic circles, which coalesced into a number of traditions conveying a growing strictness with regard to the punishment for adultery, especially towards married adulterers. In this paper I offer an interpretation of the most significant among these narrations in the early sources. In particular, I provide an account of the issue from the perspective of the early Ibāḍī sources, which are often neglected in mainstream Islamic studies, in order to trace the Ibāḍī contribution to the early juristic debate on fornication and adultery. My hypothesis is that a focus on Ibāḍī sources, which have been proven to preserve some very ancient material, provides a stronger basis for the study of the early centuries of Islam.

Leben mit verlassenen Lehmziegelsiedlungen in Zentraloman – eine archäologische Betrachtung - Döpper, Stephanie; Biezeveld, Irini (2022)

Die Stadtmauer von Bahla: Kommunale Selbstverwaltung in einer Oasensiedlung am Ende des omanischen ancien régime - Hoffmann-Ruf, Michaela; Büssow, Johann (2022)

Häuser bewohnen, mit Häusern leben. Praxistheoretische Überlegungen zu Transformationsprozessen der omanischen Lehmziegelarchitektur (anhand von Fallbeispielen) - Kanditt, Josephine; Schmidt-Lux, Thomas (2022)
Keywords: Architecture – Oman

Al-bilād und al-ḥāra, Heimatort und - Wohnquartier, in zeitgenössischer Wahrnehmung von in Maskat beschäftigten Arbeitnehmern aus Zentraloman - Mershen, Birgit (2022)

Branding and Spatial planning in Oman: a neoliberal turning point in politics? - Klinger, Thibaut (2022)
Keywords: Urbanisme – Oman

The music of the damâl ritual of the Omani Baloch: ritual practice outside of its territory of origin - Mascagni, Romain (2022)
Keywords: Musique – Oman

أعمال ندوة تطور العلوم الفقهية: فقه الماء في الشريعة الإسلامية : أحكامه الشرعية، وآفاقه الحضارية، وقضاياه المعاصرة : المنعقدة خلال عام، 1441 هـ-2019 م - ندوة تطور العلوم الفقهية (وزارة الأوقاف والشؤون الدينية, 2022)

تجديد الفكر الاسلامي : مقاربات السنة و الشيعة و الاباضية و العلمانيين - جدي, وديع (كلية الآداب والعلوم الإنسانية, 2022)

اشكال التدين في نماذج السير الاباضية ببلاد المغرب حتى القرن العاشر الهجري / 16 ميلادي - فارس, محمد (كلية العلوم الانسانية والاجتماعية, 2022)

Le tourisme tunisien face aux défis des crises multisectorielles actuelles : le cas de l'île de Djerba - Miadi-Aloui, Fadhila (Revue tunisienne de géographie, 2022)
Keywords: Tourisme – Djerba

Djerba aux portes du patrimoine mondial - Bourgou, Malek (Revue tunisienne de géographie, 2022)
La Tunisie, représentée par le Ministère des Affaires culturelles, se prépare pour déposer une proposition d'inscription de Djerba sur la liste du patrimoine mondial culturel relevant de l'UNESCO. Le choix des zones (au nombre de sept) et des monuments (au nombre de 23) à insérer a été fait et le dossier avec ses différents composantes est quasi-près. Il s'agit ici de le passer en revue, d'exposer les atouts et les limites de l'acceptation de ce dossier et de voir dans quelle mesure un tel acte pourrait protéger et mettre en valeur le patrimoine culturel et naturel de Djerba Bourgou, Malek
Keywords: Monuments – conservation – Djerba

دراسة انثروبولوجية للتراث الغذائي ليهود جربة - عبد العزيز, امنة (كلية العلوم الأنسانية والإجتماعية, 2022)
Keywords: Judaïsme – Djerba

بناء الهويات في سياقات انتقالية دراسة حالة هوية اصحاب البشرة السوداء بجزيرة جربة - المحمدي, رانيا (كلية العلوم الأنسانية والإجتماعية, 2022)

موسوعة الفقه الإباضي: الفهارس العامة - أبو زيد, منى أحمد (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Fiqh; Fiqh – Ibadisme

موسوعة الفقه الإباضي: الأفعال المنجية من المهلكة - أبو مليح, رجب (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Fiqh; Fiqh – Ibadisme

موسوعة الفقه الإباضي: البيوع - أبو مليح, رجب (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Fiqh; Fiqh – Ibadisme

موسوعة الفقه الإباضي: الرضاع – الفقد – الظهار – الإيلاء – الفداء - الطلاق - أبو مليح, رجب (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Fiqh; Fiqh – Ibadisme

موسوعة الفقه الإباضي: النفقات – الدماء – الديات - الفرائض - أبو مليح, رجب (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Fiqh; Fiqh – Ibadisme

موسوعة الفقه الإباضي: الوصايا والأحكام - أبو مليح, رجب (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Fiqh; Fiqh – Ibadisme

موسوعة الفقه الإباضي: القسمة والرهن والشفاعة والهبة - المنسي, محمد قاسم (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Fiqh; Fiqh – Ibadisme

موسوعة الفقه الإباضي: تتمة البيوع والإيجارات والشراكات - المنسي, محمد قاسم (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Fiqh; Fiqh – Ibadisme

الضوابط الفقهية الإباضية: دراسة مقارنة يالمذاهب الإسلامية - آل هرموش, محمود مصطفى عبود (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Religions comparées

الضوابط الفقهية الإباضية: دراسة مقارنة يالمذاهب الإسلامية - آل هرموش, محمود مصطفى عبود (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Religions comparées

الضوابط الفقهية الإباضية: دراسة مقارنة يالمذاهب الإسلامية - آل هرموش, محمود مصطفى عبود (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Religions comparées

محافل النظر في منطق الحجاج والجدل - الشيخ, محمد (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Philosophie islamique

المبهج في فلسفة الجمال والفن - الشيخ, محمد (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Philosophie islamique

أحكام قانون الإجراءات الجنائية في الفقه الإباضي - أبو الوفا, أحمد (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Droit – Oman

أحكام قانون الإجراءات الجنائية في الفقه الإباضي - أبو الوفا, أحمد (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Droit – Oman

أحكام قانون الإجراءات الجنائية في الفقه الإباضي - أبو الوفا, أحمد (وزارة الأوقاف والشؤون الدينية, 2022)
Keywords: Droit – Oman

موسوعة الآثار الفقهية للإمام أبي سعيد عبدالله بن عبد العزيز - ابن عبد العزيز, عبدالله (وزارة الأوقاف والشؤون الدينية, 2022)

موسوعة الآثار الفقهية للإمام أبي سعيد عبدالله بن عبد العزيز - ابن عبد العزيز, عبدالله (وزارة الأوقاف والشؤون الدينية, 2022)

مفهوم اللقب وتطبيقاته في الفروع الفقهية في المذهب الإباضي: دراسة تأصيلية تطبيقية - الجهضمية, أنوار بنت زايد بن سليمان بن عبدالله (جامعة السلطان قابوس, 2022)
University: كلية التربية

الأصول التاريخية والعقدية للفرقة الإباضية: دراسة تاريخية تحليلية - الحسنوني, عادل عبدالعزيز غيث عبدالخالق (مجلة العلوم والدراسات الإنسانية, 2022)
Number: 072

قياس الشبه عند الإباضية وتطبيقاته الفقهية: دراسة أصولية فقهية - الحضرمي, حمود بن عبدالله بن علي (جامعة السلطان قابوس, 2022)
University: كلية التربية

القاضي موسى بن علي الإزكوي "ت. 231 هـ. / 845 م." وإسهاماته في الحياة السياسية والثقافية في عمان - الخاطرية, خلود بنت حمدان (مجلة كلية الآداب, 2022)
Number: 007

الاجتهاد الأصولي: روحه ومظاهره في فكر الإمام محمد بن عبدالله الخليلي - الخروصي, أحمد بن سالم (مجلة البحوث الإسلامية, 2022)
Number: 081
Keywords: Ijtihad – Oman – 19e siècle

البيان الوافي في الرد على من قال بأن جابر بن زيد إباضي - الشريف, أحمد محمد علي خليل (مجلة كلية أصول الدين والدعوة بأسيوط, 2022)

عقيدة الإباضية في مرتكب الكبيرة: دراسة نقدية - القشيري, ندى بنت فايز بن عوظه (مجلة الدراسات العقدية, 2022)
Number: 030

العلاقة العمانية اليمنية الدينية والسياسية ما بين القرنين "1 - 3 هـ. / 7 - 9 م." - الندابى, ناصر بن على بن سالم (مجلة الأندلس للعلوم الإنسانية والاجتماعية, 2022)
Number: 054

عموم البلوى عند الإباضية: دراسة تأصيلية تطبيقية - النظيري, راشد بن حمود بن أحمد (مجلة الآداب والعلوم الاجتماعية, 2022)
Number: 002

قاعدة "من استعجل الشئ قبل أوانه عوقب بحرمانه" وتطبيقاته في فقه الأسرة عند الإباضية: دراسة مقارنة بقانون الأحوال الشخصية العماني - النظيري, راشد بن حمود بن أحمد (مجلة بحوث الشريعة, 2022)
Number: 002

نصوص إباضية مخطوطة في فلسفة المعرفة: الحواس والمحسوسات - بلقاسم, عبد الرزاق; الحاج, دواق (مجلة العلوم الاجتماعية والإنسانية, 2022)
Number: 002

تحقيق قصيدة الشيخ أطفيش في مدح سلطان زنجبار "حمود بن محمد": حكم 1314هـ - 1320هـ / 1896م - 1902م - بن ادريسو, مصطفى بن محمد (المجلة التاريخية الجزائرية, 2022)
Number: 002
Keywords: Atfiyyash; Muhammad b. Yusuf (1821-1914); Poésie – Mzab

أئمة وفقهاء الدولة الرستمية ودورهم في الحياة الاقتصادية للمغرب الأوسط 160 هـ. - 296 هـ. / 777 م. - 909 - بن شارف, أحمد (مجلة أبحاث, 2022)
Number: 002

المنجز الفكري والإصلاحي في آثار الشيخ "أبو عبدالله محمد بن بكر الفرسطائي النفوسي" - بن قومار, مليكة (مجلة الإحياء, 2022)
Number: 030
Keywords: Furṣuṭāʾī; Muḥammad b. Bakr

الحركة العلمية والمؤسسات التعليمية بمدينة أورجلان ورقلة: ما بين القرنين الرابع والسادس الهجري - بوتشيش, آمنة (مجلة الحوار المتوسطي, 2022)
Number: 002
Keywords: Enseignement – Ouargla

إسهامات المزابيين في مجال التطبيب والاستشفاء خلال الثورة التحريرية 1954-1962م - بوسعدة, محمد بن عمر (مجلة عصور, 2022)
Number: 001
Keywords: Mouvement national – Mzab

المغرب الأوسط: المجال والإنسان والاندماج - حصباية, محمد (المجلة التاريخية الجزائرية, 2022)
Number: 001

الحياة السياسية لعامة جبل نفوسة من خلال كتاب السير للشماخي "ت. 928 هـ. / 1522 م." - زايد, أسماء موسى علي (مجلة المنتدى الجامعي للدراسات الإنسانية والتطبيقية, 2022)
Number: 030
Keywords: Vie politique – Djebel Nefousa

جوانب من تاريخ مملكة تادمكة في ضوء نتائج الحفائر الاثارية وشواهد القبور من منتصف القرن الثالث حتى نهاية القرن السادس للهجرة 9-12 م. - غرياني, بطل شعبان محمد (حوليات الآداب والعلوم الاجتماعية, 2022)
Number: 605

الجانب الإلهي بين الإمام الغزالي المتوفي سنة "505" هـ. والإمام الجيطالي المتوفي سنة "750" هـ. من خلال كتابيهما إحياء علوم الدين وقناطر الخيرات: دراسة مقارنة - مبارك, مصطفى عبدالمنعم السيد (مجلة قطاع أصول الدين, 2022)
Number: 001

إباضية المغرب وخلافهم في الولاية والبراءة والامامة: قراءة تاريخية من المصادر الاباضية "ق. 2-3 هـ. / 8-9 م." - محمد, أمينة; غربي, بغداد (المجلة الجزائرية للمخطوطات, 2022)
Number: 002

الجماعات غير المالكية في منظور الفقه المالكي المغاربي من "ق. 2-5 هـ. / 8-11 م." - مهني, عز الدين; عمارة, علاوة (مجلة المعارف للبحوث والدراسات التاريخية, 2022)
Number: 004

الخلفية التاريخية النسبية والمذهبية لبني يفرن وأماكن وجودهم في المغرب والأندلس من الفتح الإسلامي إلى القرن الخامس الهجري/الحادي عشر الميلادي: دراسة تاريخية - نوار, أمل سعد; محمد, بان على (مجلة التراث العلمي العربي, 2022)
Number: 004

Explorations in the North-West Indian Ocean: The Research Journeys of the Palinurus along the Omani Coast in the mid-1800s - Risse, Marielle (2022)
MARIELLE RISSE (Salalah) introduced us to Oman, a country in the Indian Ocean world that was never under foreign control. It is also the only country on the Arabic peninsula that gets monsoonal rains. Risse focused on the two expeditions of the brig Palinurus, which took place in the 1830s and 1850s and were the first explorations by English speakers to the southern coast of Oman, around Dhofar. The expeditions had the goal of investigating whether the Omani coast and hinterlands could be of use to the British government. They also wanted to buy the island Socotra from the Sultan in order to use it for steamship traffic between India and Britain. The surviving accounts of the expedition shed light on the local peoples; they spoke three different languages but left no written records. Risse was able to trace indigenous knowledge through oral history traditions, which were approximately 150 years old by the time they were written down in around 1850. These records reveal that much more water was available at the time, indicating that climate change is already significantly affecting Oman.
Keywords: Récits de voyage – Oman

The Voyage of the Vénus - Belhacel, Abdelhakim (2022)
ABDELHAKIM BELHACEL (Paris) presented the voyage of the Vénus, a French vessel under the command of François Étienne de Rosily-Mesros, and the vessel Prévoyante, in 1785, which traveled to Comoros, Mauritius, and eastern Africa. The primary aim of this expedition was to establish a French colony in Mongalo near Zanzibar, which could serve as the base for the ivory and slave trade. In this region, different geopolitical interests were at play at the time: The local Mongalo saw the French as their ally against the Portuguese of Mozambique. A short-lived French colony existed from 1786 to 1790 before it went bankrupt and was quickly dismantled by orders of the Sultan. The expedition of these two vessels was generally regarded as a success.
Keywords: Relations – Zanzibar – France

جزيرة جربة المحلي والمركزي: خلال العصر الحديث - المريمي, محمد (اباديكا, 2022)
Keywords: Djerba – Empire ottoman; Ibadisme – Djerba

رسالة في تراجم علماء جربة - بن تعاريت, سعيد بن علي بن عمر (اباديكا, 2022)
Keywords: Abu Miswar; mosquée (Fahmine; Djerba); Abu Muhammad Kammus; mosquée (Hachene; Djerba); Abu Zakariyya Fasil; mosquée (Bani Bandou; Djerba); Ammi Umar; mosquée (Ghizen; Djerba); Attushi; mosquée al- (Wersighen; Djerba); Bardawi; mosquée al- (Mezrane; Djerba); Bin Ma'zuz; mosquée (Mezraya; Djerba); Bin Wiran; mosquée (Ajim; Djerba); Bin Ya'lâ; mosquée (Erriadh; Djerba); Bûlaymân; Mosquée (Cedghiane; Djerba); Bûlaymân; Mosquée (Ja’bîra; Djerba); Faqih Umar; mosquée al- (Ajim; Djerba); Hâra; mosquée al- (Sedouikech; Djerba); Midrâjin; mosquée (Mezraya; Djerba); Mihrab Gharib; mosquée (Ghizen; Djerba); Monuments – Djerba; Mthaniya; mosquée al- (Ajim; Djerba); Qasbiyyin; mosquée al- (Guellala; Djerba); Shaykh; mosquée al- (Guechaine; Djerba); Sidi Abd Allah; mosquée (Mezrane; Djerba); Sidi Bu Sa'id; mosquée (Bazim; Djerba); Sidi Garus; mosquée (Haddada; Djerba); Sidi Khalifa; mosquée (Houmt Arbah; Djerba); Sidi Sabbaḥ; mosquée (Tezdaine; Djerba); Sidi Salama; mosquée (Erriadh; Djerba); Sidi Salih; mosquée (Bani Bandou; Djerba); Sidi Waḥlan; mosquée (Haddada; Djerba); Sidi Yahya al-Yazmirtani; mosquée (Erriadh; Djerba); Sidi Zakri; mosquée (Mezraya; Djerba); Sidī Yaʿīsh; mosquée (Jaabira; Djerba); Talâkin; Mosquée (Ghizen; Djerba); Tîfarrûjîn; mosquée (Oualagh; Djerba); Tîwâjin; mosquée (Tîwâjin; Djerba); Yunus b. Taarit; mosquée (Fatou; Djerba)

Les Amazighs et la langue amazighe en Tunisie. État des lieux, enjeux et perspectives - Ben Maamar, Fathi (2022)
Keywords: Berbérisme – Tunisie

عمرو النامي ومنهجه في بيان ملامح النفاق وعلاجه، من خلال كتابه: "ظاهرة النفاق في إطار الموازين الإسلامية" - الخذراوي, عبد العاطي أبو العيد (مجلة أصول الدين, 2022)

Djerba, paysage culturel, témoignage d'un mode d'occupation d'un territoire insulaire :Rapport intermédiaire et demande d’informations complémentaires - Eyssar Kochlef, Chérifa (Icomos, 2022)
Keywords: Monuments – conservation – Djerba

Djerba, paysage culturel, témoignage d'un mode d'occupation d'un territoire insulaire : Résumé analytique (Ministère des Affaires culturelles, 2022)
Keywords: Monuments – conservation – Djerba

Djerba, paysage culturel, témoignage d'un mode d'occupation d'un territoire insulaire : annexe technique - Ben Nejma, Adnène; Ayari, Ghada; Cortoba, Amal; Haddouk, Asma; Ben Maïz, Amir; Mestiri, Yassine; Ben Maïz, Anouar (Ministère des Affaires culturelles, 2022)
Keywords: Monuments – conservation – Djerba

Djerba, paysage culturel, témoignage d'un mode d'occupation d'un territoire insulaire : plan de protection et de gestion - Boussoffara, Faouzi; Ghribi, Abdelhamid (Ministère des Affaires culturelles, 2022)
Keywords: Monuments – conservation – Djerba

Un projet musical autour des écoutes croisées entre le guembri tunisien et la leona mexicaine (Le Temps, 2022)
Keywords: Musique – Djerba

المؤرخ ابن سلام اللواتي (ت273ه/886م) وبدء التاريخ في إفريقية - الزرويل, صالح (مجلة العبر للدراسات التاريخية و الاثرية في شمال افريقيا, 2022)
الملخص باللغة العربية: أسهم المغاربة في بلاد المغرب عموما في كتابة تاريخهم منذ دخول الإسلام أرض إفريقية مع طلائع الفتح الأولى في القرن الأول الهجري، السابع للميلاد، ومن بين هؤلاء المؤرخين الأوائل نذكر: ابن سلاّم بن عمرو اللواتي النفوسي الذي عاش في بلدة أُغرميمان بجبل نفوسة التي تلقى فيها العلم على يد شيخه أبي أكبت وعاصر جزءًا هاما من الدولة الرستمية(160-296ه)، وكان كثير التنقل في أرجاء إفريقية ومصر وطرابلس وتوز ببلاد الجريد التي استقرّ فيها مدة من الزمن لطلب العلم، ولجمع روايات كتابه. احتوى كتاب ابن سلاّم على تعريف بأسس العقيدة الإسلامية، والتعريف بجمع من كبار الصحابة في صدر الإسلام، ثم يعرض بعد ذلك شرائع الدين المنظمة لحياة الفرد، ويسرد الأئمة الأوائل للمذهب الإباضي بالمشرق، ويتبعها بقائمة لمشايخ المذهب بالمغرب الإسلامي، وذكرٌ لدولة أبي الخطاب المعافري ودولة أبي حاتم الملزوزي أوائل القرن الثاني الهجري، ثم الرستميين من بعدهم. سلك ابن سلاّم في كتابه منهاج متعددة، فقد اختلف المؤرخون في تحديد منهجه، فمنهم من وصفه بمنهج كتب التاريخ العام، ومنهم من صنفه ضمن منهج كتب التراجم والمناقب، ومنهم من وضعه في خانة كتب السلالات، وهو بذلك لم يعتمد منهجا واحدا. Abstract: The historians of El-Maghreb have contributed to writing their history since Islam entered Ifriqiya "Africa"territory with the conquest in the first century AH, seventh century AD. Among these early historians was Ibn Salam Ibn Amr al-Lawati al-Nafousi, who lived in Agharmiman in Djebel Nafousa"mountain of Nafousa", where he received knowledge from Sheikh Abu Akbet as he lived during an important era of the Rustomid state(160-296 AH). He also was a frequent traveler throughout Ifriqiya, Egypt, Tripoli, and Tozer in the region of El Djarid; where he settled to seeking knowledge and collect his book. Ibn Salam’s book consists of the definition of the foundations of the Islamic Aqida"faith", a collection of the great companions in the early days of Islam, then showed the religious laws that ruled the life of the individual, and listed the early Imams of the Ibadiya sect in the Mashreq"east", followed by the sheikhs of the sect in the Islamic Maghreb, and mentioned the state of Abul-Khattab Al-Ma‘afiri, and the state of Abu Hatim Al-Malzuzi in the second century AH, and the Rustomid state after them. In his book, Ibn Salam adopted several approaches, Historians differed in defining his approach. Some of them described it as the general history approach. Some others classified it within the curriculum of books of biography and virtues, and some put it in the category of dynasties‘books; thus, it did not adopt a single approach.

أبو العباس أحمد الشماخي: سيرته ومنهجه في سيره - الزرويل, صالح (المجلة التاريخية الجزائرية, 2022)
تناولَت هذه الورقة البحثية بعضًا من جوانب سيرة حياة الشيخ أبي العباس أحمد الشماخي(ت928هـ/1522م) صاحب كتاب السير، وأحد أشهر مؤرخي جبل نفوسة، والتعريف بأهمّ مؤلفاته الأخرى الفقهية والعقدية والتي لا يزال أغلبها مخطوطا، أو هو في عداد المفقودات، كما تطرّقَت إلى منهجه الذي اتبعه في سيره وأسلوبه الذي سلكه، فهو أنموذج لكاتب سير مغربي إباضي، وضع بصمة تاريخية هامة على مستوى المكتبة المغاربية والإسلامية عموما، كما يُمثل آخر مؤرخي إباضية العصر الوسيط الذي جمع سير من قبله من المؤلفات السيرية الإباضية. توصلت إلى جوانب هامة في سيرة حياة الشماخي رغم نقص المؤلفات التي تناولت ذلك، تلك الجوانب التي صقلت شخصيته، كما أنه اتبع في سيره منهجا انفرد به، فقد مزج بين مناهج من سبقه كالورجلاني والوسياني والدرجيني بأسلوب بسيط، خال من غريب الألفاظ، استطاع بكتابه أن يجعل منه موسوعة سيرية إباضية جامعة لسير من قبله. This paper was exposed some aspects of the biography of Sheikh Abul-Abbas Ahmed Shamakhi(d.928ah/1522 ad), the author of the Siyar, , and the definition of his important other works of jurisprudence and doctrinal. It also touched on the approach that he followed in his biography , as he is a model for a moroccan Ibadi biographer, who represents the last Ibadi historians of the medieval era, who collected biographies before him of Ibadi biographies. I found that he followed in his biography unique approach, mixed the approaches of his pedecessors such as Wardjilani, Wassiani and Dargini, in a simple style, free of strange words, he was able in his book to makes him Siyars ibadi encyclopedia to walk before him.
Keywords: Prosopographie – Afrique du Nord

الشيخ أبو عبد الله محمد بن بكر الفرسطائي(ت440هـ/ 1048م): مؤسس نظام دولةٍ لا يزول بزوال الرجال - الزرويل, صالح (الناصرية, 2022)
يتناول المقال بعضا من جوانب حياة الشيخ أبي عبد الله محمد بن بكر بن أبي بكر الفرسطائي الإباضي مذهبا، النفوسي موطنا، واضع ومؤسس نظام العزابة في بلاد المغرب، ذلك النظام الذي لا يزال باقيا رغم مرور حوالي عشر قرون عليه، وهو صالح لكل زمان ومكان في الحل والترحال، يجمع بين السياسة والمجتمع والاقتصاد والتعليم وغيرها من المجالات. نشأ الشيخ أبي عبد الله بفرسطاء بجبل نفوسة(ليبيا)، وأخذ علومه عن مشايخ عصره فيها، كما أخذ عن الشيخ أبي نوح سعيد بن زنغيل بالحامة والشيخ أبي زكرياء بن أبي مسور اليهراسني بجربة(تونس)، كما استزاد في العلوم العقلية من جامع القيروان عن أبي زكرياء. كان رحالة في نشر العلم، فقد انتقل بحلقة علمه من نفوسة الى قسطالية بالجريد، وكنومة وتقيوس، ثم إلى أريغ ووغلانة وآجلو(حيث أسس نظام العزابة) ثم إلى ورجلان ومزاب، وكان موهوبا بالحكمة والرشد وحصافة الرأي وسداد التفكير وحسن التقدير، له في كل فن تآليف كثيرة، جمعها تلاميذه. توفاه الأجل بأجلو سنة 440هـ/1048م. رغم شظف العيش والمسيرة التعليمية الشاقة والظروف السياسية العصيبة التي عاشها الشيخ أبو عبد الله محمد الفرسطائي إلا أنه استطاع أن يترك بصمته للإباضية من بعده، ويؤسس نظاما يحفظ المذهب والمجتمع؛ سواء كان حرا أو تحت حكم أية دولة. Abstract: The research includes some aspects of the life Sheikh Abu Abdallah of his doctrine and his Libyan region nafoussa The founder of the Azzaba system in biled el maghreb which has remained effective until today and valid in all times and places. The system translator settles down from his place of birth then he took all the sciences by great scientists who lived the same period such as: Cheikh Abu Nouh Said Ibn Zanguil au Hamma de la Tunisie, et le Cheikh Abu Zakaria Ibn Abi Messouar El yarassini de Djerba, put again the mental science of Djamia El Kairaouane de Abu Zakaria. He was a traveler whose purpose was to publish knowledge. from Nafoussa to Kastilia of Djerid towards Kennouma and Tekyous. and to Righ and Ouargla and M'zab. His character wisdom and prudence from his point of view. among his collections which were gathered by his apprentices "Kitab Attouhaf El Makhzouna", he is died in the year 440/1048.
Keywords: Furṣuṭāʾī; Muḥammad b. Bakr

Narratives of Migration from East Africa to the Arabian Gulf during the decades of the 1960s and 1970s - Baraza, Swahili; Matthews, Nathaniel (2022)
Zentrum Moderner Orient (ZMO)

المسائل الخلافية بين الأشعرية والإباضية - دراسة استقرائية تحليليلة مقارنة - درار, نسمة; رجاتي, نورة (مجلة البحوث العلمية والدراسات الإسلامية, 2022)
تتحدث هذه الدراسة عن الاختلاف العقدي؛ فشأنه شأن الاختلاف الفقهي، وكان النموذج المختار لذلك؛ المسائل الخلافية بين الأشعرية والإباضية، من خلال الوقوف على المبادئ والأصول العقدية لكل من المذهبين الأشعري والإباضي؛ ومدى اتفاقهما واختلافهما.وقد تم التوصل من خلال هذه الدراسة إلى أن الاختلاف الذي بين الأشعرية والإباضية؛ كان في الفروع، وهو اختلاف أقرب إلى التنوع من التضاد. Abstract This study talk about differences of faith ; is the same as difference in the branches of Islamique Fikh; and it was the chosen model for that ; Conflicting Issues between Ach’arism and Ibadhism, through examining the principles and creedal origins of Alachari ideology and Ibadhism ideology, and the extent of their agreement and disagreement. .It was found through this study ; that the defference between Ach’arism and Ibadhism he was in the branches ; and he is closer to diversity than antagonism

التعايش والتسامح المذهبي والديني والعرقي في دولة الرستميين - هشام, نمر بومدين (مجلة عصور الجديدة, 2022)
سنعالج في هذا المقال مسألة التعايش والتسامح المذهبي والديني والعرقي في دولة الرستميين، حيث تضمن ستة عناصر، سنتطرق في أولها إلى التعريف بالتسامح والتعايش، واللذين يتلخصان في مسالمة الآخر وتقبله، وبعد ذلك ننتقل للحديث عن المذهب الإباضي وكيفية دخوله إلى المغرب الإسلامي، الذي كان اعتناقه كرد فعل على سياسة الولاة الأمويين تجاه البربر، ثم سنتطرق إلى قيام دولة الرستميين، والظروف التي ساعدت على قيامها، بعدها سنتناول عوامل التنوع العرقي والمذهبي والديني بالدولة الرستمية، والتي تتمثل: أولا: في طبيعة النظام السياسي والمذهب العقدي للدولة الذي أتاح التعددية، والذي كان قائما على سياسة العدل والتسامح التي أقرها الأئمة، وثانيا: في التجارة التي ساهمت في دخول عناصر جديدة إلى الدولة الرستمية، ولا سيما تاهرت عاصمة الدولة، تلى ذلك عنصر تحدثنا فيه عن بعض المظاهر التي عكست هذا التعايش والتسامح المذهبي والديني والعرقي في هذه الدولة، وتجلت هذه المظاهر فيما يلي: المناظرات الدينية والعلمية، التي كانت تتم في جو من التفاهم والحوار الهادئ، وكانت أشهرها المناظرة بين الإباضية والمعتزلة، وكذلك في الحرية الدينية والمذهبية والفكرية، وفي إيواء اللاجئين السياسيين من مذاهب مخالفة، وأيضا في والمساواة بين الإباضية من كافة الأعراق في تولي منصب الإمامة، وفي آخر عنصر قمنا بالتعريف ببعض الأعلام غير الإباضيين الذين عاشوا في الدولة الرستمية. In this article, we will deal with the issue of coexistence and sectarian, religious and ethnic tolerance in the state of the Rustamids; It contains six elements ; In the first place, we will discuss the definition of tolerance and coexistence, which are summarized in the peace and acceptance of the other ; And then we move on to talking about his entry into the Islamic Maghreb, whose embrace was as a reaction to the policy of the Umayyad rulers towards the Berbers ; Then we will discuss the establishment of the Rustamid state, and the circumstances that helped establish it ; Then we will address the factors of ethnic, sectarian and religious diversity in the Rustumiya state; This was followed by an element in which we talked about some aspects that reflected this sectarian, religious and ethnic coexistence and tolerance in this country; In the last element, we introduced some non-Ibadi figures who lived in the Rustumiya state.
Keywords: Tolérance religieuse – Tahert

تاهرت مدينة الجلال والعظمة في عيون العلماء والرحالة والمؤرخين والجغرافيين - كربوش, إبراهيم (مجلة هيرودوت للعلوم الإنسانية والاجتماعية, 2022)
يتناول الملخص إحدى المدن الجزائرية العريقة التي كتبت اسمها على صفحات التاريخ الجزائري، ومضى ذكرها في عرض البلدان وطولها، إذ نافست مدنا عريقة زاهية كبلخ ودمشق والعراق. وهي دولة إباضية أسست بنيانها في المغرب الأوسط، وهي كذلك من الدول التي استقلت عن الدولة العباسية. وعرفت ازدهارا واسعا، غطى مجالات الحياة المختلفة علما، فكرا، فلسفة وعمرانا، وزادها موقعها الاستراتيجي حصانة ومنعة، كما أنها كانت أرضا خصبة كثيرة الخيرات كثيرة المياه، وأشتهر حكامها بالعلم والفقه، فأشاعوا الحريات ومبادئ التسامح، فكانت بذلك بلدا آمنا، يقصده الناس من كل حدب وصوب، حيث أمّها العلماء، الرحالة، الجغرافيون، المؤرخون وغيرهم، وكل سال لسانه تعبيرا عن جمالها، وكثرة خيراتها، و وفرة مياهها، وازدهار عمرانها. Abstract: The summary deals with one of the ancient Algerian cities whose name was written on the pages of Algerian history, and it was mentioned in the width and length of the countries, as it competed with the ancient and colorful cities of Kabalkh, Damascus and Iraq. It is an Ibadi state that established its structure in the central Maghreb, and it is also one of the countries that became independent from the Abbasid state. And it knew a wide prosperity, which covered the various fields of life in science, thought, philosophy and urbanization, and its strategic location increased its immunity and inviolability. It swayed towards and towards, where its mother was scholars, travelers, geographers, historians and others, and each spoke his tongue to express its beauty, its abundance of bounties, its abundance of water, and the prosperity of its construction. Keywords: geographers; historians; Ibadites; Tahert; travelers
Keywords: Tolérance religieuse – Tahert

دور العقيدة الإباضية في المحافظة على المجتمع الرستمي - الحلقة أنموذجا- - ليبدري, بلخير (مجلة أنثروبولوجية الأديان, 2022)
الملخص: تدور هذه الدراسة حول أهم تنظيم عرفه المجتمع الإباضي هو الحلقة أو العزابة التي تظل ركيزة أساسية في المنهج والمذهب الإباضي نظرا لاهتمامهم بالتعليم وتربية النشئ وزادت أهمية الحلقة بعد سقوط الدولة الرستمية على يد الشيعة الفاطميين فأرادوا بها إعادة بعث المجتمع الإباضي والمحافظة عليه. Résumé : La présente étude tourne au tour de l’une des plus importantes organisation qu’a connu la société ibadite : « lahalka » ou « Hazzaba »celle ci demeure le principale pilier de la doctrine Ibadite, vu l’importance quelle accorde à l’enseignement et particulièrement après la chute de l’état rostomidevaincue par les fatimides d’obédience chiite, cet intérét accordé à l’enseignement visé a préserver la société ibadite et la promouvoir

الشيخ أبو عمار عبد الكافي الورجلاني (ت قبل 570هـ/1174م) -سيرته ومنهجه في سيرته- - الزرويل, صالح; بحاز, إبراهيم بن بكير (الساورة للدراسات الانسانية والاجتماعية, 2022)
تهدف هذه الورقة البحثية للتعريف بالشيخ أبي عمّار عبد الكافي التناوتي الوارجلاني(ت قبل570ه/1174م) في سيرة حياته، نشأة وتعلّما، وتعليما وتأليفا، مع ذكر كتابه السير ومنهجه فيه، فهو عَلَم من أعلام الجزائر في تاريخها الوسيط، مهتمٌّ بكتابة السير وعارف بمدى أهميتها أما جميع أنواع الكتابات التاريخية الأخرى. ساهم بمؤلفه المشهور"سير أبي عمّار" في ذكر سلسلة مشايخ الإباضية من لدن أبي عبيدة مسلم بن ابي كريمة البصري في القرن الأول الهجري وإلى زمان أبي يعقوب يوسف بن إبراهيم السدراتي الورجلاني، فهو بذلك يربط بين القرون زمانا وبين المشرق والمغرب مكانا، وقد ضمّن كتابه الأساس الذي قام عليه الإباضية والسير التي تمسّكوا بها عبر الأزمنة والأوطان، رغم المحن والشدائد التي تعرّضوا لها إلا أنهم استطاعوا الصمود والبقاء بفضل نظام العزابة الذي كان الشيخ أبو عبد الله الفرسطائي منظرا له، وأبي عمار باعثه ومطوّره. This research paper seeks to introduce Sheikh Abi Amar Abdul Kafi Al-Tnawati Al-Warjilani (before570Ah/1174Ad), in his biography; Growing up and learning, teaching and composing, with his book and curriculum in it. He learned from Algeria's medieval history, interested in writing the walk, and knew how important it was to all other kinds of historical writings. With his famous author "Siyar Abi Amar," he contributed to the series of epigraphic commenter's from Abu Ubayda Muslim Ibn Abi Karima and to the time of Abi Yacoub Yucef al Al-Warjilani. On the other hand, his book guarantees the basis for the allegory and the progress that they have pursued through times and nations, despite the hardships and hardships. However, they have been able to survive thanks to the undisputed regime of the Azzaba Ring. Since its establishment in the 5th/11th century, it was founded by Sheikh Abu Abdullah Mohammed bin Bakr bin Abi Bakr Al-Faristaei Al-Nafuss , who looked at it, and was its developer.
Keywords: Biographies – Ouargla

الشيخ المؤرخ إبراهيم أبو اليقظان الجزائري وإسهاماته التاريخية (1888-1973م) - الزرويل, صالح (رفوف, 2022)
يعتبر الشيخ أبو اليقظان (1888-1973)، أول صحافي وإعلامي جزائري قاوم الاستعمار الفرنسي بجرائده الثماني، التي كان يصادرها المستعمر، لكن في نفس الوقت كان من بين المؤرخين الذين تركوا تآليف كثيرة في التاريخ عامة، وفي التاريخ الإباضي الوسيط بخاصة، الذي غلب عليه طابع التراجم، فقد كتب عن كبار شيوخ الإباضية كالإمام عبد الله بن إباض والشيخ أبي إسحاق إبراهيم اطفيش وغيرهم، كما خصّ نفسه بترجمة مستفيضة عن تفاصيل حياته، كما كانت له كتابات أخرى في أحوال بلدته القرارة بولاية غرداية، وأهم إنجاز تاريخي يُحسب له هو ملحق سير الشماخي في ثلاثة أجزاء، أتم به ما انتهى إليه الشيخ الشماخي(ت928هـ) صاحب كتاب"سير الشماخي"، وهو بمثابة حلقة وصل بين مشايخ الإباضية في التاريخ الوسيط ومشايخ العصر الحديث والمعاصر، وتبقى جلّ مؤلفاته مخطوطة تنتظر التحقيق العلمي. ونحن نرمي إلى التعريف بمؤلفاته التاريخية علّها تجد من يهتم بتحقيقها ودراستها. Chaykh Abul-Yakdan, through his eight newspapers which has been confiscated one by one, is the first journalist who fought against the French colonization. He was, besides, a historian who wrote many books about general history and the Ibadhi Medieval one in particular. His style was mainly biographies at which he wrote about senior Ibadi scholars “shuyukh” such as Imam Abdullah bin Ibad, Abu Ishaq Ibrahim Tfayesh and others. He has dedicated as well certain chapters to his life, and other writings on his hometown Guerrara in Ghardaia. His most important historical achievement is The Shammakhi Biographies Addendum“Moulhak of Siyar Shammakhi” in three volumes; in which he completed what Chaykh Shammakhi ended. This book was the bridge between Ibadhi Medieval & Modern Eras scholars. Most of Abul-Yakdan’s manuscripts remain, awaiting scientific treatment. We aim, through this research, to introduce his historical writings that may find someone will take care of it.
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973)

نظام العزابة وآلياتها في ضبط الجماعة الإباضية بمزاب - بسيس, نصرالدين; رميتة, أحمد (مجلة العلوم الإنسانية والاجتماعية, 2022)
نظام "العزابة" في "مزاب"، نظام اجتماعي أثبت قدرته في ضبط الجماعة الإباضية قرابة ألف عام. نظام جدير بالبحث عن سرّ بقاءه وفعاليته. سنحاول في هذه الورقة البحثيّة أن نكشف الأسس القاعدية التّي يتشكّل منها هذا النّظام؛ وكيف أسّست منظومة القيم للعقيدة الإباضية قواعده ليستجيب لوضع إباضية شمال إفريقيا المضطّرب؟ ابتدأت خطتنا المنهجيّة بمعرفة سبب ابتكار نظام العزابة ليكون بديلا عن "إمامة الكتمان"، ولماذا اختار منطقة مزابَ كمأمن يلجؤون إليه رغم قساوة طبيعتها، وما الذي مكَّنَه من أَنْ يكون المرجعية السّلطوية فيه بوجود سلطة "العوام" القبلية؛ ولكون المجتمع المزابي يقوم على قاعدة دينية فقد حاولنا تسليط الضوء على العقيدة الاباضية، حيث تحليل مبادئها سيكشف عن منظومة القيم الأساسية التّي اعتمدها نظام العزابة في تسيير شؤون المجتمع المزابي، وضبط علاقاته الدّاخلية والخارجية بما يحفظ للجماعة المزابية تماسكها وتضامنها مهما كانت حالتها، وأخيرا عرض التحدّيات التّي تواجه نظام العزابة في الدّولة الوطنية وانعكاسات ذلك على السّياسة المحلية، وردود أفعال المزابيين حيال هذه الانعكاسات. The "Azzaba" system in "M’zab" is a social system that has proved its ability to control the the Ibadite community for nearly a thousand years. It is worth investigating the survival and effectiveness of this system. In this research paper، we seek to uncover the basic foundations that make up this system، why did the Azzaba system choose M’zab as a safety zone، even though it is a difficult area to live in، and what enabled this system to be the authoritarian reference in "M’zab" with the existence of the "Awam" tribal authority. Considering that M’zab society is based on religious grounds، we try to shed light on the Ibadite doctrine so that the analysis of its principles will reveal the system of the fundamental values adopted by the "Azzaba" system in running the Mozabite society، and controlling of its internal and external relations in a manner that preserves cohesion and solidarity in all circumstances and situations. Finally، the paper presents the challenges facing the "Azzaba" system in the national state and their implications on local politics، and the reactions of the Mozabites towards these repercussions. Le système « Azzaba » de « M’zab » est un système social qui a prouvé sa capacité à contrôler la communauté Ibadite depuis près de mille ans. Il vaut la peine d’étudier la survie et l’efficacité de ce système. Dans cet article de recherche, nous cherchons à découvrir les fondements fondamentaux qui composent ce système, pourquoi le système Azzaba a-t-il choisi M’zab comme zone de sécurité, même si c’est une zone difficile à vivre, et ce qui a permis à ce système d’être la référence autoritaire dans « M’zab » avec l’existence de l’autorité tribale « Awam ». Considérant que la société M’zab est fondée sur des motifs religieux, nous essayons de faire la lumière sur la doctrine Ibadite afin que l’analyse de ses principes révèle le système des valeurs fondamentales adoptées par le système « azzaba » dans la gestion de la société Mozabite, et le contrôle de ses relations internes et externes d’une manière qui préserve la cohésion et la solidarité dans toutes les circonstances et situations. Enfin, le document présente les défis auxquels est confronté le système « azzaba » dans l’État national et leurs implications sur la politique locale, et les réactions des Mozabites face à ces répercussions.

هجرات القبائل الإباضية من المغرب الأوسط إلى بلاد الأندلس خلال القرن (4هـ-10م) - كرطالي, أمين (الباحث, 2022)
خلال القرن الرّابع الهجري شهدت بلاد المغرب الأوسط صراعا قويّا بين الفاطميّيين وحلفائهم من الكتاميّين ثمّ الزيريّين، و حلفاء الأمويّين في الأندلس من قبائل زناتة وغيرها والتي كان عدد منها يتبنّى المذهب الإباضي، نجم عن هذا الصّراع إضافة إلى ما عرفته بلاد الأندلس من حوادث هجرةَ عدد من القبائل البربرية الإباضية إلى بلاط الأمويين في الأندلس، ولعبت هذه القبائل أدوارا بارزة في الصعيدين السياسي والعسكري، وساهم ذلك في انحصار المذهب الإباضي ببلاد الزاب وعدد من مدن المغرب الأوسط. During the fourth century AH, the Middle Maghreb witnessed a strong conflict between the Fatimids and their allies from the Katamites, then the Zirids, and the allies of the Umayyads in Andalusia from the Zenata tribes and others, a number of which adopted the Ibadi sect. The Ibadi Berber tribes to the Umayyad court in Andalusia, and these tribes played prominent roles in the political and military levels, and this contributed to the confinement of the Ibadi sect in the country of the Zab and a number of cities in the central Maghreb.
Keywords: Emigrations – Afrique du Nord – Andalousie; Ibadisme – Andalousie

حفريات في أقدم نص فلسفي مخطوط في تعريف الإنسان في التراث الإباضي المغاربي (كتاب الإنسان)، إبراهيم بن ملال المطكودي المزّاتي البصير أبو إسماعيل (300ه-350 ه) - عبد الرزاق, بلقاسم; دواق, حاج (الفكر المتوسطي, 2022)
ملخص: محاولة تهدف إلى تطبق منهج "علاقات النص" قصد اكتشاف نصوص في الفلسفة، و علم الكلام في مصادر التراث الكلامي المخطوط عند الإباضيين المغاربين، إنطلاقا نص كلامي من القرن الثالث لمتكلم إباضي مغاربي، هو إبراهيم بن ملال المطكودي المزاتي البصير ( 300ه-350 ه)، ثم هذا النص نجده مقتبسا في مخطوط ثان هو" كتاب السؤالات" "لأبي عمرو عثمان بن خليفة السوفي"(ق6ه)، كما قام متكلم إباضي ثالث هو " أبو عمار عبد الكافي التنتاوي الوارجلاني" بشرحه ضمن الشرح الكلي للكتاب .إن الفرضية التي تنطلق منها الدراسة هي إمكانية اكتشاف أقدم نص فلسفي كلامي مغاربي يعرف الإنسان. و تحقيا لهذا الهدف وجب التمهيد لهذه الدراسة، بماهية الإنسان لدى المدارس الكلامية، بغرض تأصيل النصوص القديمة، في ما يصطلح عليه بالمدونة الكلامية المغاربية. Abstract : An attempt aimed at applying the "text relations" approach in order to discover texts in philosophy and theology in the sources of the written theological heritage of the Ibadis of the Maghreb, starting with a speech text from the third century of a Maghreb Ibadi speaker, Ibrahim bin Mellal Al-Matkoudi Al-Mazzati Al-Basir (300 AH-350). e) , Then we find this text quoted in a second manuscript, “The Book of Questions” by Abu Amr Othman bin Khalifa Al-Sufi (C6 AH), and a third Ibadi speaker, “Abu Ammar Abdul Kafi Al-Tantawi Al-Wargelani” explained it within the overall explanation of the book. The hypothesis that stems from it The study is the possibility of discovering the oldest spoken philosophical text of the Maghreb that knows man. In order to achieve this goal, it is necessary to prepare for this study, the nature of man in the theological schools, with the aim of rooting the ancient texts, in what is termed the Maghreb theological code
Keywords: Foi – Traité – 10e siècle

الأدوار السياسية والمذىبية لقبيلة هوارة في الغرب الإسلامي في العصر الوسيط - بن عبد المؤمن, سارة مروى (جامعة ابن خلدون, 2022)
تعالج هذه الدراسة الأدوار السياسية والمذهبية لقبيلة هوارة البرنسية في العصر الوسيط في الغرب الإسلامي، معرجة على مختلف المساهمات السياسية لهذه القبيلة وأهم الدول و الكيانات السياسية التي أسستها ،وإبراز مظاهر قوة و ضعف هذه القبيلة ،وكذا إسهامات علماء و فقهاء القبيلة في حياة المذهبية و الفكرية على حد سواء .
Accepted: 2023-01-24T13:21:12Z

الاجتهاد المقاصدي عند الإباضية في باب الأحوال الشخصية - الصادق, ياسين بن أحمد (جامعة غرداية, 2022)
لقد حاول الباحث في هذه الدّراسة البحثَ في جانب الفِكْرِ المقاصديّ للإباضيّة في باب من أبواب الفقه؛ حيث حاول الإجابةَ عن مدى توظيف عُلماء الإباضيّة للنّظر في المقصد، والكشف عن الحِكمة، واستنباط المصلحة من إقرار الْحُكم الفقهيّ أو توجيهه في مسائل الأحوال الشّخصيّة. وقامت أسسُه وارتكزت على بيان طرق تحقيق المقاصد الكليّة، واستندت على إيضاح وسائل تحصيل المصلحة الشّرعيّة، من خلال إقرار الأحكام الشّرعيّة العَمليّة، وبيان أثر ذلك على الفرد والأمَّة؛ وذلك في أبواب الأسرة والوصايا والمواريث والهبات والأوقاف. بناءً على ما تقدّم؛ فإنّه قد أجال النّظر في معالم الفِكر المقاصديّ، ومسالك النّظر الاستصلاحيّ لعُلماء المذهب، وأَعْمَل الفِكر في اجتهاداتهم واستنباطاتهم، وتحليلاتهم وتوجيهاتهم للأحكام الفقهيّة في باب الأحوال الشّخصيّة في ضوء المقاصد الكليّة والأهداف العامَّة للشّريعة الإسلاميّة، دون البحث في المقاصد الجزئيّة، وبعيدا عن كشف الأدلّة والمناهج الاجتهاديّة الأصوليّة، ووَفقا لهذه النّظرة واستنادا عليها تحدّدت معالم البحث وانبنت فصوله ومباحثه، وانتظمت تفاصيله وجزئيّاته. فجاءت المقاصد الكليّة الضّابطة لباب الأسرة مُتمثّلة في التعبّد والخشية لله، وحفظ النّسل، وتحقيق السّكن والاستقرار. وتمثّلت الأهداف العامّة الحاكمة لأبواب الوصايا والمواريث والهبات والأوقاف في التّقوى والْهُدَى، وإقامة العدل، وتحصيل المصالح ودرء المفاسد. وخَلُص البحث إلى أنّ جميع الأحكام إنّما شُرعت لحفظ الأمّة، وصَوْنِ نِظامها، وتحقيق التّكامل والتضامُن بين أفرادها، وَوِقايتها من اضطراب الحال، وحِراستها من سوء المآل.
Accepted: 2022-05-23T13:52:14Z
Keywords: Ijtihad

ثورة أبو الخزر يغلى بن زلتاف، وأبو نوح سعيد بن زنغيل الوسيانيان 358هـ/968م مظهر من مظاهر التضامن الإباضي في بلاد المغرب - معاش, أسامة; بن عمر, علال (مجلة المواقف, 2022)
بعد سقوط الدولة الرستمية حافظ الإباضيون على الروابط الاجتماعية والاقتصادية والثقافية التي جمعتهم، ومن مظاهر هذه العلاقات ثورة أبي الخزر يغلى بن زلتاف وأبي نوح سعيد بن زنغيل الوسيانيين، وأردنا من خلال هذا المقال التعريف بهذه الثورة من خلال تتبع السياق التاريخي لظهور قادتها ومن ثم الشرارة الأولى لانطلاقها، ولاسيما الاستجابة التي تلقتها الدعوة للانضمام إلى هذا العمل من قبل الإباضية في مختلف المناطق، وانتهاء بـمصير قادتها وانعكاساتها. والواقع أن كل هذه المراحل تضمنت شيئًا من الاتحاد الذي جمع أنصار المذهب الإباضي.
Keywords: Ibn Kaydad

نظرية المصلحة عند الإباضية وتطبيقاتها الفقهية من خلال آثار ابن بركة وأبي سعيد الكُدَمي - فخار, جابر بن سليمان (جامعة غرداية, 2022)
تطرُق الدراسة موضوعا أصوليًّا مقاصديا متجدِّدا، من زاوية تراثية، حيث تهدف إلى تقديم صورة شاملة عن نظرية الـمصلحة عند الإباضية من خلال نتاجهم الفقهي والأصولي، في بناء منهجي، محاولا استيعاب الـمفاصل الأساسية للموضوع عبر مسلك الاستقراء، وعرضها في أسلوب إقناعي يقوم على منهج التعليل والتدليل. ويحاول البحث الإجابة عن ثلاثة أسئلة رئيسة هي: ما أسس النظرية؟ ما هي قواعدها الـمنهجية؟ ما هي خططها الإجرائية؟ أما مفاصل الدراسة فهي تشتمل على فصل تمهيدي وخمسة فصول، ثم خاتمة تتضمن أهم النتائج الـمتوصل إليها؛ حيث احتوى الفصل التمهيدي على التعريف بشخصية الإمامين ابن بركة والكدمي من حيث مسيرتهما وآثرهما العلمية، مع الوقوف على أهم خصائص مدرستهما الفقهية. هذا، وتشترك الفصول الثلاثة الأولى في بحث أسس النظرية وقواعدها الـمنهجية؛ حيث خصص الأول لدراسة مصطلح الـمصلحة، والـمصطلحات ذات الصلة في التراث الفقهي، ثم سؤال الـمرجعية في إدراك الـمصالح. أما الفصل الثاني فتمحض لمسائل التعليل، وكان الفصل الثالث لدراسة علاقة الـمصلحة بالنص توافقا وتعارضا، مع بيان أهم الـمسالك الـمنهجية الكفيلة برفع التعارض، وتحقيق الانسجام والتكامل. وفي الفصل الرابع عرضٌ لموقف الإباضية من الأدلة الاجتهادية الـمبنية على الـمصلحة، تأصيلا وتطبيقا، وخُصِّص الفصل الأخير لموضوع فقه الـموازنات عند الإمامين، محاولا اكتشاف أهم قواعد الـموازنة والترجيح بين الـمصالح والـمفاسد. وقد أبانت الدراسة عن منطق البحث الفقهي لدى علماء الإباضية في التعامل مع الـمصالح والنصوص، حيث كان الاجتهاد الـمصلحي عموما قائما على أساس معقولية الأحكام ومصلحية التشريع جملة وتفصيلا، متخذا قواعد منهجية ضابطة للنظر العقلي، وخطط إجرائية كفيلة بسداد الفهم، وسلامة التطبيق لمقررات التشريع، بما يحقق مقاصدها الـمنشودة. كما كشفت الدراسة عن تميُّز كلٍّ من الإمامين بمنهج في الاستدلال بالـمصالح؛ حيث كان ابن بركة ينحو منحى التدليل القياسي تأييدا لاجتهاده الـمصلحي، مما يدل على هيمنة دليل القياس في فكره الفقهي، أما الكدمي فقد تميز بتلك العقلية الاستقرائية التي تتخذ من الـمعاني الكلية سندا في النظر الـمصلحي.
Accepted: 2022-01-05T10:56:14Z
Keywords: Fiqh

قاعدة «الأمور بمقاصدها» وتطبيقاتها في فقه الأحوال الشّخصيّة عند الإباضيّة (باب الأسرة أنموذجا) - الصادق, ياسين بن أحمد; باجو, مصطفى بن صالح (المعيار, 2022)
تتجلّى أهمّية هذه الدّراسة في كونها تهدف إلى بيان مدى التفات عُلماء الإباضيّة قديمًا وحديثا إلى اعتبار النيات، والاعتداد بالمقاصد، ومدى تفعيلهم لقاعدة "الأمور بمقاصدها" وما تفرّع منها في فروعهم الفقهيّة في باب الأحوال الشّخصيّة، وتقصد إلى إبراز الفكر المقاصديّ والنّظر الغائيّ المبثوث في فتاويهم، والماثل في أقضيتهم، مُحاولة تقديم إجابةٍ عِلميّة عن إشكاليّة مدى احتفاء العقل الفقهيّ الإباضيّ باعتبار المقصد عند الاجتهاد، ومدى اعتداده بالنّية لدى نظره في أفعال العِباد. وقد انتهت الدّراسة عَقِب التَّطواف والتَّجوال في مصادر المذهب قديمها وحديثها إلى أنّ عُلماء المذهب اعتبروا النيّة أساس الأعمال، وعَدُّوا القصد محور الأفعال، تدور معه وجودًا وعدمًا؛ فحيث وُجدت النيّة، وتوفَّر القصد؛ وُجد العمل وثَبت الْـفِعل، وحيث فُقِدت النيّة، وغاب القصد؛ انعدم العمل، ولم يجزئ الفعل؛ وثمرةً لذلك فإنّ قاعدة «الأمور بمقاصدها» وما تفرّع منها كانت حاضرةً في نَظرهم، وراسخة في فكرهم، وعُدّت مُوَجِّها رئيسًا يحدّد وجهة اجتهاداتهم، وبَوْصلة أمينة تضبط استنتاجاتهم. This study’s importance appears in highlighting the extent to which the Ibadi scholars, in the past and present, pay attention to the consideration of intentions, estimation of the purposes, and the extent to which they activate the rule of "matters are evaluated based on their purposes" and its jurisprudential branches in the personal status chapter. In addition, the current investigation intends to highlight the intentional thought and teleological consideration transmitted in their fatwas, and present in their judgments, attempting to provide a scientific answer to the problem of the extent to which the Ibadi jurisprudential mind celebrates the intent in the Ijtihad, and the extent to which it relies on intention when considering the actions of the servants. After a digging deeper into the Ibadi doctrine literature, both old and recent, the study concluded that the scholars considered the intention as the basis of actions, and the purpose as the axis of deeds be it in being or nothingness; whenever the intention and the purpose are available the action is found and the deed is proven, and whenever the intention and the purpose are absent the action ceases to exist and the deed was insufficient. As a result, the rule of "matters are evaluated based on their purposes" and its derivatives were present in the Ibadi scholars' view and firmly rooted in their thought. Moreover, this rule is considered the leading factor determining the direction of the Ibadi jurisprudential diligence and an honest compass controlling its conclusions.
Keywords: Fiqh

كتاب "الإيضاح" للشيخ عامر بن علي الشماخي (ت 792هـ/1279م) -دراسة وتحقيق كتاب الشركة - الدبوز, حسن بن عيسى (جامعة غرداية, 2022)
يعتبر الشيخ عامر بن علي الشماخي (ت792هـ/1279م) أحد أبرز أعلام المدرسة الإباضية الذين ساهموا في مجال التأليف، مع قلة العناوين التي تركها، إلا أن كتابه "الإيضاح" برز بروزا واضحا في المذهب، فاهتم به الطلبة وأشاد به العلماء قديما وحديثا، واعتمده الفقهاء المغاربة مرجعا للفتوى في زمانه إلى يوم الناس هذا وفي مختلف حواضر الإباضية، كما اهتم به المشارقة كثيرا، وحظي بالاعتناء به حاشية واعتمادا وتلخيصا ونسخا وطباعة، إلا أنه لم يحظ بتحقيق علمي يبرزه كما ألَّفه مؤلفُه، ويكشف عن مكنوناته ومنهجه، ومن هذا المنطلق جاء هذا البحث لدراسة قسم من أقسامه وتحقيقه، تحت عنوان: كتاب "الإيضاح" للشيخ عامر بن علي الشماخي (ت792هـ/1279م) -دراسة وتحقيق كتاب الشركة- وفي هذا البحث تحقيق نص الكتاب بالمقارنة بين نسخه الخطية، وضبط نصه وخدمته، إلى جانب دراسة مضمون هذا النص لمعرفة منهج المؤلف في تأليفه، ودراسة مدى التزامه به في أبواب الكتاب، وبيان ما لم يذكره المؤلف من الجوانب المنهجية للكتاب من ذكر المصادر التي اعتمد عليه، وكذا منهجه في إقرار المسائل وأحكامها وما عليه العمل منها، ومنهج الاستدلال والتعليل في الكتاب.
Accepted: 2022-05-24T14:18:13Z

الفروق الفقهية عند الإباضية - علواني, إسماعيل بن إبراهيم (جامعة الحاج لخضر, 2022)
يتناول هذا البحث دراسة لعلم الفروق الفقهية عند الإباضية تنظيرا و تطبيقا، و هذا من خلال كتب أصول الفقه في المذهب الإباضي و استقراء الفروق الواردة في كتابي مدونة أبي غانم و جامع ابن بركة، متبعا في ذلك كله: المنهج الوصفي في المقدمات التنظيرية؛ و المنهج التوثيقي في جمع و تركيب الفروق المتناثرة في الكتابين؛ و المنهج التحليلي في تأصيل الفروق الفقهية في جانبيها التنظيري و التطبيقي و إثراء المسائل و مناقشتها . فجاء البحث مقسما على بابين؛ الأول خصصته للجانب النظري و دراسة منهج الفروق المستخلصة؛ و الثاني: ضمنته الفروق المستخرجة من الكتابين عينتي البحث، و تفرع عن كلا البابين ثلاثة فصول؛ فكانت فصول الباب الأول في بيان حقيقة الفروق الفقهية، و أهميتها و مراحل نشأتها، و تأصيلها الأصولي و الفقهي، مع عرضٍ لمناهج التفريق الفقهي و مسالك الكشف عن الوصف الفارق في كتب الفروق عموما، مرصعا هذا الباب بتوضيح منهج التفريق الفقهي عند الإمامين أبي غانم و ابن بركة من خلال كتابيهما المدونة و الجامع . و تناولت في فصول الباب الثاني من البحث مسائل الفروق المستخلصة من كتابي المدونة و الجامع، في جانب العبادات و الأيمان و النذور، و جانب العقود و المعاملات، و كذا مسائل القضاء و الدعاوى و الشهادات. و كللت الرسالة بخاتمة حاوية لأهم النتائج و التوصيات. و أهم ما يمكن أن نسجله من النتائج في هذه الدراسة : - بعد الاستقراء للفروق الفقهية الواردة في مدونة أبي غانم و جامع ابن بركة، خلصنا إلى أن الإباضية و إن لم يفردوا مصنفا خاصا بالفروق الفقهية و لا سفرا مستقلا في ذلك، لم يبسطوا القول في قواعده و أسسه، إلا أنهم عرفوا الكتابة في هذا الفن منذ عهدهم الأول كما تظهر ذلك الفصول التطبيقية في البحث، و هذا من خلال ما أودعوا في كتب الفروع من تفريقات دقيقة و تمييزات رشيقة. و الملاحظ من خلال فروق المدونة و الجامع أنها متركزة بشكل أكبر في قسم العبادات. كما أني من خلال هذا الاستقراء و التتبع لم أجد بين المصنفين منهجا متحدا في التفريق الفقهي، و ذلك للاختلاف في غرضهما من تأليف كتابيهما؛ بين من قصد بتصنيفه حفظ آثار العلماء من الاندثار فالتزم النقل الحرفي للأجوبة، و من سلك مسلك التأصيل و التحليل و المناقشة فلم يتقيد بذلك؛ و أضف إلى ذلك كون أبي غانم في بدايات عصر التدوين، بخلاف ابن بركة الموجود في عصر تمايزت فيه العلوم و تأسس معظمها. - إن الناظر في الاستدلالات الفرقية و الآليات المعتمدة في التفريق عند هذين العالمين يتبين له مدى رسوخ قدم علماء الإباضية في الفقه من أول أمرهم، كما أنه يقف على مدى توسعهم في الأخذ بالأدلة النصية و الاجتهادية، مما يجعل هذا المذهب مدرسة إسلامية أصيلة لازالت تحتاج إلى مزيد اعتناء و خدمة من الباحثين .
Keywords: Fiqh

السير الإباضية في بلاد المغرب الوسيط: مسارها ومشايخها - الزرويل, صالح; بوسعد, الطيب (مجلة مدارات تاريخية, 2022)
عالج الباحث في هذه الورقة البحثية مسار السير الإباضية، منذ ظهورها ببلاد المغرب، وأهم مشايخها الذين خلفوا كتبا تحمل عنوان السير والطبقات، وقد حاول تتبع تلك المدونات حسب المناطق الجغرافية والحواضر الكبرى التي كانت آهلة بأتباع المذهب الإباضي إلى وقت قريب، ذاكرا تراجم شخصية لكاتبيها وعناوين كتبهم إلى جانب نسخها المخطوطة ومحققيها، ومن النتائج المتوصل إليها باختصار هي استمرارية تلك السير زمانا ومكانا دون انقطاع، مع بعض الاختلافات البسيطة في المنهج، إلى جانب عددها المعتبر، المعروف منها والمفقود، ضف إلى ذلك تبيان دلالة كلمة السير عند الإباضية واختلافها في معناها لدى المؤرخين القدامى والمعاصرين. الكلمات الدالة: السير، بلاد المغرب، الإباضية، المشايخ، الطبقات In this paper , the researcher dealt with the path of Abadit ,since its emergence in the Maghreb. And the most important of its Sheikhs, who left books bearing biographies and classes. He tried to follow those codes according to the geographical regions and major metropolitan areas that were populated by following the Ibadi school of thought until recently. The personal biographies of its authors and titles of their books, as well as the manuscript copies and their editors are mentioned. One of the continuous results to it in short is the continuity of that march through time and time. Without interruption with some slight differences in the curriclum. besides their significant number;known and lost ones. Add to that clarificationof the meaning of the word biography of the Ibadis and its difference in its meaning among ancient and contemporary historians.

تجارة العاج في زنجبار ومناطق شرق أفريقيا بين النشاط العُماني والحماية البريطانية 1890- 1945 دراسة وثائقية - محروس, صلاح محمد (مجلة دراسات افريقية, 2022)

نشاطات ورسائل سليمان الباروني في العراق وعُمان 1929-1939 - عباس, علي حمزة; حسن, مهند حازم محمد (مجلة ابحاث كلية التربية الاساسية, 2022)

مواقف فقهاء عُمان من قضية عزل الإمام الصلت الخروصي: من اجتماع سعال حتى اجتماع الرستاق خلال الفترة (272-1034هـ/885-1624م) - الخاطرية, خلود بنت حمدان; الريامي, علي بن سعيد (مجلة الآداب, 2022)
Keywords: Fiqh

موقف المملكة العربية السعودية من الصراع بين الامامة والسلطنة في عمان 1955-1971 - علوش, تيسير جدوع (مجلة الجامعة العراقية, 2022)
Keywords: Relations – Oman – Arabie Saoudite

البحرية العمانية ودورها في تنمية التجارة العمانية الداخلية والخارجية 1741 – 1856 - الدليمي, دحام فرحان عبد الحمد; جامل, معد انور عبداللطيف (مجلة جامعة تكريت للعلوم الإنسانية, 2022)

القاضي محمد بن محبوب الرحيلي (ت:260هـ/873م) وإسهاماته في الحياة الادارية والعلمية في عُمان - الخاطرية, خلود بنت حمدان (مجلة آداب البصرة, 2022)

مظاهر الحياة الاجتماعية في عُمان من القرن الثالث الهجري الى نهاية القرن الثامن الهجري - محمد, نور باسم; شريمص, عبد الجبار محمود (مجلة جامعة الانبار للعلوم الانسانية, 2022)

البعثة العسكرية الامريكية لسلطنة عمان عام 1973 والموقف البريطاني منها في ضوء الوثائق اليريطانية - فاضل, علاء رزاق (جملة آداب الفراهيدي, 2022)

بريطانيا في الصراعات الداخلية العُمانية 1913-1932 - عباس, علي حمزة (مجلة أبحاث كلية التربية الأساسية, 2022)
Keywords: Vie politique – Oman – 1913-1932

من وثائق األرشيف العُماني رحلة القبطان همرتون من مسقط إلى زنجبار عام 1257ه/1841م-دراسة وتحقيق - الحاتمية, فاطمة بنت ناصر بن خلف; الطرونة, محمد سالم غثيان (مجلة أبجاث ميسان, 2022)
Keywords: Récits de voyage – Oman

مهام مجلس وزراء سلطنة عمان من خلال وثيقة أرشيفية تعود لعام 1344هــ / 1925م - الحراصي, حاتم بن حمود بن سعيد; الطراونة, محمد سالم (مجلة أبجاث ميسان, 2022)

الاوضاع السياسية في سلطنة عمان في القرن الثامن عشر - حميد, جنان نصر (مجلة الباحث, 2022)
Keywords: Vie politique – Oman – 18e siècle

موقف جريدة اتحاد الشعب من حركات التحرر العربي (الجزائر وسلطنة عُمان ) أنموذجا (1959-1960) - القيسي, سيف عدنان أرحيم; داود, مصطفى عباس (مجلة مداد الآداب, 2022)

Patrimonialisation de la mosquée littorale Sidi Jmour à Djerba, un monument, plusieurs vies - Tobji, Najoua (Al-Sabîl, 2022)
Située au Sud-Est de la Tunisie, l’île de Djerba était dotée depuis le moyen âge d’une chaine de mosquées littorales qui ceinturait ces côtes en vue d’assurer un rôle essentiellement défensif. La mosquée Sidi Jmour constitue un maillon important de cette ligne de défense avancée et représente ainsi un témoin architectural précieux qui nous renseigne sur un épisode tumultueux de l’histoire de l’île. Toutefois, suite aux mutations qu’a connues l’île au fil des siècles le monument a évolué en accueillant d’autres vocations. Dans cette étude, nous tenterons d’identifier et d’évaluer l’impact de ces changements de vocations sur les valeurs et les attributs de ce patrimoine religieux en voie de son inscription sur la liste du patrimoine mondial de l’Unesco. Afin de parvenir à cet objectif, nous préciserons les moments les plus marquants de la vie de la mosquée Sidi Jmour afin de suivre la genèse et l’évolution de ce monument palimpseste. Nous évaluerons par la suite l’impact des changements de vocation sur les valeurs et attributs de ce patrimoine religieux et sur ses modes de gestion. Pour ce faire, nous nous sommes fondés sur les sources historiques écrites, les études architecturales et archéologiques ainsi que sur les relevés architecturaux et les photos d’archives. Les résultats de l’étude du cas de Sidi Jmour montrent que la fonction joue un rôle fondamental dans la survie, le maintien et la sauvegarde des monuments. Toutefois, en l’absence d’encadrement institutionnel et de stratégie de reconversion, les dérapages induits par l’abus d’utilisation risquent d’entraîner la perte totale et définitive de l’authenticité des monuments. La patrimonialisation pourrait, dans ce cas, constituer la solution la plus adéquate pour étayer l’effort des autorités responsables et accompagner l’évolution des monuments et leur reconversion dans le respect de leurs spécificités architecturales et culturelles. Le rôle de la société civile s’avère, ainsi, fondamental afin d’instaurer une stratégie de sauvegarde et de mise en valeur du patrimoine fondée sur l’approche participative.
Keywords: Architecture – Djerba; Monuments – Djerba; Sidi Jmur; mosquée (El Groo; Djerba)

Thinking about Muslim Sects and Schools - Gaiser, Adam R. (Fifteen Eighty Four: Academic perspectives from Cambridge University Press, 2022)
The Muslim community, known as the umma, is meant to be united. The Qur’an, in chapter 29, verse 92, states that ““Indeed, this your umma is one umma, and I am your Lord; so worship Me.” Yet Muslims, just like Jews, Christians and other religious groups, divided into various communal divisions quite early in their history.

The legal reasoning of Nūr al-Dīn al-Sālimī (1868-1914): ordering what cannot be done is not possible - Zdanowski, Jerzy (AFM Publishing House, 2022)

İbâzıyye Mezhebinin Teşekkülü, Sistematiği ve Farklılaşmalar - Ölmez, Sadi (Eskiyeni, 2022)
Teşekkülü hicrî birinci asra denk gelen İbâzıyye mezhebi, fıkhî bir mezhep vasfından ziyade daha çok siyasi bir fırka olarak şöhret bulmuştur. Böyle bir anlaşılmaya maruz kalmasının altında selef olarak gördükleri bazı şahsiyetlerin Hâricîlerle iltisakları yatmaktadır. Bu durum İbâzıyye’nin fıkhî bir mezhep olarak bilinmesinin önüne geçmiştir. Bundan ötürü İbâzıyye daha çok mezhepler tarihi ve itikâdî görüşlerinden ötürü kelâm alanında çalışılmıştır. Bu yönelim mezhebin fıkhî yönünün ihmal edilmesine sebep olmuştur. Oysaki İbâzıyye zengin fıkhî müktesebatı ve literatürüyle müstakil bir ameli mezheptir. Hatta İbâzîlere göre kendi mezhepleri, kronolojik olarak teşekkül eden ilk fikhî mezheptir. İbâzıyye mezhebi Abdullah b. İbâz’a nispet olunmakla birlikte İbâzîler, Câbir b. Zeyd’i müessis olarak kabul ederler. İbâzîler hicrî üçüncü asrın sonralarına kadar kendilerini İbâzî olarak isimlendirmekten kaçınmışlardır. Çünkü onlar fıkhî mezheplerin, kurucularına nispet edilmesini gerektiğini, mezhep kurucularının da Câbir b. Zeyd olduğunu söylerler. Mezheplerinin Abdullah b. İbâz’a nispet edilmesinin siyasi saikler nedeniyle olduğunu ısrarla vurgularlar. Bundan ötürü İbâzîler mezheplerinin müessisi olarak Câbir b. Zeyd’i görürler. Câbir, tâbiîn alimlerinden olup Basra müftüsü olmasıyla da şöhret bulmuştur. İbâzıyye mezhebinin Câbir’den sonraki en etkili şahsiyeti olarak kabul edilen Ebû Ubeyde Muslim b. Ebî Kerime mezhebin teşekkülünde ve sistemleşmesinde son derece ehemmiyetli bir yere sahiptir. Ebû Ubeyde gerek Emevîler gerekse de Abbâsîler döneminde İbâzîlere yönelik baskılara rağmen mezhebi bir arada tutarak Basra dışına özellikle de Kuzey Afrika’da yayılmasını sağlamıştır. İbâzıyye mezhebinin hicrî ikinci asrın ikinci çeyreğinden itibaren farklı coğrafyalara taşınması bu mezhebin sistemleşmesi bakımından önemli bir süreç olmuştur. Ayrıca İbâzıyye mezhebinin Basra dışındaki bölgelere yayılması İbâzî fıkıhla ilgili tedvinlerin artmasını sağlamıştır. İbâzî fıkhının günümüze ulaşmış kıymetli eserlerinin başında gelen Ebû Gānim el-Horâsânî’nin el-Müdevvenetü’l-Kübrâ’sı bu dönemin mahsulüdür. İbâzıyye mezhebi sünnî mezheplerin fıkhî meselelerde başvurdukları istinbât ve istidlâl yönteminden farklı bir yöntem kullanmamıştır. Kur’ân, Sünnet, icmâ, kıyas ve diğer istidlâl yöntemleri İbâzî fakihlerce de başvurulan yöntemlerdir. Dolayısıyla İbâzîlerin kullanmış olduğu usûl yöntemlerinin diğer mezheplerin usûl yöntemiyle tam olarak aynı olmasa da birbirine çok yakın olduğunu söylemek mümkündür. İbâzîlerin istidlâlî deliller kısmında diğer mezheplerden farklılaşması ilham konusunda olmuştur. İbâzîlerde tartışmalı olmakla birlikte ilham istidlâlî delillerden biri olarak zikredilmiştir. Bu çalışmada İbâzıyye mezhebinin Hâricîlerle bağlantısı, mezhebin ortaya çıkışı, fıkhı ve usûl anlayışı ele alınmıştır.
Number: 47

Tevhid Esası Ekseninde İbâdiyye-Mu‘tezile Etkileşimi - Yoldaş, Mehmet Hanifi; Kubat, Mehmet (Journal of the Near East University Islamic Research Center, 2022)

Hâricîliğin Ortaya Çıkışı ve İbâzî Anlayışında Hâricîlik Yorumu - Ölmez, Sadi (Van İlahiyat Dergisi, 2022)
Her ne kadar Hz. Peygamber döneminde yaşanan bir ganimet taksimi sonucunda Hâricî anlayışının ortaya çıktığı iddia edilmişse de bir fırka olarak zuhur etmeleri Sıffin savaşında olmuştur. Hz. Ali ve Muâviye arasındaki tahkim meselesinde ‘‘Hüküm ancak Allâh’ındır’’ şiarıyla şöhret kazanan bu oluşum Muaviye’nin Hz. Ali’ye karşı isyanını geride bırakacak kadar ön plana çıkmıştır. Öyle ki Sıffin savaşı denilince araştırmacılar Muâviye ve yaptıklarından çok Hâricîler ve yaptıkları üzerinde durmaktadırlar. Bunun birçok sebebi olmakla birlikte, Hâricîlik ve Hâricîlerin genellikle Sünnî kaynaklar çerçevesinde değerlendirilmesidir. Hâricilik ve Hâricîler konusunda objektif olabilmenin yolu bizzat Hâricîlerin ya da Hâricîlerle bağlantılı fırkaların kaynaklarına müracaat etmek olduğunu söyleyebiliriz. Hâricîler, itikadi veya fıkhi bir mezhep olarak sistemleşen bir oluşum değildir. Ancak Hz. Ali’den ayrılıp Harûrâ denilen yerde toplanan gurup arasında daha sonraları İbâzî adıyla bilinecek olan mezhebin öncüleri de yer aldığı için, İbâzî mezhebi Hâricî bir fırka olarak bilinmektedir. Hicrî 64 senesinde Harûrâ ehli kendi arasında fırkalara ayrılmıştır. Bu ayrışmanın temel sebebi, özellikle Nâfi’ b. Ezrâk’ın şiddeti meşru görüp kendileri gibi düşünmeyen diğer Müslümanları tekfir etmesi, kanlarını, mallarını ve ırzlarını helal saymasıdır. Bu ayrışmadan sonra Hâricîler Ezârikâ, Sufriyye, Necdiyye/Necedât ve İbâziler şeklindeki isimlendirmelerle anılmışlardır. İbâzîler radikal tutumlarından ötürü bu fırkalardan beri olduğunu özellikle belirtmiştir. Abdullah b. İbâz ve Emevî halifesi Abdulmelik b. Mervân arasında geçen yazışmalarda bu durum özellikle vurgulanmıştır. Ancak Hâricîlik konusu ele alınırken bu ayrışmanın niçin olduğu göz ardı edilmiş olup, ılımlı bir anlayışa sahip olan İbâziler, şiddet ve tekfir yanlısı olan diğer Hâricî fırkalarla aynı kategoride değerlendirilmiştir. Yine söz konusu yazışmalarda yer aldığı üzere İbâzîler böyle bir genellemeye şiddetle karşı çıkmış ve kendilerinin diğer Hâricî fırkalardan ayrı bir şekilde değerlendirilmeleri gerektiğini belirtmişlerdir. Çalışmamızda İbâzîlerin bu tutumuna ve gerekçelerine yer verilmiş olup, gerek kendi kaynakları gerekse de Sünnî kaynaklar referans gösterilerek izah edilmeye çalışılmıştır. Diğer önemli bir husus ise İbâzîler Hâricî olarak isimlendirilmek istemezler. Onlar kendilerini Şurât, Ehlu’l-İstikâme, Hâruriye ve Vehbiye olarak isimlendirilmeyi daha uygun görmüşlerdir. Günümüze kadar ulaşabilmeyi başaran İbâzî mezhebi Hâriciler ve Hâricîlik konusunda özgün görüşlere sahip olmakla birlikte, kendilerini Hâricî olarak görüp görmedikleri konusunda da fikir beyan etmişlerdir. Ayrıca Hâricîliğe yaklaşımları ve tanımlamaları Sünnî kaynaklarda zikredilenle farklılık arz etmektedir. Hâricîlerle olan bu bağlantıları ve günümüze kadar ulaşmış olmalarından ötürü objektiflik açısından Hâricilik konusunda İbâzî kaynaklara müracaat etmek bir gerekliliktir. Ancak İbâzîlerin daha çok Sünnî kaynaklara bağlı kalınarak tanıtıldığını söyleyebiliriz. Böyle bir yaklaşım ise İbâzîlerin doğru anlaşılmamasının yanı sıra onların başta Ezârikâ olmak üzere diğer Hâricî fırkalarıyla bir tutulmasına da neden teşkil edebilir. Bu çalışmamızda İbâzilerin, Hâricî ve Hâricilik konusuna yaklaşımları ve kendilerini Hâricî bir fırka olarak görüp görmediklerini bizzat onların kaynaklarını temel alarak ele almaya çalışacağız.
Number: 17

Hâricî ve İbâzî Literatüre Dair Bir Kavram Tespit Denemesi - Ağirkaya, Güven (Eskiyeni, 2022)
İslam düşünce tarihinin ilk oluşumlarından biri Hâricîlerdir. Onlar ilk olarak Sıffin’de tahkim hadisesi üzerine Hz. Ali’den ayrılmış daha sonra ise kendi aralarında ihtilaf ederek bölünmüşlerdir. Onların kimi kılıç kalkan taraftarı olup kendilerinden olmayanlara karşı son derece sert ve katı bir yolu benimserken, kimi de daha mutedil bir yaklaşım içerisinde olmuştur. Özellikle marjinal bir grup olarak maruf olmuş Hâricîlerin mutedil kanadını temsil eden İbâzîler varlıklarını günümüze kadar sürdürürken, mutedil olmayanlar zamanla tarihe karışmışlardır. İbâzîlik tarih boyunca Hâricîliğin gölgesinde azınlıkta bir mezhep olarak kalmakla beraber kendilerine has dinî ve entelektüel bir literatür oluşturmayı başarmış bir oluşumdur. Tarihi süreçte Hâricî-İbâzî bağlamında günümüze ulaşmış literatürün hemen tamamı İbâzîlere aittir. Ülkemizde özellikle son dönemlerde İbâzî literatüre dönük akademik bir ilgi söz konusudur. Bir literatürün incelenmesinde en öncelikli hususlardan biri ilgili alandaki terminolojidir. Zira lafızlar tutarlı bir sisteme sahip düşünce teşekküllerinin anlam örgüsüne girdiklerinde ilk vaz edildikleri anlamlardan uzaklaşarak farklı işlevsellikler kazanırlar. Müşterek kavramların düşünce ekolleri tarafından kendi entelektüel birikimlerinde farklı anlamlarda kullanılması ise mezkûr durumu daha da ehemmiyetli hale getirir. Binâenaleyh araştırma konusu yapılmış bir literatürün doğru mütalaa edilmesi ancak terminolojisinin kendi düşünce örgüsünde tanımlanıp anlaşılmasıyla mümkündür. Bu bağlamda İbâzîler kendi literatürlerini aynı zamanda kendilerine has bir terminolojiyle oluşturmuşlardır. Bu araştırmada, İbâzîlikle ilgili okumalarda sıkça tesadüf edilecek kavramların derlenip mümkün olduğunca kendi kaynakları doğrultusunda medlullerinin tespit edilmesi hedeflenmiştir. Burada özellikle araştırma konusu yapılan, mezhep müellifleri tarafından İbâzîlere has anlamlarla kullanılan kavramlardır. Çalışma, isminden de anlaşıldığı üzere, İbâzîlere ait bütün kavramları tespit etme gayesi gütmemiştir. Özellikle İbâzîlere has kullanım ve muhtevaları olan kavramların tespitine ağırlık verilmiştir. Tespit edilen kavramlar, Türkçe telaffuz ve kullanımları dikkate alınarak alfabetik sıraya konulmuştur. Ancak özellikle beraber kullanımı yaygınlaşmış ve muhtevaları birbiriyle ilişkili bazı kavramlar bir arada verilmiştir. Çalışma yürütülürken ulaşılan İbâzî eser ve sözlükler tarama yöntemi kullanılarak incelenmiş ve gerekli görülen yerlerde mezhep dışı eserlere başvurularak karşılaştırmalar yapılmıştır. Genel itibariyle iki ana bölümden müteşekkil olan çalışmanın giriş ve birinci bölümünde İbâzîlik ve ıstılah kavramı hakkında kısa bilgiler verilmiş; ikinci bölümde ise tespit edilen kavramlar üç gruba ayrılmış olarak maddeler halinde serdedilmiştir.
Number: 47
Keywords: Kharijisme

İbâzî Tefsirlerde İ'câzü'l-Kur'an - Altun, Fatih; Atmaca, Gökhan (Tasavvur / Tekirdağ İlahiyat Dergisi, 2022)
İslam alimleri; Kur’an’ın evrenselliğini, erişilmez üstünlüğünü ve ilahî kelam olduğunu ifade eden i‘câzü’l-Kur’an üzerinde önemle durmuşlar, yetiştikleri ortam ve ilmi birikimleriyle Kur’an’ın i‘câzını anlamaya çalışmışlardır. Bu konuda, İslam tarihinin erken döneminde teşekkül eden ve günümüzde varlığını devam ettiren İbâziyye mezhebine mensup müfessirler de çaba göstermişlerdir. Bu makalede İbâzî müfessirlerin i‘câzü’l-Kur’an’a yaklaşımlarının incelenmesi hedeflenmiştir. Bununla birlikte İbâzî tefsirlerde ve bazı Sünnî kaynaklarda i‘câz, mucize ve tehaddînin neler olduğu tespit edilmeye çalışılmış ve bu iki ekolün görüşlerinin kıyaslanması amaçlanmıştır. Araştırmanın sonucunda İbâzî müfessirlerin Kur’an’ın metin ve muhtevasıyla tehaddîde bulunduğu, benzerinin meydana getirilemeyeceği ve kıyamete kadar geçerli bir mûcize olduğu hususunda aynı kanaati taşıdıkları anlaşılmıştır. Ayrıca İbâzî müfessirlerle Sünnî âlimlerin i‘câzü’l-Kur’an’a bakış açılarının benzer olduğu görülmüştür. Bunun istisnası, İbâzî müfessirlerden Ettafeyyiş’in tehaddî ile halku’l-Kur’an arasında kurduğu ilişkidir. İbâzî ve Sünnî alimlerin görüşlerindeki benzerliğin çokluğu, i‘câzü’l-Kur’an’a tenzihi bir anlayışla yaklaşmaları ve tefsir kaynaklarının aynı olmasıyla; görüşlerindeki farklılığın sebebi ise mezhebi düşüncenin etkisiyle açıklanabilir.
Number: 1
Keywords: Coran – Commentaires

قراءة في مخطوطة: أجوبة للشيخ الأجهوري وغيره عن سؤال وقع بشأن الفرق الإباضية. (الجزء الثاني) - تغلات, زهير (دراسات في الإنسانيات, 2022)

Le « Gazoul », l'or vert des Djerbiens en Tunisie - Pouvoir antioxidant et antimicrobien de l'Allium roseum var. odoratissimum - Touihri, Barakati imen (Edition universitaire européenne, 2022)
Keywords: Botanique – Djerba

مسكة المساك الموقع الأسماء في شرك الاشتراك - بن رزيق, حميد بن محمد (مكتبة مسقط, 2022)

شذرات من أصول الفقه - البراشدي, مبارك بن عبد الله (مكتبة بذور التمير, 2022)
Keywords: Fiqh

الخزانة : ‏قرأه فهرسة في مخطوطات خزنة الشيخ العلامة سالم بن حمود السيابي - المحرزي, سند بن حمد (مكتبة الجيل الواعد, 2022)
Volume 2 manquant
Keywords: Bibliothèques – Oman

اللغة الأمازيغية الابدال ‏النحو ‏الأمازيغي - يخلف, عيسى (‏المركز الليبي للدراسات الأمازيغية, 2022)
Keywords: Linguistique

تعرف على الألحاد - البوسعيدي, سالم بن سعيد (روئ, 2022)

الحياة العلمية في عمان ‏منذ بداية القرن الأول حتى نهاية القرن الرابع الهجري - الناجم, نورة سعد (‏ملامح للنشر وتوزيع, 2022)

منهاج السلامة في أحكام الامامة - الحمسعيدي, سالم بن عبد الله (‏مؤسسة اللبان للنشر, 2022)

الأمير الثائر: ‏خالد بن ‏برغش - الرحبي, فهد (مكتبة بذور التمير, 2022)

شرح كتاب أصول الفقه من جوهر النظام - السالمي, عبد الله بن حميد (غاية المراد, 2022)
Keywords: Fiqh

الاهتمام بجمع شمل الامة - الراشدي, مبارك بن عبد الله (مكتبة بذور التمير, 2022)

الجذور التاريخية ‏لبلاد المغرب جدلية السلطة والمجتمع و المجال (خلال القرنين الأول والثاني الهجري/ السابع والثامن الميلادي) - حسن, محمد (مجمع الأطرش, 2022)
Keywords: Afrique du Nord – Histoire

الخوارج: ‏بين المشرق والمغرب (37هـ/657م - 543هـ/1148م). ‏وصولهم - طوائفهم - أفكارهم - زعماؤهم - حروبهم - إماراتهم - سلامة, عبد الحميد (مجمع الأطرش, 2022)
Keywords: Kharijisme

‏حديث لبعض ما حدث في حياة السلف ودليل الخلف - الزيدي, ناصر بن محمد (مكتبة الجيل الواعد, 2022)

قصة الخيل العربية التي أهداها السيد سعيد سلطان عمان إل السلطات البريطانية دراسة وثائقية - الندوي, صاحب عالم الاعظمي (‏رسالة الجواد العربي, 2022)

Le pouvoir des listes: canoniser le passé et fixer la généalogie de la bonne dissidence. L’exemple du regard ibadite sur le kharijisme - Baptiste, Enki (2022)

Re-Evaluating the Notion of Isrâ and Mi’râj in Ibadi Tradition: With Special References to the Modern Sirah Readings - Albayrak, Ismail; Shueili, Sulaiman bin Ali bin Amir al- (Religions, 2022)
The notion of mi’râj (the heavenly journey of Prophet Muhammad) is an important non-homogenic topic, although it is not often handled in Ibadi intellectual, sīrah (biography of the Prophet) and exegetical traditions. In this article, we analyse the treatment of the subject chronologically in the Ibadi tradition. We discuss the Ibadis’ main concerns on the subject, how they differ, what inferences they make from the related verses, sīrah, hadith and exegetical (tafsir) reports, and most importantly whether they accept the notion of mi’râj. This article analyses the notion of isrâ because of its close relationship to mi’râj. In summary, there are variations on the issue of mi’râj among the North African and Omani Ibadis. Even more interesting is the existence of significant nuances among the Omani Ibadis. In short, while all North African Ibadis accept mi’raj as an event, it is observed that some Omani Ibadis accept it, while others sometimes reject it for religious and sometimes rational grounds.
Keywords: Coran – Commentaires

La mémoire à travers l’histoire le puzzle de la mémoire en naufrage chez Slimane Benaissa : La triade de « Babour Ghraq» - Bourouis, Khalid; Semoum, Khireddine (Université Kasdi Merbah, 2022)
Le présent travail de recherche s’intitule la mémoire à travers l’Histoire : le puzzle de la mémoire en naufrage chez Slimane Baissa : la triade de « Babour Ghraq» vise à étudier comment Slimane BENAISSA, à partir de la tirade «Nâalbou li mayhebnach », est parvenu à construire et à transmettre la mémoire plurielle des algériens. Ce travail comporte deux chapitres, dans le premier nous abordons la représentation de l’auteur et ses œuvres, et dans le deuxième chapitre nous étudions les procédés et les stratégies textuelles et théâtrales de la construction et de la transmission de la mémoire que renferme cette tirade.
Keywords: Littérature – Mzab

Islamic Sects in Tunisian Province and its Relationship with the Ottoman Authority during the 16th Century =المذاهب الإسلامية في الإيالة التونسية وعلاقتها بالسلطة العثمانية خلال القرن 16م - Şeri̇foğlu, Metin (Çukurova Üniversitesi İlahiyat Fakültesi Dergisi (ÇÜİFD), 2022)
يتناول هذا البحث مسألة المذاهب الإسلامية في البلاد التونسية وعلاقتها بالدولة العثمانية خلال القرن 16م. ذلك أن المسألة المذهبية عريقة في البلاد التونسية. حيث عرفت تونس عبر تاريخها الإسلامي العديد من المذاهب الإسلامية، منها السنة والشيعة والخوارج. وقد ارتبط انتشار هذه المذاهب بالتطورات السياسية التي شهدتها تونس من الفتح الإسلامي إلى حدود العهد العثماني. كما ظلت في تونس ثلاثة مذاهب إلى يومنا هذا، وهي المالكية والحنفية والإباضية. أما بقية المذاهب فلم يعد لها وجود يذكر. وقد بقي المذهب المالكي أكثر انتشارا في تونس وفي شمال إفريقيا. وعندما دخلت تونس تحت الحكم العثماني عاد المذهب الحنفي إلى الانتشار من جديد، وأصبح المذهب الرسمي للدولة. وقد انتهج العثمانيون سياسة متسامحة مع كل المذاهب في تونس. وسنقوم في هذا البحث بتحليل ثلاثة مباحث هي: أولا أهم المذاهب الإسلامية التي وجدت في تونس قبل الدخول العثماني، ثانيا الدخول العثماني إلى تونس وانعكاساته على الخارطة المذهبية فيها، ثالثا المؤسسات التي أقامها العثمانيون في تونس ودور المذاهب الدينية فيها , This research deals with the issue of Islamic sects in Tunisia and their relationship with the Ottoman Empire during the 16th century. Throughout its Islamic history, Tunisia has known many Islamic sects, including Sunnis, Shiites, and Kharijites. The spread of these sects was linked to the political developments that Tunisia witnessed from the Islamic conquest to the borders of the Ottoman era. There have remained in Tunisia three schools of thought to this day, namely Malikiyya, Hanafiyya and Ibadiyya. The rest of the sects no longer exist in Tunisia. On the other hand, the Maliki school of thought remained more prevalent in Tunisia and in the North African region. And when Tunisia entered under the Ottoman rule, the Hanafi school of thought returned to spread again, and it became the official sect of the state. The Ottomans pursued a tolerant policy with all sects in Tunisia. From this point of view, we will address our research in three sections: First, the most important Islamic sects of thought that existed in Tunisia before the Ottoman entry, second, the Ottoman entry into Tunisia and its repercussions on the sectarian map in it, and thirdly, the institutions established by the Ottomans in Tunisia and the role of religious sects in it. , Bu araştırma, Tunus'taki İslam mezhepleri konusunu ve 16. yüzyılda Osmanlı İmparatorluğu ile olan ilişkilerini ele almaktadır. Nitekim Tunus, İslam tarihi boyunca Sünnî, Şîî ve Hâricî dahil olmak üzere birçok İslam mezhebini tanımıştır. Bu mezheplerin yaygınlaşması, İslam fetihlerinden Osmanlı döneminin sınırlarına kadar Tunus'un tanık olduğu siyasi gelişmelere bağlanmıştır. Tunus'ta bugüne kadar Mâlikî, Hanefî ve İbâdî olmak üzere üç İslam mezhebi kaldı. Tunus’taki diğer mezhepler ise artık kalmamıştır. Öte yandan Mâlikî mezhebi, Tunus ve Kuzey Afrika'da en yaygın mezhep olmaya devam etti. Tunus, Osmanlı hakimiyetine girdiğinde, Hanefî mezhebi yeniden yayılmaya başladı ve devletin resmi mezhebi haline gelmiştir. Osmanlılar Tunus'ta tüm mezheplere karşı hoşgörülü bir politika izlemiştir. Bu bağlamda, bu araştırmayı üç bölümde ele alacağız: Birincisi, Osmanlı'ya girmeden önce Tunus'ta var olan en önemli İslam mezhepleri. İkincisi, Osmanlı'nın Tunus'a girişi ve bunun mezhep haritasındaki yansıması. Üçüncüsü ise, Osmanlıların Tunus'ta kurdukları kurumlarda İslam mezheplerinin rolü.

Reasons for the tendency of North African barbarians to the Kharijite political and social approach 1 - کریمیان راوندی, سعید; انصاری, مهدی (Political Sociology of Iran, 2022)
One of the most influential sects in the early history of Islam is the Kharijites. They suffered severe blows during the Umayyad period and, as their power and influence in the central lands of the caliphate diminished, they moved to more distant lands, such as North Africa.Groups of North Africans embraced the sometimes extremist political ideas of the Kharijites and succeeded in forming government in parts of the region. Examining the process by which this situation took place and the reasons for accepting Kharijite political and social ideas, it was concluded that the Kharijite anti-authoritarian ideas and beliefs were in harmony with the ideals and motives of the Barbarians, and mistreated the Barbarians who prepared them. In order to accept the teachings based on justice and freedom, the uprising against the oppression of the Umayyad governors paved the way for the acceptance of the Kharijite invitation by the Berbers and the development of foreign socio-political ideas in North Africa.
Keywords: Kharijisme

شیوه های نفوذ اندیشه‌های سیاسی-فرهنگی خوار به شمال آفریقا = Ways of infiltrating Kharijite political-cultural ideas into North Africa - کریمیان راوندی, سعید; انصاری, مهدی; شرفی, محبوبه (ماهنامه جامعه شناسی سیاسی ایران, 2022)
The Kharijites were the most important political-military opponents of the Umayyads, but despite their high military capability and good governing ideology, they could not find their place in the eastern lands of the Caliphate. The barbarians succeeded in gaining popularity among a significant section of the North African barbarians and disseminating their ideas. The results of this study, which is a descriptive way to answer the question of what were the ways of influencing Kharijite ideas politically and culturally in North Africa and the development of foreign thought in this region, show that Kharijites use the slogan of justice and equality that Their main principle and distinction was with other political groups of that time, as well as the use of cultural tools such as the Arabic language, organizations called "Al-Azaba" and the theories of their perpetrators and cultural claimants, as well as political methods such as invitations and active invitation centers in major cities. Use covert networks to promote their ideas and thus influence and attract fans in North Africa. In addition, taking advantage of the dissatisfaction of the original inhabitants of these areas due to the oppression of the Umayyad governors, was effective in facilitating the success of the Kharijites in their influence in North Africa

السياسة والحكم - الأغبري, إسماعيل بن صالح (مكتبة الضامري, 2022)

فقه التركات ‏في الإسلام - الراشدي, مبارك بن عبد الله; بوزكري, خميس ساسي (مكتبة بذور التمير, 2022)
Keywords: Fiqh

الإمبراطورية العمانية ‏في شرق أفريقيا شروق وغروب دراسة ‏وثائقية - محروس, صلاح محمد (روئ, 2022)

المفاهيم اللغوية عند الأصوليين الإباضيين: ‏كتاب طلعت الشمس انمؤذجا (دراسة وصفية تحليلية) - السعدي, عبد الله بن مبارك (النادي الثقافي, 2022)

المنهج في تذكرة الزواج - الصقري, إبراهيم بن سليمان (مكتبة الجيل الواعد, 2022)
Keywords: Fiqh – mariage

‏وثائق أوقاف السيد حمود بن أحمد البوسعيدي على بيتي الرباط في مكة المشرفة - القدحات, محمد بن عبد الله (‏مكتبة نذور التميز, 2022)
Keywords: Waqf (fondations) – La Mecque

تجربة تدريس اللغة الامازيغية ‏في ليبيا - أبو زخار, فتحي سالم (اتحاد الناشرين ليبيا, 2022)
Keywords: Enseignement – Libye

From text to architecture: the evolution of the Musalla of ʿAmmi Saʿīd in 13th/19th century Mzāb - Kwan, Elisabeth (2022)
Keywords: Archéologie – Mzab

The influence of Ibāḍī imamate on the political integration and economic development in Oman during Julanda dynasty (7th 8th centuries AD)" - Pour, Ali Bahrani (2022)
Keywords: Vie politique – Oman – 749-751

Ibāḍiyya: Sunnis or Shiites or between? (on the 7th/9th c. conflicts) - Qorbanyar, Hadi (2022)

Masālik al-Din in the historical Progress of Imamate: a Study on Ibāḍiya in the First three centuries AH - Shabeer, Mohammad (2022)

Al-Julandā b. Masʿūd: an Ibāḍī Imām, between History and Memory - Baptiste, Enki (2022)
Keywords: Vie politique – Oman – 749-751

Āl al-Raḥīl and their political and ideological role in Oman in the 2nd-4th Century AH / 8th-10th Century AD - Nabhani, Badriya al- (2022)

On Studying the early historical sources: The Epistle of Khalf b. Ziyad al-Bahrani - Salimi, Abdulrahman al- (2022)

The Society of Missionaries of Africa and their Encounter with the Ibadi Community of the Mzab Valley, Algeria (in light of their diaries) - Meghnine, Khaled (2022)

Maghribi Scholars and the shape of the Ibāḍi Sect: Texts and Contexts - Boufrikha, Oussama (2022)

Thoughts on the stringency of the vision of tolerance within Ibadi Oman (Formation and development of the narrative of tolerance in the Ibāḍiyya in Oman since the Nahda period) - Weber, Gregor (2022)
Keywords: Tolérance religieuse – Oman

The Nukkari doctrine through ar-Risala al-Ḥuǧǧa (2nd /9th c.) - Bahmani, Salah (2022)
Keywords: Nukkarisme

Origins of the Ibadiyya - competing narratives of Ibadi Origins - Gaiser, Adam R. (2022)
Keywords: Historiographie – Ibadisme

On the influence of early "imported" Ibāḍi books on Djerbian lifestyle and architecture (with focus on 'houses of worship' / mosques and Ibāḍīs’ way of worship) - Ben Yahiaten, Gacem (2022)
Keywords: Architecture – Djerba

صيانة وحفظ التراث الثقافي المادي: إشكاليات الترجمة - الخروصي, خالد بن سليمان (2022)

ترجمة وثائق الوجود البرتغالي في منطقة أرخبيل الملايو؛ قلعة ملقا: (1511-1641م) - أحمد, هدى يعقوب (2022)

جهود العمانيين في ترجمة موسوعة الوثائق البرتغالية - علي, محمود محمد (2022)

الترجمة البريطانية للنصوص العمانية خلال القرن (19م)؛ جسور للتعارف أم أداة للهيمنة؟ - السعدي, ناصر بن سيف (2022)

أراجيز أحمد بن ماجد السعدي في اللغة الروسية - الهاشمي, سعيد بن محمد (2022)

ترجمة إنتاجات العالم العماني ودورها الحضاري (إنتاجات الشيخ أحمد الخليلي أنموذجا) - البوسعيدي, أحمد بن سعيد (2022)

الشيخ المترجم سعيد بن عبد الله بن سيف الحاتمي؛ حياته وآثاره في التأليف والترجمة - الحوقاني, خليل بن محمد بن راشد (2022)
Keywords: Biographies – Oman

الشيخ المترجم عيسى بن سالم الرواحي؛ وآثاره في التأليف والترجمة - الرواحي, محمد بن عيسى (2022)

أثر السواحلية في تآليف العمانيين في المهجر الأفريقي؛ قراءة في مخطوط كنوز الأسرار في علم الأشجار والأحجار - العيسري, محمد بن عامر (2022)

جواب مسائل النصارى لابن أبي نبهان؛ رحلتي في البحث عن السائل وعناية المستشرقين بالجواب - الخروصي, أحمد بن سالم (2022)

ما وصلنا من كتاب: مبتدأ الأسفار في بيان نبذة يسيرة من لغة أهل زنِجبار بالمشهور من اللغة العربية - الرمحي, أحمد بن محمد (2022)

المخطوطات غير العربية المحفوظة في الخزائن العمانية (دراسة إحصائية تحليلية) - السعدي, فهد بن علي (2022)
Keywords: Bibliothèques – Oman

لدخيل في معجم المصطلحات البحرية بسلطنة عمان والخليج العربي - الفارسي, علي بن حمد (2022)

العلاقات التاريخية العمانية الصينية؛ دراسة تحليلية في نصوص الحوليات الصينية - الهادي, حبيب بن مرهون (2022)

العوامل التي ساعدت على تطور الترجمة في عمان(1804–1856م) - الشعيلي, محمد بن حمد (2022)

ترجمة كتاب «مغامر عماني في أدغال أفريقيا»(تجربة ذاتية) - المحروقي, محمد بن ناصر (2022)

الترجمة في سلطنة عمان بين الماضي والحاضر - المعني, مسلم بن علي (2022)

تجربة الترجمة الآلية للغة العربية - خضر, محمد زكي (2022)

حركة الترجمة في أذربيجان (عرض تحارب وتقويم) - مصطفاييف, إيلنور (2022)

تساؤلات في ترجمة التراث العماني - الحجري, هلال بن سعيد (2022)

رسالة التقارب بين الشعوب من خلال الترجمة - عبدول, داتؤ محمود (2022)

دور الترجمة في التواصل بين الثقافات - عناية, عز الدين (2022)

دور المستشرقين في ترجمة وطباعة التراث العماني - ضيائي, علي أكبر (2022)

حاجتن الترجمة تراثنا في عصر التعددية والعولمة - المعولي, زياد بن طالب (2022)

الفلاحة و الصيد البحري في جزيرة جربة (1918-1939) من خلال محاضر جلسات المجلس البلدي - النجار, حسن (المجلة الجزائرية للبحوث والدراسات التاريخية المتوسطية, 2022)
يندرج هذا البحث ضمن مجال الجغرافية التاريخية ذات البعد المحلي، و هو من المجالات الهامة في الدراسات التاريخية المعاصرة المهتمة بمنطقة حوض البحر الأبيض المتوسط. كان الإقتصاد الجربي في فترة ما بين الحربين يعتمد بالأساس على الفلاحة و الصيد البحري. و قد ساهم هذا القطاع في تحقيق الإكتفاء الغذائي الذاتي لسكان جزيرة جربة، رغم ارتباط الفلاحة الشديد بالمعدل السنوي لنزول الأمطار في الجزيرة. و قد أمكن لنا من خلال المعطيات المتوفرة حول الفلاحة و الصيد البحري من معرفة أبرز خصائص الإقتصاد الجربي في تلك الفترة و ذلك من خلال اعتماد منهج تحليلي للمعطيات التي توفرت لنا سواء في الأرشيف الوطني أو في أرشيف بلدية جربة، أو كذلك المستقاة من بعض المصادر و المراجع. و قد توصلنا في هذا البحث إلى معرفة أبرز خصائص الفلاحة و الصيد البحري في جزيرة جربة. حيث تميزت الفلاحة الجربية بسيطرة زراعات الحبوب التي كانت تعتمد بالأساس على مياه الأمطار، كالقمح و الشعير. أما الفلاحة السقوية فكانت تعتمد على مياه الأبار المنتشرة في المناطق العذبة للجزيرة، و التي كانت بها كل أنواع الأشجار المثمرة خاصة البرتقال و التفاح الجربي. أما بالنسبة للصيد البحري، فقد نشط الأوروبيون في استخراج الإسفنج الأبيض المتوفر بسواحل الجزيرة و الذي كان يعتمد على وسائل متطورة. أما الصيادون الجرابة و بحكم إمكانياتهم المتواضعة فكانوا يكتفون بصيد الإسفنج الأسود القريب من السواحل. كما ساهم صيد السمك في امتصاص البطالة و انقاذ الجزيرة من المجاعات في مواسم الجفاف.
Keywords: Pêche – Djerba

سكان جزيرة جربة و أنشطتهم الحرفية (1918-1939) - النجار, حسن (المجلة الجزائرية للدراسات التاريخية والقانونية, 2022)
لقد حاولنا في هذه الورقة البحثية الكشف عن أهم ملامح و خصوصيات سكان جزيرة جربة و أبرز الحرف التي نشطوا بها. و قد توصلنا إلى معرفة أن سكان جزيرة جربة تميزوا بالتنوع المذهبي و الديني و العرقي، و قد تميزوا أيضا بالتسامح و التعايش بين مختلف الأديان و المذاهب. و قد شهدت جزيرة جربة خلال الفترة المدروسة كثافة سكانية كبيرة مقارنة ببقية مناطق الجنوب التونسي و ذلك نظرا للحركية الإقتصادية التي كانت تشهدها الجزيرة. و قد اقتصرنا في هذه الدراسة على أهم الحرف التي تميزت بها الجزيرة و المتمثلة خاصة في صناعتي النسيج و الفخار، حيث شهدت الجزيرة نموا كبيرا سواء على مستوى عدد المعامل أو كمية الإنتاج، مما أهلها لتكون في تلك الفترة قطبا صناعيا محليا و إقليميا. و مما مكنها أيضا من أن تصبح مصدرة لهذه البضائع التي تميزت بجودة عالية رغم الوسائل التقليدية المستعملة سواء في صناعة النسيج أو الفخار. إلا أن غزو البضائع الأوروبية و خاصة الأقمشة و الأغطية الأوروبية قلّص من عدد المعامل و من كمية الإنتاج في مجال صناعة النسيج.
Keywords: Artisanat – Djerba

‘예루살렘의 대기실’ 제르바 섬 유대 문화의 인식론적 특성 연구 A Study on the Epistemological Characteristics of Jewish Culture in Djerba Island with the ‘Antechamber of Jerusalem’ - Gidae, Lim (경희대학교 글로벌인문학술원 Cross Cultural Studies, 2022)
The Berber people, natives of the Maghreb region, are located on the island of Djerba, where Jewish culture is firmly established. In addition, traces of connection with Jerusalem, the center of the Jewish community, persist throughout the island. The island of Djerba is the only holy place for Jews outside Jerusalem. It is also well known as the ‘Antechamber of Jerusalem’ and preserves its traces relatively well. Therefore, Djerba Island is a very meaningful place as it can look at the exchanges of Jewish diaspora civilization, coexistence, and win-win relationship between Islam and Jews, and Berber. In order to understand the meaning of ‘Antechamber of Jerusalem’, this paper aims to briefly examine the Jewish situation in three Maghreb countries (Morocco, Algeria, and Tunisia) before and after French colonial rule, and to examine the current situation of Jews in the region developed in history. Next, we will assess the characteristics of the Jewish community on the island of Djerba, called the ‘Antechamber of Jerusalem’. Like the rest of the Maghreb region, the island of Djerba is also a place of cultural division. Nevertheless, the memory of Jerusalem remains the strongest in history on the island of Djerba. In this sense, it seems meaningful to examine the issue of epistemological ‘rupture or 'continuity’. This shows how Jews were able to coexist and co-exist on the island of Djerba, the ‘Antechamber of Jerusalem’, and how the French colonization and subsequent process led to a conflict and a ‘rupture’ in the coexistence. Therefore, through this paper, we will be able to understand the Jewish cultural identity of the island of Djerba, coexistence, and conflict of civilization
Keywords: Judaïsme – Djerba

Augustin Jomier, Islam, réforme et colonisation. Une histoire de l’ibadisme en Algérie (1882-1962). Paris, Éditions de la Sorbonne, 2020. 397 pp. €35.00 (pb). ISBN 979-10-351-0532-7. - Messaoudi, Alain (H-France Review, 2022)
Keywords: Recension

베르베르와 예루살렘 관계를 통해서 본 ‘갈등과 공존’의 메커니즘 양상 The Mechanism of ‘Conflict and Coexistence’ in the Relationship between Berber and Jerusalem - Gidae, Lim; Jihoon, Kang (인문사회과학연구 Institute for Humanities and Social Sciences, 2022)
Berber and Jerusalem are not often mentioned because there is not much connection between them. This is because the existence of berber itself has not been mentioned in history. Moreover, the geographical distance from Jerusalem made it impossible to imagine the Berber connection to Jerusalem. However, 'Yennayer', the most important festival for Berbers today, mentions the ancient Pharaoh and Jerusalem. It shows that the relationship between the Berbers, Jerusalem, and the jews has existed since ancient times. This study examines the mechanism of 'conflict and coexistence' between Berber and Jerusalem from ancient times to the present. First, examine the relationship between the Berbers, Jerusalem, and Jews, focusing on the era of the Pharaoh and the era after the destruction of the Jerusalem temple. This process seems very meaningful in examining the relationship between the ancient Berbers and Jerusalem. Second, although there may have been conflicts, there are regions where the paradigm of 'coexistence' has been maintained relatively well. This is not Jerusalem, but the case of Djerba island, which contains the soul of Jerusalem, is a case in point. Although Djerba island is an islamization place, it is a unique place where is lamic ibadism, Berbers, and Jews form a 'coexistence' relationship. It examine how they were able to maintain a relationship of coexistence. Finally, we examine the conflict relationship that erupted again before and after French colonial rule. Such a process provides a meaningful interpretation in examining how the mechanism of 'conflict and coexistence' between Berber and Jerusalem has been formed, and is useful for understanding various forms of cultural exchange in the region.
Keywords: Judaïsme – Djerba

Tunisie : Journées internationales du patrimoine de Djerba - kapitalis, webmaster (Kapitalis, 2022)
Djerba Cult, les Journées internationales du patrimoine de Djerba, se tiendront du 16 au 18 mai 2022n en marge du pèlerinage de Ghriba.
Keywords: Monuments – conservation – Djerba

Anthropological study on human settlements of hot arid environnements - The valley of M'Zab - Naidja, Amina (مجلة العلوم الانسانية لجامعة أم البواقي, 2022)
The human settlement can be considered as a specific historical creation; it has not always existed however appeared at a certain moment in the societies evolution, and can disappear, or be radically changed at another moment. The anthropology of space is interested in the representation, production and social use of human space, just like the cognitive sciences. In this regard, we attempt over this study to analyze the anthropology of Saharan human settlement (The city of Ghardaïa). The results reveal that social ties and human needs are determining factors in the morphology of Saharan human settlements.
Keywords: Urbanisme – Mzab

Câbir b. Zeyd ve İbâdî Fıkhındaki Yeri - Göksün, Ahmet Faruk (İslam Hukuku Araştırmaları Dergisi, 2022)
Hicrî ilk asırda doğan ve aynı asırda vefat eden Câbir b. Zeyd (ö. 93/711-12), tâbiîn âlimleri içerisinde önemli bir konuma sahiptir. Umman doğumlu olan Câbir henüz genç yaşlarda ailesi ile birlikte Basra’ya göç etmiş ve memleketinde aldığı ilk eğitimine burada devam etmiştir. Basra’daki ilmî ortamla yetinmemiş, sık sık Hicaz bölgesine giderek sahâbîler ile görüşme ve onlardan istifade etme fırsatı bulmuştur. Abdullah b. Abbâs başta olmak üzere Hz. Âişe, Abdullah b. Ömer, Enes b. Mâlik, Abdullah b. Mesud, Câbir b. Abdullah, Ebû Hureyre, Ebû Said el-Hudrî (r.anhüm) gibi sahâbenin önemli isimlerinin tedrisinden geçmiş ve onlardan hadis rivayetinde bulunmuştur. Bedir ehlinden yetmiş kişiye yetiştiği ve İbn Abbâs dışında hepsinin ilmini kavradığına dair kendisinden birden fazla eserde aktarılan ifadeler, onun sahâbe ile ne derece sıkı bir bağının bulunduğunu göstermesi açısından önemlidir. Câbir, sahâbenin yanı sıra Hasan Basri, İbn Abbâs’ın azatlısı İkrime ve Muhammed b. Sîrîn gibi tâbiînin meşhur simaları ile de arkadaşlık yapmış ve onlarla karşılıklı ilim alışverişinde bulunmuştur. Sahâbenin ve tâbiîn âlimlerinin övgülerine mazhar olmuş ve Basra gibi ilmî bir merkezde insanlardan kabul görerek fetva vermeye başlamıştır. Câbir b. Zeyd’in başta İbâdiyye mezhebinin ikinci imamı olan Ebû Ubeyde Müslim b. Ebî Kerime (ö. 145/762) ve üçüncü imamı olan Rebîʿ b. Habîb (ö. 180/796) olmak üzere yetmişe yakın öğrenci yetiştirdiği aktarılmaktadır. Ebû Nuh Sâlih ed-Dehhân, Dımâm b. Sâib ve Hayyân el-Aʿrac bunlardan bazılarıdır. Câbir b. Zeyd, İbâdî âlimler tarafından İbâdiyye mezhebinin kurucusu olarak kabul edilmektedir; ancak Sünnî âlimler Câbir b. Zeyd’in İbâdî olmadığını, hatta kendisine bu konu sorulduğunda onlardan beri olduğunu ifade ettiğini aktarmaktadır. Ayrıca Sünnî âlimler tabakât ve ricâl kitaplarında ondan övgüyle söz etmişlerdir. İbâdîlere göre ise bu, baskıcı Emevî idaresinin bulunduğu dönemde yapılmış bir takıyyeden ibarettir. Mezhebin gerçek imamı olan Câbir’in meydana çıkması hareketin geleceği için tehlikeli olacağından dolayı mezhebin dışa bakan yüzü olma görevini Abdullah b. İbâd üstlenmiş, direktifleri ise Câbir’den almaya devam etmiştir. Ancak bu makalenin konusu gereği onun gerçek mezhebi hakkındaki bu tartışmalara girilmeyecek, sadece İbâdî fıkhı içerisinde nasıl bir konuma oturtulduğu tespit edilmeye çalışılacaktır. Câbir b. Zeyd, yaşadığı dönem itibarıyla ilimler henüz birbirinden ayrışmadığı için hadis, tefsir ve fıkıh ilimlerinde belli bir noktaya ulaşmıştır. Bu makalede onun genel olarak ilmî konumuna özel olarak ise fıkıh ve İbâdî fıkhı içerisindeki konumuna temas edilmeye çalışılmıştır. Câbir’in ilmî konumunun tespitinde her bir ilim için farklı kaynaklar üzerinden gidilmiştir. Tefsir ilmindeki konumu için hocası İbn Abbâs’ın onun hakkındaki görüşleri, müfessirlerin ondan nasıl bahsettikleri ve tefsir kitaplarında onun görüşlerine yapılan atıflara bakılmış, hadis ilminde İslâm dünyasında meşhur olan hadis kitaplarında Câbir kanalıyla nakledilen rivayetler ve tabakât kitaplarında onu nasıl anlattıkları üzerinden gidilmiştir. Fıkıh ilminde ise genel olarak ondan aktarılan fıkhî rivayetlerden bahsedildikten sonra İbâdî fıkıh literatürü içerisinden seçilen birtakım eserlerde Câbir’in görüş ve fetvalarına yapılan atıflara bakarak onun İbâdî fıkhı için nasıl bir noktada konumlandığı tespit edilmeye çalışılmıştır. Sonuç olarak ise tefsir ve hadis ilimlerinde yüksek bir mertebeye sahip olan Câbir’in İbâdî fıkhının kurucularından sayılabilecek derecede bir otoriteye sahip olduğu tespit edilmiştir.
Number: 39

The Chronology of Kilwa Kisiwani, AD 800–1500 - Horton, Mark; Olsen, Jesper; Fleisher, Jeffrey; Wynne-Jones, Stephanie (The African Archaeological Review, 2022)
In this article, we present the results of a recent program of high-resolution radiocarbon dating on the urban sequence at Kilwa Kisiwani in southern Tanzania, including Bayesian modeling of 21 calibrated 14C dates. These data come from the 2016 excavation of a large trench directly adjacent to trench ZLL, one of the key 1960s excavations that served to establish the original chronology of the town. The new sequence reported here anchors the phases of Kilwa’s development for the first time in absolute terms. The dates, stratigraphy, and artifact assemblage offer a number of new insights into the timing and tempo of the occupation at Kilwa, notably placing the first coral buildings and coins at the end of the tenth century. Insights also include findings related to the earliest phases of settlement and periods of possible urban decline. We argue against a trend for understanding Swahili towns according to a common coastal trajectory and suggest that it is important to consider regional diversity by recognizing the particular, episodic sequence at Kilwa.
Keywords: Archéologie – Kilwa

Exploring Narratives on Omani Peace Culture - Bonnefoy, Laurent; Rabaani, Ahmed al- (Arabian Humanities, 2022)
The Sultanate of Oman has often been portrayed as a haven of peace in a most turbulent region. The projection of a peace-loving country is at the core of many narratives that this article intends to study, looking at how they are constructed. The purpose of this article is certainly not normative. We do not aim to test the reality or operationalization of such discourses or projections on the allegedly pacific nature of Oman as a state and society. Rather, our purpose is to understand how this dimension has come to be considered a natural feature of contemporary Oman and what arguments, images and figures they mobilize. Our first ambition will thus be to identify the structuration of the narrative focusing on Omani peace and its various dimensions, be they historical, religious, political or diplomatic. We will finally delve into discourses regarding the sustainability of the feature of Oman as a peace-loving country and the challenges it faces.
Number: 16
Keywords: Vie politique – Oman

The Heritage of the Arabian Mission of the Reformed Church in America, the Omani Context, and the Work of Al Amana Centre - Meyers, Justin (Reconciliation, Heritage and Social Inclusion in the Middle East and North Africa, 2022)
The setting of the Sultanate of Oman combined with the heritage of the Arabian Mission of the Reformed Church in America has created a unique context for the work of the Al Amana Centre. This article will explore the history and modern-day experience of tolerance and pluralism in Oman, the historical, theological movements of the Reformed Church in America missionaries toward a more accepting view of Islam, and how these two combine to create opportunities for participants in Al Amana Centre’s programing to discover and experience reconciliation. This article will draw upon scholars who have a long history with Oman, the stories and history of the Arabian Mission, and accounts of the current work of Al Amana Centre.
Keywords: Missionnaires – Oman

The tale of the two Sultanates, Oman and Brunei: Foreign policy and bilateral relations - Hassan, Gubara Said; Al Rabaani, Ahmed Hamad; Nejjari, Maria (Asian Affairs, 2022)
Oman and Brunei are two countries with a long history of sultanic regimes. A sultanate is a kingdom ruled by a Muslim monarch. Because of these two countries’ geopolitical and geostrategic locations, they are very important in global affairs. At the same time, although situated in the highly tense regions of the Middle East and Southeast Asia respectively, Oman and Brunei are generally quite stable. They have recently become involved in China’s global economic project, the Belt and Road Initiative (BRI). Using a theory of small states, this article applies a qualitative research methodology focusing mainly on foreign policy analysis in a comprehensive analytical framework. The study uses face-to-face and by-correspondence interviews with government officials from both sultanates. It investigates whether the domestic determinants of small states’ foreign policy directly affect the bilateral relations between the two sultanates. The main finding of this study is that Oman and Brunei have greatly benefited through the establishment of a satisfactory bilateral relationship based mainly on four pillars from the list of determinants of small states’ foreign policy: historical connectivity, an Islamic monarchical dynastic system of governance, a state rentier economy, and shared foreign policy principles.
_eprint: https://doi.org/10.1080/00927678.2022.2089523
Keywords: Relations – Oman – Brunei

التعليل عند الإباضية وأثره في الفروع الفقهية دراسة أصولية مقاصدية - تمزغين, يوسف بن علي (جامعة العلوم الإسلامية الماليزية, 2022)
Keywords: Fiqh – Ibadisme

نظام العزابة عند إباضية وارجلان في عصر الخلافة الفاطمية بالمغرب (297 – 362هـ) - محمود إسماعيل, سلمى (حوليات أداب عين شمس, 2022)
معلوم أن نظام العزابة أبدعه إباضية بلاد المغرب بعد سقوط الدولة الرستمية علي يد الداعية الفاطمي أبي عبد الله الشيعي سنة 296هـ وفي العام التالي نصب الإمام الإسماعيلي عبيد الله المهدي أول خليفة للدولة الفاطمية في مدينة رقاده. وعلي أثر سقوط الدولة الرستمية وتعرض إباضيتها للاضطهاد نزح معظمهم إلي جبل نفوسة وجزيرة جربة وواحة وارجلان في جوف الصحراء الكبري. في جبل نفوسة حاول إباضيتها إحياء الإمامة الرستمية، لكن جهودهم باءت بالفشل نتيجة تهديدات الخليفة المهدي الفاطمي. وفي جزيرة جرة – وكان إباضيتها علي مذهب النفاثية – نجحوا في إقامة نظام العزابة كبديل لنظام الإمامة، بالمثل أقام إباضية واحة وارجلان – وكان معظمهم علي مذهب الوهبية – نظام العزابة الذي كان أكثر تنظيماً وأكبر تأثيراً من عزابات جبل نفوسية وجزيرة جربة.

Amazigh Politics in the Wake of the Arab Spring - Maddy-Weitzman, Bruce (University of Texas Press, 2022)
Keywords: Berbérisme – Afrique du Nord

André Ravéreau e i progetti per lo M’Zab = André Ravéreau and the plans for the M’Zab - Ruggeri, Daniela (Rivista internazionale di architettura nel mondo islamico, 2022)
The M’ Zab Pentapolis, located on the edge of the northern Sahara, is a settlement system composed of five fortified cities (ksour) founded from the year One thousand by a group of religious dissidents, the Ibadis, on the slopes of the Algerian oasis that runs along the M’Zab uadi. The French architect André Ravéreau, was contacted in 1960 by the Agence du Plan d’Alger to participate in the Plan for the M’Zab Valley. With his wife, the photographer Manuelle Roche, Ravéreau drew up an interpretative analysis of the territory: he broke the valley down into its constituent parts to reuse them in his design projects. His studies also have contributed to create a certain imagery of the model of the “ideal Islamic city”. This paper aims to highlight how the architect’s interpretative reading of the valley is trans- ferred to his projects. Ravéreau was commissioned to design villes nouvelles within a valley surrounded by five ancient Islamic cities. He came up with proposals that were in continuity with the existing urban structure – demonstrating his ability to build relationships between the building, the ancient city, and the landscape – while at the same time attempting to com- bine the requirements of traditional culture with modern aspirations.
Keywords: Architecture – Mzab

حركة الزهد ومنظومة التصوف عند إباضية المغرب (بين الإرث التاريخي والتأثيرات المحلّية) من مطلع القرن الثاني للهجرة إلى سقوط تاهرت 296هـ/909م - بن عمر, علال (مجلة قبس للدراسات الإنسانية والاجتماعية, 2022)
ملخص المقال لا شك أنّ الإباضية باعتبارها أولى فرق الإسلام ظهورا قد عرفت منذ وقت مبكر حركة زهدية اشتهرت عند زعمائهم الأوائل من أتباع المحكّمة الأولى وأهل النهروان، والأكيد أنَّ وحدة الفكر والمذهب بين إباضية المشرق والمغرب جعلت من الممارسات التعبّدية لكليهما مشتركة إلى حدِّ التطابق، لذلك نجد ارتباط إباضية المغرب بحركة الزهد إنما كان عن طريق تأثّرهم بأئمة الإباضية بالمشرق، ولمَّا ارتبطت دعوة الإباضية بحركة الزهد في هذا الوقت المبكّر من ظهور مذهبهم ببلاد المغرب أردنا تتبّع تطور حركة الزهد عند إباضية المغرب انطلاقا من الإشكالية التالية: هل انتقلت حركة الزهد التي عرفها إباضية المغرب في جانبها المظهري والتعبّدي إلى حركة صوفية، لها ممارساتها العملية، وهل ارتقت الحركة الصوفية إلى أن أصبحت ظاهرة اجتماعية؟.تصوف An article summary. the movement of Asceticism and the system of Sufism at the Ibadis of Maghreb ( Between the historical heritage and the local influences). From the beginning of the Hijri second century to the fall of Tiaret (296 AH / 909 CE) In Islam, there is no doubt that Asceticism is a necessary introduction about the Sufism because Asceticism and Sufism are behavior and practice associated with many Islamic doctrines. Certainly, Ibadism was the first islamic sect that appeared since early. Ibadism knew an ascetic movement was famous among their early leaders who are followers of the first Kharijites and the Nahrawan people.The unity of thought and doctrine between the Ibadis of Mashreq and Maghreb showed that the practices of worship are common; Therefore, Ibadhism was associated with the movement of asceticism at this early time when their doctrine appeared in the Maghreb. We tried to follow the evolution of asceticism at Ibadis of Maghreb from the following questions: Do we consider the Ibadi Asceticism like an early stage for the emergence of the Ibadi Sufism? Or that the Ibadi Asceticism was confined about the ritual aspects? Has the Ibadi Asceticism movement been able to become an organized social phenomenon? Or it remained associated with individual exercise, as a special behavior between the servant and his Lord?.

İbâdiyye'nin Hâricîliğe İsnadı Meselesi - Yoldaş, Mehmet Hanifi; Kubat, Mehmet (İslami İlimler Dergisi, 2022)
Sıffîn savaşı esnasında Muâviye ve Amr b. As’ın Tahkîm’e gitme önerisinin Halife Hz. Ali tarafından kabulü onun ordusunda bölünmeye yol açtı. Bu bölünme neticesinde makâlât türü kaynakların “Havâric” olarak adlandırdığı, İbâdîlerin ise “Muhakkimetü’l-Ûlâ” dedikleri ilk fırkalaşma hareketi başlamış oldu. Hicrî 64/684 yılında Muhakkimetü’l-Ûlâ’nın parçalanması ve sonrasında meydana gelen fırkaların hepsi Mezhepler Tarihçileri tarafından genel bir değerlendirme ile Hâricîliğin alt kolları olarak kabul edildi. Yapılan tanımlamalarda Ezârika, Necedât, Acâride, Sufriyye, Beyhesiyye ve diğer Hâricî fırkalar sertlik yanlısı ve aşırıya kaçanlar olarak vasıflandırıldı. İbâdîler ise Hâricîliğin günümüze kadar yaşayan mutedil fırkası olarak kabul edildi. Bu niteleme ile İbâdiyye Hâricî fırkalardan biri olarak konumlandırılmış oldu. Şiddet taraftarı Hâricî fırkalardan hiçbiri varlığını sürdüremezken İbâdiyye’nin günümüze kadar varlığını devam ettirmesinin temel sebebinin görüşlerindeki itidal olduğu söylenebilir. İbâdiyye’yi Hâricî olmakla itham eden müellifler, çeşitli konulardaki görüşlerinin benzerliğini delil gösterirler. Ancak bu iddialar İbâdîler tarafından kesin bir dille reddedilmektedir. Bu makalede İbâdî müelliflerin doğrudan kendi eserleri ekseninde benzer olduğu iddia edilen görüşler Hâricîlerin temel düşünceleriyle karşılaştırılarak bir sonuca ulaşılmaya çalışılacaktır.
Number: 1
Keywords: Kharijisme

الحملات العسكرية العباسية ضد الحركة الإباضية في عمان ١٣٤-٢٨٠هـ/٧٥٢–٨٩٣م - كدرو, نرجس; السلامة, عرفان علي (مجلة إكليل للدراسات الانسانية, 2022)

The Sultanate of Oman in the Historical Context - Barrett, Roby Carol (Manara Magazine, 2022)

Book Review: "Sultan Qaboos and Modern Oman, 1970-2020" by Allen James Fromherz and Abdulrahman al-Salimi, eds. - Junyent, Marc Martorell (Manara Magazine, 2022)
Keywords: Recension

في ذكرى الشيخ طلاي هل يستمر الكفاح؟ - وينتن, مصطفى بن الناصر (2022)
Keywords: Ṭallāy; Ibrāhīm b. Muḥammad (1929-2021)

الاحتياط الفقهي وتطبيقاته عند الشيخ امحمد بن يوسف أطفيش من خلال كتاب "شرح كتاب النيل" باب العبادات والنكاح منوذجا– - إتبيرن, رستم بن عيسى; أرفيس, أحمد بن محمد (مجلة الواحات للبحوث والدراسات, 2022)
Keywords: Atfiyyash; Muhammad b. Yusuf (1821-1914); Fiqh; Fiqh – Commentaires – 19e siècle

ما يوجبه النظر عند الشيخ عامر الشماخي - مباحث الشفعة من كتاب الإيضاح أنموذجا - الدبوز, حسن بن عيسى; باجو, مصطفى بن صالح (مجلة الواحات للبحوث والدراسات, 2022)
تعدد ورود عبارة "ما يوجبه النظر" وما شابهها من صيغ في كتاب الإيضاح للشيخ عامر الشماخي (ت792هـ) الذي يعتبر من أبرز كتب الفتوى عند إباضية المغرب الإسلامي، سنقوم في هذا البحث ببيان الوجوه التي استعمل فيها الشيخ عامر الشماخي هذه العبارة في مباحث الشفعة كأنموذج من مباحث كتابه الإيضاح، فخصصنا المبحث الأول لتعريف الوجوب والنظر في اللغة والاصطلاح ومعنى عبارة "ما يوجبه النظر"، إلى جانب بيان مواضع ورود هذه العبارة واستعمالها في كتب الفقه الإباضي وأبرز المذاهب الإسلامية الأخرى، وقمنا في المبحث الثاني ببيان الوجوه التي استعملت فيها هذه العبارة في مباحث الشفعة من كتابه الإيضاح، بذكر قول المؤلف في تلك المسائل الفقهية ومقارنة بعضها بما ورد في أبرز كتب الفتوى عند الإباضية وعند غيرها من المذاهب الفقهية. The phrase "what is necessary to consider and similar formulations in the book of simplification by Sheikh Amer Al-Shammakh(d. 792 AH) (who wrote the legal opinion in the Ibadis of the Islamic Maghreb) as a phrase to indicate the result of his diligence in jurisprudential issues In the discussions of preemption as a model from the topics of his book the simplification, in the first topic the definition of obligation and consideration and the meaning of the phrase "what is necessary to consider", in addition to explaining the places of this expression and its use in books of Ibadi jurisprudence and the most prominent other Islamic doctrine, and in the second topic it deals with the aspects that In it, Sheikh Amer used this phrase comparing them with what was mentioned in the most prominent fatwa books of Ibadi and books of jurisprudence of all the jurisprudential doctrines.
Keywords: Fiqh

الذاكرة العمانية حتى لا ننسى - الشيباني, سلطان بن مبارك (محبوب للنشر والتوزيع, 2022)

جبل سُوفجج بين النصوص المصدرية الاباضية والمعطيـات الميدانية قراءة تاريخية-طوبونيمية - بوشامة, أحمد; بن علي, طاهر (مجلة الواحات للبحوث والدراسات, 2022)
يُحاول هذا المقال تقديم دراسة في جغرافية جبل سوفجج، والأحداث التاريخية المرتبة به قبيل قيام الدولة الرستمية، وذلك من خلال تحليل ما تفرّدت به المصادر الإباضية من أخبا عن هذا الجبل في هذه الفترة، وربطها بالمعطيات الميدانية التي بقيت شاهدا على وجوده، فانطلق هذا البحث من مُحاولة معرفة البنية اللغوية لاسمه، وتفكيكها لتحديد ما تحمله من دلالات معرفية، ثمّ استجلاء النصوص المصدرية من أجل الكشف عن بعض القرائن التي تخصُّ موقعه الجغرافي، وبعدها عرض ومناقشة الأحداث التاريخية التي ارتبطت بهذا الجبل، بداية من فرار عبد الرحمن بن رستم إليه، والتفاف الإباضية حوله، ثمّ مُحاصرة ابن الأشعث لهم في هذا الجبل، إلى مرحلة انتقال عبد الرحمن بن رستم إلى الموقع الذي بُنيت فيه العاصمة الرستمية. ولتأكيد الحضور الجغرافي لهذا الجبل في منطقة تيهرت، تدعّم هذا المقال، بزيارة ميدانية إلى منطقة الناظورة (جنوب ولاية تيارت) للوقوف على بعض المعطيات الجغرافية التي تُشير إلى وجود جبل سوفجج في هذه النواحي، ثمّ القيام بتحليلها وفق الإطار التاريخي الذي كَشفته المصادر الإباضية عن هذا الجبل. This article attempts to present a study of the geography of : Sufjjaj Mount, and the historical events arranged in it prior to the establishment of the Rustamid state, by analyzing the uniqueness of the Ibadi sources of information about this generation at that time, and by linking them to the field data that have remained witnesses of its existence, this research is an attempt to determine the linguistic structure of its name, to dismantle it to determine its cognitive connotations, then clarify the source texts in order to discover some clues about its geographical location, and this in the context of the display and discussion of historical events that I associated with this mountain, starting with the flight of Abd al-Rahman ibn Rustom towards it, and the ibadi circumference around it, then besieging Ibn Al-Ash'ath for them on this mountain, at the stage of Abd al-Rahman ibn Rustom moving to the place where the capital was built, and to confirm the geographical presence of this mountain, this document was strengthened by a visit to Nadhourah area (Tiaret State) to discover some of the geographical data that indicate the presence of: Sufjjaj Mountain in this regard, and then analyzing the historical framework revealed by the Ibadi sources on this mountain.

الاقلية الذاتية للمنزابيين في الفترة الاستعنارية عزض ومناقشة: الجزء الأول - خواجة, عبد العزيز بن محمد (2022)
Keywords: Recension

العلاقة العلمية بين المشرق الاباضي ومغربه.. قراءة في مراسلة الشيخ أبي مسلم العماني إلى الشيخ اطفيش الجزائري - سيوسيو, صالح بن بكير; بولخراص, كرمية (مجلة الواحات للبحوث والدراسات, 2022)
Keywords: Atfiyyash; Muhammad b. Yusuf (1821-1914); Relations – Oman – Mzab

الاجتهاد بالرأي عند الإباضية خلال القرون الهجرية الثلاثة الأولى- قراءة كرونولوجية نقدية - فخار, جابر بن سليمان; باجو, مصطفى بن صالح (مجلة المعارف للبحوث والدراسات التاريخية, 2022)
تطرق المقال إلى دراسة الموقف العام للمدرسة الإباضية الأولى من الاجتهاد بالرأي، وموقعها بين مدرستي الرأي والأثر، وذلك ببحث مكانة الرأي والقياس لدى أبرز أعلام هذه المدرسة. وقد اختارت الدراسة القرون الثلاثة الأولى محددا زمنيا، والبصرة وعُمَان محددا مكانيا. وكان المنهج استنباطيا تحليليا للنصوص، ونقديا لبعض المفاهيم والمقولات المنسوبة إلى الإباضية في هذا المجال. وقد أسفر البحث عن نتائج تتجلى أهمها في نقد التصنيف العام للمدرسة الإباضية إلى رأي أو أثر، واختيار التصنيف التدقيقي وفق مناهج أعلامها في الاجتهاد. كما توصلت الدراسة إلى تطور الاجتهاد بالرأي عندهم، والمتمثل في دليل القياس، ليكون أكثر حضورا عند إباضية عمان خلال القرن الثالث، ويستقر العمل به خلال القرن الرابع. The article touched upon the study of the general position of the first Ibadi school of ijtihad by opinion, and its location between the two schools of opinion and Hadith and knowing the status of Qiyas among the most important scholars of Ibadism. The study chose the first three centuries as a chronological determinant, and Basra and Oman as a spatial determinant. The approach adopted was an analytical deduction of the texts, and a critical point of some concepts and visions attributed to the Ibadis in this field.The most important results of the research are represented in the criticism of the general classification of the Ibadi school into an opinion or Hadith, and the choice of auditing classification according to the methods of its scholars. The study also found the development of the Qiyas guide for them, to be more present at the Ibadis of Oman during the third century.
Keywords: Fiqh; Ijtihad

‏هداية الرحمن الى ثبوت خلق القرآن تأليف الشيخ القاضي متصور بن ناصر محمد الفارسي (ت: 1396 / 1976م) دراسة وتحقيقها - الجابري, محمد بن خلفان (كلية العلوم الشعرية, 2022)
Keywords: Coran – Commentaires

‏ترجيجات الشيخ الشماخي في باب الطهارات من خلال كتاب الإيضاح دراسة فقهية مقارنة - الجعفري, عبد الرؤوف أحمد (كلية العلوم الشعرية, 2022)
Keywords: Fiqh

الذاكرة العمانية في محضر قضائي من دفتر أحكام القاضي أبي زكريا - الشيباني, سلطان بن مبارك (محبوب للنشر الرقمي, 2022)

المخطوطات العمانية في روسيا وأوروبا الشرقية - الشيباني, سلطان بن مبارك (محبوب للنشر الرقمي, 2022)
p. 24, Cliché de Smogorzewski en habit de Azzabi (source ?)
Keywords: Catalogue – Lviv; Manuscrits – Lviv

قصة نجاح (انموذج إسهام المرأة العمانية) - الشيباني, سلطان بن مبارك (محبوب للنشر الرقمي, 2022)

مظهر الخاف (انموذج مصنفات العروض والقوافي) - الشيباني, سلطان بن مبارك (محبوب للنشر الرقمي, 2022)

تعليق وإحاطة سياقية على هامش محاضرة د. أمل غزال حول بعض مضامين محاضرتها بعنوان: التكوين الذاتي للأقلية: المزابيون وأداء الاختلاف في المستعمر الفرنسية" - حجاج, قاسم بن حمو (2022)
تعتبر الدراسات المتعلقة بتاريخ الأفكار والأيديولوجيات مجال خصب تحليل الأوضاع والتوجهات الماضية والحاضرة والمستقبلية للمجتمعات، وبالاستناد إلى تدريسي الطويل لمادة الفكر السياسي الحديث والمعاصر ولمادة الأقليات والأمن الدولي. ولما كانت الباحثة قد اشتغلت في مراكز أبحاث أمريكية على الأقليات وخاصة الجماعة المزابية في شمال إفريقيا فإنه لا يمكن استبعاد الدور التمهيدي لمثل هذه لمشاريع البحثية على سياسات القوى الكبرى وحتى الإقليمية كقطر وإسرائيل والإمارات في صنع الأقليات والتلاعب بالتركيبات المجتمعية، علما أن للباحثة أعمال علمية سابقة منشورة عن المزابيين منها دورهم في شمال إفريقيا إبان الحرب العالمية الثانية وعلاقاتهم الخارجية بدويلة طرابلس وبتونس...

دور الجهود الرسمية والاهلية في حفظ المخطوط العماني وصيانته وتحقيقه ونشره وفهرسته ورقمنته - سويلم, منال محمد (2022)
Keywords: Manuscrits – Conservation; Manuscrits – Oman

القيم الحضارية للمخطوط العماني من خلال كتاب الف باء المخطوطة العمانية - النوفلي, حميد بن سيف (2022)
Keywords: Manuscrits – Oman

دور الشيخ سليم بن يعقوب الجربي في انقاد التراث العماني في مصر - ناصر, بالحاج بن باحمد (2022)

جهود اللجنة العلمية بموقع بصيرة ومكتبة خزائن الاثار في خدمة المخطوط العماني - الراشدي, الأزهر بن يوسف (2022)
Keywords: Manuscrits – Oman

تحقيق ودراسة كتاب مبتدا الكشف في علم الصرف - الريامية, كاملة بنت سليمان (2022)

رحلة المخطوط العماني الى الجزائر: نموذج مكتبة الحاج صالح لعلي بوادي ميزاب - وينتن, مصطفى بن الناصر (2022)
Keywords: Manuscrits – Mzab

الاسهامات الجزائرية في خدمة المخطوط العماني - زرمان, محمد (2022)

دور الرحلات في انتقال المخخطوط العماني الى الجزائر - الحاج موسى, بشير بن موسى (2022)
Keywords: Bibliothèques – Mzab

جهود الشيخ سيف بن حمود البطاشي في خدمة المخطوطات العمانية - البطاشي, ماجد بن محمد (2022)

اهمية مخطوطات التاريخ المحفوظة بدار المخطوطات في وزارة التراث بسلطنة عمان - يطو, فتيحة (2022)
Keywords: Manuscrits – Oman

جهود جامعة السلطان قابوس الريادية في حفظ المخطوطات العمانية - الخالدي, أنور عوده (2022)
Keywords: Manuscrits – Oman

خزانة سعيد بن ناصر بن حمود السعدي واسهامها في حفظ المخطوط العماني - السعدي, طالب بن علي (2022)
Keywords: Bibliothèques – Oman

اسهام مؤسسة ذاكرة عمان في خدمة التراث العماني المخطوط: مجلة الذاكرة انموذجا - يطو, عائشة (2022)
Keywords: Manuscrits – Oman

جهود المؤسسات الاهلية في خدمة التراث الفكري العماني: مركز ذاكرة عمان انموذجا - الجالودي, عليان (2022)
Keywords: Manuscrits – Oman

جهود المؤسسات الخاصة في ترميم المخطوطات العمانية وصيانتها: بيت الترميم انموذجا - الشكيلية, وضحة بنت محمد (2022)
Keywords: Manuscrits – Oman

فلك الانوار ومحك الاشعار بين القيمة المعرقية ومشكلات النسخ والتحقيق - بنجلالي, عبد المجيد (2022)

الجهود العمانية في صنعة المخطوط: مبتدا الكشف في علم الصرف انموذجا - الصوافي, حمود بن عامر بن ناصر (2022)

المخطوط العماني وملامحه المادية: المصحف والكتاب الصحاري والبهلاني انموذجا - الشريف, لؤي محمد (2022)

الجوانب الفنية في مخطوط ديوان المتنبي بمكتبة ناصر بن صالح الاسماعيلي - الإسماعيلي, ناصر بن صالح (2022)

المدن في ساحل شرق افريفيا طبقا لمخطوطة السلوة في اخبار كلوة - السعيد, وفيقة أحمد (2022)

موانئ وحصون وفلاع الساحل العماني في ضوء مخطوط برتغالي: دراسة في التاريخ الاثار - البياضي, سامي صالح عبد المالك (2022)

معجم اعلام الاباضية في خراسان وخوارزم والجزيرة وبلاد الهند والسند - الشيباني, سلطان بن مبارك (محبوب للنشر الرقمي, 2022)

الجهود العلمية لرقمنة المخطوطات العمانية في الفضاء الالكتروني بين الواقع والافاق - أبو رحمة, سعيد (2022)
Keywords: Manuscrits – Oman

الاتجاهات الراهنة والمستقبلية في رقمنة المخطوطات (رؤية في المخطوط العماني) - الرحامنة, علي (2022)
Keywords: Manuscrits – Oman

برامج القراءة الالية المخطوط العربي: من التعرف الى تحليل المحتوى - حمادي, طارق (2022)

تصور مقترح لدراسة اشكاليات المخطوطات العمانية وسبل التغلب عليها - العابد, وفاء زهير (2022)
Keywords: Manuscrits – Conservation; Manuscrits – Oman

تقاليد النساخة في المخطوط العماني - حاج أمحمد, عيسى بن إبراهيم (2022)
Keywords: Manuscrits – Oman

دور النساخ في حفظ المخطوطات العمانية ووصولها الى المكتبات - الشماس, سارة محمد (2022)
Keywords: Manuscrits – Oman

دور جامعة نزوى في تحقيق المخطوطات - آل ثاني, يعقوب بن سالم (2022)
Keywords: Manuscrits – Oman

الجهود الاهلية في خدمة المخطوطات العمانية: مركز منح الثقافي انموذجا - البوسعيدي, سالم بن علي (2022)

مشاركة الاردن في احياء الموروث العماني - الدروبي, محمد (2022)

المخطوط العماني في كتابات واهتمامات المؤرخة والاكاديمية النرويجية ان كي بانج - الحسيني, سليمان بن سالم (2022)
Keywords: Manuscrits – Oman

المخطوطات العمانية واسهامها في كتابة التاريخ العماني والتطورات الحضارية - الحسيني, فاضل محمد (2022)
Keywords: Manuscrits – Oman

توثيق الانساب في المخطوطات العمانية - العبدلي, خالد بن محمد (2022)

القيم الاجتماعية والتاريخية والثقافية للمخطوطات العمانية - بني يونس, يوسف بن محمد (2022)
Keywords: Manuscrits – Oman

العلقات العمانية العثمانية من خلال قراءة وثائقية في الارشيف العثماني (دراسة وثائقية تاريخية) - مشرف, عبد اللطيف بن عبد الغني (2022)

تجربتي في رصد مصطلحات المخطوط العماني - الشيباني, سلطان بن مبارك (2022)

خزانة عبد الله بن زياج وقيمتها التاريخية والحضارية - السعدي, فهد بن علي (2022)
Keywords: Bibliothèques – Oman

المخطوطات الادبية العمانية بين تحقيق والنشر - عبد الله, هناء عبد الكريم فضل (2022)
Keywords: Manuscrits – Oman

دور الاعلام الجديد في تعزيز ثقافة الحفاظ على المخطوطات العمانية - أبو شباب, محمد بن سالم (2022)
Keywords: Manuscrits – Conservation; Manuscrits – Oman

اسهامات السيد حمود بن أحمد البوسعيدي الوقفية بزنجبار ومكة المشرقة: قراءة تحليلية لبعض مضامين وثائقه الوقفية - القدحات, محمد بن عبد الله (2022)
Keywords: Waqf (fondations) – Zanzibar

دور المؤسسات الرسمية والأهلية في سلطنة عمان في البحث عن المخطوطات العمانية المهاجرة (جهود هيئة الوثائق والمحفوظات الوطنية انموذجا) - المحذوري, عبد العزيز بن حميد (2022)
Keywords: Manuscrits – Oman

محطوطة مواقيف سمد نزوى ودورها الحضاري والثقافي - البطراني, جمعة بن خلفان (2022)
Keywords: Bibliothèques – Oman

وثائق الشيخ محمد بن سالم الرقيشي (1387هـ) وقيمتها العلمية والتاريخية والحضارية - الحوسني, زاهر بن عبد الله (2022)

القيمة الحضارية لنسخ الاوقاف العمانية: نسخة الشيخ محمد بن أخمد الكندي لاوقاف سمد نزوى انموذجا - الرحبي, خالد بن محمد (2022)
Keywords: Waqf (fondations) – Oman

مخطوط خزانة الاخيار في بيوعات الخيار للخراسيني: فراءة تحليلية معاصرة - حريز, سفيان (2022)

المخطوط العماني: هوية وتراث - الخالدي, أنور عوده; عثامنة, محمد سعيد صلاح (2022)

مكتبة السيد محمد بن احمد البوسعيدي ودورها الريادي في حفظ المخطوط العماني - الكندي, أحمد بن عبد الله; الناصري, أحمد (2022)
Keywords: Bibliothèques – Oman

دور المؤسسات الحكومية والخاصة والجامعات والاعلام في حفظ المخطوطات العمانية - الهنداوي, هنادي زعل (2022)
Keywords: Manuscrits – Oman

خدمة المخطوط في كلية العلوم الشرعية من البكالوريوس الى الماجستير - بوعجيلة, فتحي (2022)
Keywords: Manuscrits – Oman

الجهود الرسمية في حفظ المخطوط العماني وصيانته وتحقيقه ونشره وفهرسته - الطارشي, محمد بن فائل بن علي (2022)
Keywords: Manuscrits – Conservation; Manuscrits – Oman

جهود وزارة التراث والسياحة في حفظ المخطوطات العمانية: جهينة الاخبار اموذجا - محروس, صلاح محمد; الكاسبي, يوسف بن سعيد بن ناجم (2022)
Keywords: Manuscrits – Conservation; Manuscrits – Oman

المستظهرون لكتاب الله العزيز بالقرارة (1442 1443 / 2021 2022) (الحياة, 2022)

شفرة الباروني (مخطوط الأزهار الرياضية) - أبو الصديق, مليكة بنت حمو بن باحمد (الحياة, 2022)

البراءة والعضوية في المجتمع المسلم - التندميرتي, عمرو أحمد (الحياة, 2022)

تحريم الاحتكار وأثره في إصلاح الاقتصاد من منظور إسلامي - الجهضمي, علي بن سليمان (الحياة, 2022)

القيادات العلمية ودورها في اختيار أئمة الحكم بعمان (الحلقة الثانية) - الريامي, عبد الله بن سليمان (الحياة, 2022)

الافتتاحية - الشيخ بالحاج, بكير بن محمد (الحياة, 2022)

الاجتهاد المقاصدي عند الإباضية في باب الأحوال الشخصية (ملخص أطروحة دكتوراه) - الصادق, ياسين بن أحمد (الحياة, 2022)
Keywords: Ijtihad

ملامح الكتابة التأريخية عند الشيخ أبي مهدي عيسى المصعبي (من خلال تراثه) (الحلقة الثانية) - امعيز الحاج أحمد, باحمد بن داود (الحياة, 2022)

وثيقة اتفاق عرش القرارة في عرف السيل ومجراه - بكوش, محمد بن موسى (الحياة, 2022)

المعازف والغناء؛ دراسة من خلال تطبيق القاعدة الحديثية: حد النص التابع للسند - بن دريسو, مصطفى بن محمد (الحياة, 2022)

قراءة نقدية لكتاب بدء الإسلام وشرائع الدين - بن يحياتن, ساسي بن عمر (الحياة, 2022)

في حياة الإمام جابر بن زيد الأزدي مشروع أمة (الحلقة الثانية) - بوحجام, محمد بن قاسم ناصر (الحياة, 2022)

المعلقات والألواح في الميزان - بوراس, يحيى بن عيسى (الحياة, 2022)

النظام القضائي في المجتمع المزابي (الحلقة الثالثة) المحكمة الشرعية الإباضية بالقرارة نموذجا - حمدي, إبراهيم بن صالح (الحياة, 2022)

قانون المشيئة في الكتاب من خلال بعض أسماء الثواب «الرحمة» و«المغفرة» نموذجا (الحلقة الثانية) - حمدي, إبراهيم بن صالح (الحياة, 2022)

العلاقات المتبادلة بين الأغواط وغرداية زمن الحركة الإصلاحية - خبزي, موسى بن محمد (الحياة, 2022)
Keywords: Réformisme – Mzab

«إن مع العسر يسرا» (شعر) - دواق, سليمان بن عمر (الحياة, 2022)
Keywords: Poésie – Mzab

الآثار العلمية للشيخ أبي عبد الله محمد بن بكر الفرسطائي (الحلقة الثانية) - زندوح, منير محمد خليفة (الحياة, 2022)
Keywords: Furṣuṭāʾī; Muḥammad b. Bakr

القواعد والضوابط الفقهية للعمارة في الفقه الإباضي: كتاب القسمة وأصول الأراضين للشيخ أبي العباس أحمد بن محمد الفرسطائي نموذجا (ملخص أطروحة دكتوراه) - كعبوش, زكرياء بن قاسم (الحياة, 2022)
Keywords: Fiqh; Furṣuṭāʾī; Aḥmad b. Muḥammad

«ماذا يقول الرداء؟!» (شعر) - ناصر, محمد صالح (الحياة, 2022)
Keywords: Poésie – Mzab

Abū Isḥāq Aṭfayyiš eṭ la redéfinition de l’identité ibadite dans l’entre-deux guerres (1923-1939) : réformisme, communauté et pouvoir - Cernon, Baudouin de (Inalco, 2022)
Keywords: Aṭfiyyash; Ibrāhīm b. Muḥammad (1886-1965); Réformisme – Mzab

Cahier Trouvé Sous L'oreiller: Poésies de Jeunesse 1958 - 1965 - Perreau, Anne-Marie (Le Lys Bleu Éditions, 2022)
Intro – I – Poèmes de jeunesse - De 1958 à 1965 – (Écrits entre 10 et 17 ans) – Interrogation – Symphonie du passé – Sonate pour une défaite – Sonate pour les jours monotones – Symphonie du bout du monde – Drogue – Lilas – À toi, qui que tu sois – Rêve de mai – Spleen – Ami, lève la tête – Chanson – Si… – La reine des gitans – Nativité – Berceuse rose – Solitude – Le sentier de Calais – France, mon amie – Jeunesse – Visite – La mouette et le marin – Reflets – L'obscur jardin de ma jeunesse – Adieu au Saint-Laurent – À la mère qui n'existait pas – Poème jamais écrit – Départ – Dans un square à Saint-Denis – Nuits tunisiennes – Dans une rue – Illusion – Djerba – Sur El Edjezaïr – Départ – Attente – Bateaux – Prose du minuit new-yorkais – II – Poèmes plus tardifs – Une autre fois, peut-être… – Éblouissement – Toi, mon amour, mon frère – Notes.
Keywords: Poésie – Djerba

Commerce d’êtres humains et projets coloniaux à Zanzibar et Kilwa : Étude de la traite négrière française à la côte swahilie et des relations diplomatiques liant Français, Swahilis et Omanais (1770-1859) - Belhacel, Abdelhakim (Université Paris Nanterre, 2022)
Keywords: Zanzibar

كيف نفكر في الفن الإباضي ؟‏ ‏مقاربة آثارية مذهبية للموروث الإباضي في بلاد المغرب الإسلامي الوسيط‏ - عبد الستار, عاطف (GLD, 2022)
في هذه الدراسة حرص الأستاذ عاطف عبد الستار على عرض وتوليف مختلف الدراسات وخاصة أحدثها المتعلقة بالعمارة الإباضية مثريا المادّة المتنوعة التي جمعها والمتعلقة بأشهر وأهم المناطق الإباضية بالغرب الإسلامي (معتمدا على نماذج) من الفقه الإباضي (ومنخرطا) في الإشكالية القديمة المتجددة حول هوية هذا الفن الذي تتنازعه إكراهات البيئة وصروف الدهر والعقائد الإباضية، بمعنى آخر هل نحن إزاء عمارة إباضية أم عمارة محلية ؟ إشكالية كنا قد طرقنا جوانب منها في ما يخص عمارة مساجد جربة، وها هو ذا الأستاذ عاطف عبد الستار يوسّع الاهتمام بها إلى وادي مزاب وجبل نفوسة، وهي (إشكالية.) في (قلب.) الإشكالية الأم المتعلقة بمساهمة الفن الإسلامي. بهذا المعنى يضع اليوم هذا الباحث الشاب بين يدي قراء العربية يجمع ويلخص دراسات أكاديمية يصعب الوصول إليها على عموم القرّاء، في صياغة على قدر من الوضوح والجرأة المتحررة أحيانا من الضوابط. -الأستاذ قيصر الجليدي-

الجزائريون بالبلاد التونسية زمن الإستعمار الفرنسي : ‏رعايا الباي ورعايا الدولة الفرنسية (1830-1939)‏: ‏دراسة تاريخية لإشكالية الإستعمار والهجرة وتجزئة الأوضاع القانونية للمجتمعات الإسلامية‏ - الماجري, عبد الكريم (نشر المؤلف, 2022)
Keywords: Emigration – Mzab – Tunisie

Le bilan du sommet de Djerba passé en revue entre Jerandi et Desiree N. Herrera - African Manager (2022)
Le ministre des Affaires étrangères, de la Migration et des Tunisiens de l'étranger, Othman Jerandi a reçu, mardi, le conseiller politique et diplomatique
Keywords: Francophonie – Djerba

جذور"(إِزُورَانْ/ ⵉⵣⴻⵔⴰⵏ) - جمعية التنشيط الثقافي جربة حومة السوق (2022)
تتشرف جمعيّة التنشيط الثّقافي بجربة بدعوتكم لمواكبة تظاهرة "جذور"(إِزُورَانْ/ ⵉⵣⴻⵔⴰⵏ) وذلك يوم الإربعاء 21 ديسمبر 2022 بداية من الساعة الثّالثة مساء بالمركز الثّقافي والسّياحي المتوسّطي. وتتضمّن التظاهرة: -تقديم كتاب رسالة في تراجم علماء جربة لسعيد بن تعاريت تحقيق ساسي بن يحياتن: يقدّم الكتاب الأستاذ بشير بن غازي. -تقديم كتاب حكايات أمازيغيّة جربية لفتحي بن معمّر: تقدّم الكتاب السيّدة صالحة القطوفي. -افتتاح معرض الرّسام لطفي الغول برواق المتوسّط الذي يتواصل إلى يوم الأحد 25 ديسمبر 2022.
Keywords: Vie culturelle – Djerba

Le site de Ras R’mal à Djerba, théâtre de tous les outrages - Bouabid, Naceur (Kapitalis, 2022)
La situation dans laquelle se trouve, aujourd’hui encore, la flèche sableuse de Ras R’mal à Djerba est regrettable, déplorable et révoltante. Voilà pourquoi… Par Naceur Bouabid * Cette situation est regrettable au vu du sort ingrat et réducteur réservé à ce merveilleux site naturel d’une rare beauté et aux spécificités paysagères exceptionnelles, indigne d’une zone humide...
Keywords: Crises environnementales – Djerba

Ceremony held at Tokyo University on donation of books by Sultanate of Oman (Arab News Japan, 2022)
Arab News JapanTOKYO: A ceremony was held on Friday to ・・・
Keywords: Relations – Oman – Japon

Le projet du Centre culturel de Djerba avance à grands pas (Kapitalis, 2022)
L’île de Djerba sera prochainement dotée de l’un des plus grands centres culturels du pays. Le chantier avance à grands pas et le projet ne tardera plus à se concrétiser. La construction d’un immense complexe culturel à Djerba est une initiative du metteur en scène et réalisateur Fadhel Jaïbi qui a longtemps rêvé de ce...
Keywords: Vie culturelle – Djerba

Les Juifs de Djerba au passé et au présent - Gozlan, Martine (Marianne, 2022)
Au musée d’Art et d’histoire du judaïsme, à Paris, une exposition consacrée au photographe Jacques Perez remet à l’honneur Djerba, sa lumière et son dernier ilot hébraïque.
Keywords: Judaïsme – Djerba

Tunisie : les dessous peu ragoûtants du pèlerinage juif de la Ghriba - Bomse, Audrey; Chabbi, Nizar (Kapitalis, 2022)
Nizar Chabbi nous a fait parvenir ce texte, co-écrit avec Audrey Bomse, avocate juive américaine de Floride, publié une première fois en mai 2014, et réécrit récemment, où il évoque les dessous peu ragoûtants du pèlerinage juif à la synagogue de la Ghriba, à Djerba, en Tunisie. La normalisation du président Kaïs Saïed, le plus...
Keywords: Judaïsme – Djerba

Interventions auprès de l'administration pénitentiaire: Un islam méconnu : l'ibadisme (Université Lumière Lyon 2, 2022)
4 - "Un islam méconnu : l'ibadisme" / Cyrille Aillet : parmi les multiples courants de pensée qui ont caractérisé le monde musulman des premiers temps, l'ibadisme est l'un des plus méconnus. Très minoritaire aujourd'hui, il s'est implanté principalement en Arabie et parmi les Berbères du Maghreb, où il a fondé des pouvoirs régionaux. Son étude permet pourtant d'accéder à des traditions théologiques et politiques très anciennes et de découvrir une vision originale de l'imamat, c'est-à-dire de la souveraineté et du gouvernement en Islam."
Keywords: Ibadisme – thèmes et motifs

Djerba comme on ne l'a pas encore visité - El Cadi, Khaoula (TICDCE, 2022)
Keywords: Tourisme – Djerba

Le Tafsīr de Hūd b. Muḥakkam al-Hawwārī (IIIe/IXe s.). Analyse d’un commentaire coranique ibadite - Khelifa, Ahmed (Université Lumière Lyon 2, 2022)
Ce travail de fin d’études pour l’obtention du Master est consacré à l’analyse d’un commentaire coranique peu connu, en l’occurrence, celui de Hūd b. Muḥakkam al-Hawwārī (m. v. 280/893), un exégète ibadite du IXe siècle. En effet, les études consacrées à la tradition exégétique ibadite se comptent sur les doigts d’une main d’où notre intérêt pour le sujet. L’objectif était de voir dans quelle mesure le commentaire de Hūd constitue le témoin d’une tradition exégétique proprement ibadite. A l’issue d’une analyse comparative avec un commentaire qui lui est antérieur à savoir le tafsīr de Yaḥyā b. Sallām (m. 200/815), un exégète de Baṣra qui a vécu à Kairouan à la fin de sa vie où il a diffusé son savoir religieux et notamment son commentaire coranique, qui a été utilisé ultérieurement par Hūd b. Muḥakkam, comme source principale pour réaliser un tafs īr abrégé compatible avec sa doctrine ibadite. Tel est le résultat que nous avons établi par une étude comparative intertextuelle entre les deux commentaires. De la même manière, la comparaison avec l’exégèse sunnite de Ṭabarī (m. 310/923), elle ne laisse aucun doute que l’abrégé de Hūd s’inscrit entièrement dans le cadre de la doctrine ibadite. Après avoir confirmé l’hypothèse formulée par l’éditeur du commentaire coranique à savoir que Hūd b. Muḥakkam s’est basé sur le tafsīr d’Ibn Sallām pour réaliser son commentaire exégétique, ce mémoire a permis également de déterminer la méthode exégétique de l’auteur ibadite qui a été basée essentiellement sur la séléction dans le commentaire source d’Ibn Sallām, des traditions jugées compatibles avec les fondements de son école ibadite et le rajout de quelques adaptations afin de rendre son commentaire conforme aux attentes de sa communauté.
Keywords: Coran – Commentaires – 9e siècle; Hawwārī; Hūd b. Muḥkim al-

جربة حكايات فونادة وجومادة - العمري, الصادق (2022)

كتاب النكاح للشيخ ابي زكرياء الجناوني (ق 5-6هـ/11-12م): دراسة وتحقيق من بداية الكتاب الى باب نكاح المتعة ونكاح الشعري - بكلي, إبراهيم (جامعة غرداية, 2022)
Keywords: Fiqh – Libye – 12e siècle; Jannāwunī; Yaḥyā b. al-Khayr

Islam, réforme et colonisation. Une histoire de l’ibadisme en Algérie (1882-1962), written by Augustin Jomier - Francesca, Ersilia (Studia Islamica, 2022)
Keywords: Recension

Salah Ben Youssef et les youssefistes au tournant de l'indépendance tunisienne 1955-1956 - Oualdi, M'hamed (Cérès Editions, 2022)
Keywords: Ben Youssef; Salah 1907-1961

Le théâtre de plein air de Djerba - Zarrouk, Riadh (Archibat, 2022)
Keywords: Architecture – Djerba

Religious and political authority among the Ibadis of Sahara: Not Sunni, not Arab, but Algerian? - Vikør, Knut S. (2022)
In the Sahara, the oasis of Mzab is the home of a small minority of Berber-speaking Muslims, the Ibadis. Long time isolated, they were for the first time integrated into what became “Algeria” with French colonialism. This raised the challenge for the religious and worldly authorities of the community: Should they resist integration into the new larger entity, or should they join in a wider, national struggle for Islamic renewal? How should they relate to the foreign, French authorities? This seminar will place the Mzab in Ibadi history, and trace how the community responded to these challenges during the twentieth century.
Keywords: Réformisme – Mzab

Front de libération du Dhofar, 1965 : La lutte armée dans le Dhofar arabe - Seurat, Leila; Sfeir, Jihane (Ecrits politiques arabes: une anthologie des idées au Maghreb et au Machrek au XXe siècle, 2022)
Keywords: Dhofar

جزيرة جربة ورحلة المشتاق - البوجديدي, علي (إبداع - الإصدار الرابع, 2022)
Keywords: Récits de voyage – Djerba

العمارة التقليدية بمنطقة الجريد: عمارة المسكن نموذجا - القليوبي, هاني أحمد محمد (مجلة الإتحاد العام للآثاريين العرب, 2022)
"يتناول هذا البحث العمارة السكنية التقليدية بمنطقة الجريد التونسي الواقعة في واحات الجريد التونسي جنوب غرب البلاد التونسية والتي تتبع ولاية توزر إداريا، يشتمل البحث على مقدمة عامة عن المسكن التقليدي وموضح بها إشكالية الدراسة وأهداف الدراسة والإطار الجغرافي والتاريخي للمنطقة، ثم تطرقت لتناول البحث على ثلاث محاور رئيسة تتمثل في: -المحور الأول: يتناول مكونات عمارة المسكن التقليدي. -المحور الثاني: يتناول مواد البناء وتقنيات البناء والعناصر الزخرفية. -المحور الثالث: يتناول التصنيف الفني لأنماط العمارة التقليدية بالمنطقة. لقد مكنني البحث في تلك العمارة بتصنيفها ضمن ما اصطلح على تسميته بالمعمار المحلي، فهوية عمارة الجريد هي نتاج لمورث محلي في عناصره الزخرفية، كما مثلت المحلية روح شخصيتها من خلال الاعتماد على مواد البناء المحلية مثل الآجر والطوب وخشب النخيل، كما مثلت أيضا البساطة في عمارة المسكن الجريد أهم الخصوصيات المعمارية التي ظهرت على المعمار التقليدي بمنطقة الجريد، ويلاحظ ذلك من خلال النموذجين اللذان وقعا الاختيار عليهما بمدينة نفطة ولقد قمت بوصفهما مع التوضيح بالأشكال واللوحات."
Place: القاهرة
Keywords: Architecture – Nefta

الحلقة في نظام العزابة: المهاد التاريخي والبنى الرمزية - اللموشي, إقبال العبيدي (مجلة روافد للدراسات والأبحاث العلمية في العلوم الاجتماعية والانسانية, 2022)
نتناول في هذه الورقة العلمية المقترحة: الحلقة في نظام العزابة: المهاد التاريخي والبنى الرمزية، قراءة في نظام حلقة العزابة بجزيرة جربة في حدود القرن الخامس هجريا. وتنطلق هذه القراءة من النصوص الإباضية المؤسسة للدرجيني (ت 670ه/ 1271م) والبرادي (ت 810 ه/ 1407م)، وصولا إلى النصوص الاستشراقية اللاحقة، مستقرئين ما تستبطنه مكوناتها من دلالات وبنى رمزية. ومما لا شك فيه أن مقاربة النصوص الإباضية المؤسسة كفيلة بالكشف عن أصالة مفهوم الحلقة، وحيثيات تكونها. ما نريد الإبانة عنه في هذا المقال، من خلال دراسة الممارسات اليومية بما تحمله من طقوس اللباس والأكل وقوانين الانتظام وقواعده، لحلقة العزابة هو البحث في المهاد الذي ولد فيه مفهوم "الحلقة"، وكيفية تطوره، محاولين الكشف عن بناه الرمزية والدلالات الثقافية التي يمارسها الوعي واللاوعي الجمعي على حد سواء.
Place: عين تموشنت

من أجل بعث مسلك ثقافي وسياحي بجزيرة جربة: طريق الزيتون - بن صالح, عماد (أبحاث المؤتمر الدولي الأول: التراث الثقافي بالبلدان المغاربية - القيم المجتمعية والاستثمار التنموي, 2022)
Keywords: Moeurs et coutumes – Djerba

الإباضية الذاكرة المتشظية - تغلات, زهير (حوارات فكرية, 2022)
Place: تونس

ماذا بقي من المذهب الإباضي ببلاد الجريد؟ واحة نفطة نموذجا: دراسة في الأنتروبولوجيا التاريخية - النوري, نور الدين (2022)
Keywords: Ibadisme – Djérid

مدونة أعلام الإباضية ببلاد الجريد خلال العصر الوسيط - النوري, نور الدين (2022)

Sectarianism in Islam: the Umma divided - Gaiser, Adam R. (Cambridge University Press, 2022)
"This is a book about intra-religious divisions among Muslims - what medieval Muslims might have called, and contemporary Muslims might call (sing. madhhab). That is to say, it is a book about how Muslims have, over the course of their long history and in the many geographical areas where they found themselves, forged and often re-forged divergent notions of what it means to be a Muslim. This process might be called "sectarianism," or even "Islamic sectarianism," though the moniker is fraught with problems, not the least of which being that several of the recognized divisions among Muslims (e.g. ) would not technically qualify as being "sects" according to the myriad scholarly definitions of that term. To account for this particular issue, this work focuses on Muslim sects and "schools," meaning here schools of thought, as a means of approaching what Muslim authors might have implied when they described these groups as At the outset, it is worth asking after the purpose of such a book? Why read it? On the face of it, it would seem that current world conditions make the answers to these questions obvious: communal unrest or outright violence in Muslim majority countries such as Iraq, Bahrain, Lebanon, Yemen, and Pakistan (to name a few) often gets articulated in sectarian terms, not only by the actors and the victims of such violence, but also by the various journalists, anchors, and writers whose task it is to report and explain these events to the rest of the world. For many popular media outlets, affiliations, such as Sunni or , offer convenient identity markers by bounding groups by their communal affiliation. These sectarian classifications are meant to "make sense" of conflict in the Islamic world by providing their readers a means to navigate that world, and they gain legitimacy as explanatory devices insofar as they reflect the ways that some Muslims articulate the underlying causes of their conflicts. Indeed, many Sunnis and among others, employ sectarian categories as a means to identify themselves, or as the basis for polemics (as a simple search of the internet will show), or as a reason to engage in violence. Journalists, then, can accurately claim that their reporting reflects "local" perceptions of the situation on the ground"–
Don de l'auteur

‫قراءة في كتاب العقيدة‬ - الهميمي, الفاضل سليمان بن عبد الله (2022)

‫قراءة في مذكرات غير منشورة‬ - الحوقاني, خليل بن محمد بن راشد (2022)
Keywords: Biographies – Djerba – 20e siècle

‫الشيخ عاشور وحياته التربوية والدعوية‬ - القصابي, خليفة بن احمد (2022)
Keywords: Biographies – Djerba – 20e siècle

‫الشيخ عاشور كسكاس والعمل الجمعياتي‬ - قوجة, صلاح الدين بن رخب (2022)

‫ندوة الشيخ عاشور بن يوسف (عطاء علمي ومسلك تربوي)‬ - الشبلي, عمر (2022)

‫الجانب الإنساني لدى الشيخ عاشور‬ - مصلح, أحمد بن مهني (2022)

‫شيخ عاشور نسبه وحياته العلمية - كسكاس, رضوان بب عاشور (2022)
Keywords: Biographies – Djerba – 20e siècle

Was Muṭarrif b. al-Mughīra al-Thaqafī a Khārijite? Rebellion in the Early Marwānid Period - Hagemann, Hannah-Lena (Al-ʿuṣūr al-wusṭa, The Bulletin of Middle East Medievalists, 2022)
This article reassesses the “Khārijite” rebellion of Muṭarrif b. al-Mughīra b. Shuʿba al-Thaqafī in 77/696–97 and recontextualizes it within a different “category” of revolt. Analyzing both the history and the historiography of this uprising, the article argues that Muṭarrif’s rebellion is best understood not within a Khārijite framework, but rather as part of a series of revolts carried out by other Iraqi tribal notables (ashrāf) in the same period. This reevaluation is based, for example, on the composition of Muṭarrif’s following, which shows clear connections with other important Iraqi/eastern leaders, such as Muṣʿab b. al-Zubayr, Ibn al-Ashʿath, and Yazīd b. al-Muhallab. These connections, observable in other structural patterns common to Marwānid-era rebellions as well, point to a similarity of grievances, reactions, and aims whose salience far exceeded the context of individual revolts. More broadly, this article also seeks to challenge the received scholarly understanding of Khārijism and to question its usefulness as a category of historical analysis, suggesting instead different approaches to a renewed engagement with this phenomenon.
Keywords: Kharijisme

تحقيق نسبة كتاب الوضع إلى الشيخ أبي زكرياء الجناوني - بكلي, إبراهيم; باجو, مصطفى بن صالح (مجلة الواحات للبحوث والدراسات, 2022)
ملخص: تهدف هذه الدراسة إلى التحقق من نسبة كتاب الوضع إلى الشيخ أبي زكرياء الجناوني (ق05-06هـ/ 11-12م) الذي اشتُهِر بنسبة الكتاب إليه شهرة مستفيضة مع وجود بعض الشكوك في نسبة الكتاب إليه من بعض العلماء قديـمًا وبعض الباحثين حديثًا، وذلك من خلال استعمال المنهج الوصفي والمنهج الاستقرائي والمنهج التحليلي، والرجوع إلى نصوص العلماء والباحثين، وفهارس المخطوطات، وأهم نتيجة انتهت إليها الدراسة أن كتاب الوضع من المستبعد جدًّا أن يكون الشيخ أبو زكرياء يحيى بن الخير الجناوني هو من قام بتأليفه؛ وأنَّ مُؤلِّفَ كتاب الوضع عالـمٌ إباضيٌّ من جبل نفوسة بليبيا، عاش ما بين نهاية القرن السادس الهجري ونهاية القرن السابع الهجري
Keywords: Fiqh; Jannāwunī; Yaḥyā b. al-Khayr

Falaj Communities in Oman: A Case for Local Governance?: Ibāḍī Legal Rulings and Spatial and Ethnohistorical Observations - Bandyopadhyay, Soumyen; Mershen, Birgit (Journal of Material Cultures in the Muslim World, 2022)
This contribution studies the complex arrangement of legal, socio-economic, and technical aspects of the aflāj (s. falaj) water distribution and irrigation system, and how they have shaped communities and built environments in Oman, where the falaj has provided the virtual lifeline of oasis life since the first millennium BCE. Three case studies of falaj communities are presented, Birkat al-Mawz, al-Ḥamrāʾ, and Misfāt al-ʿAbrīyin, which developed during the prosperous early-Yaʿrubi period in the mid-eleventh/seventeenth century. It investigates the extent to which the Ibāḍī-Islamic legal framework allowed flexibility for the local governance, management, and organisation of this ancient system, and its adaptation to diverse demographic, environmental, and emergent socio-political conditions.
Keywords: Irrigation – Oman

The making of Islamic reform (iṣlāḥ) in Colonial Algeria (1882–1938): Ibadi scholars, French officials and the conceptual foundations of modern Islamic studies - Jomier, Augustin (Die Welt des Islams, 2022)
Among the conceptual foundations on which scholars of modern Islam have built their narratives for decades, ideas such as “reform” and “reformism” have been singled out for charges of Eurocentricism and Orientalism. At the same time, research on early modern Islam leads us to question the specificities of these nineteenth and twentieth-century concepts. Building on this scholarship, this article examines the case of Algerian Ibadi reform (iṣlāḥ) in order to reassert the specificity of the early twentieth century as a moment when Islamic concepts acquired new meanings, but also as a moment of deep entanglements between Islamic and colonial knowledge production. It shows that a systematic understanding of iṣlāḥ as social and religious reform linked to the idea of progress developed only during the interwar period. It also demonstrates that the emic and etic uses of iṣlāḥ and “reform” developed together, a result of the confluence between modern Islamic scholarship and scholarship about Islam in the early twentieth-century Algerian colonial public sphere. Thus, the conceptual history of iṣlāḥ warns us against approaches that consider emic and etic categories bounded entities and invites us instead to unravel their complexities.

Cyrille Aillet, L’ibadisme dans les sociétés de l’Islam médiéval. Modèles et interactions - Rebstock, Ulrich (Die Welt des Islams, 2022)
Keywords: Recension

Institut français d'islamologie : comment étudier scientifiquement l'Islam aujourd'hui ? - Laurentin, Emmanuel (Radio France, 2022)
Annoncé en octobre 2020 par Emmanuel Macron, l'Institut français d'Islamologie a été inauguré ce mardi 22 novembre. Si réinvestir la religion musulmane par une démarche scientifique apparaît comme une initiative indispensable, celle-ci pourrait-elle faire évoluer l'approche de l’Islam en France ?
Section: Info
Keywords: Islamologie – France

Djerba, l’île du «vivre-ensemble», hôte du sommet de la Francophonie - Lartigue, Aurore (RFI, 2022)
L'île touristique de Djerba, au sud de la Tunisie, accueille le sommet de la Francophonie à partir de ce samedi 19 novembre. Au-delà des raisons pragmatiques de ce choix, l'événement est l’occasion de…
Section: monde
Keywords: Francophonie – Djerba

Exode massif des jeunes Tunisiens : Village dépeuplé à Djerba - Ben Nacer, Teycir (Nawaat, 2022)
Alors que les refoulements s’intensifient en Serbie, des milliers de jeunes Tunisiens rêvant d’Europe, continuent de tenter leur chance par la route des Balkans. « Je peux compter sur les doigts d’une main ceux qui sont restés », regrette un sexagénaire, dans un petit village au centre de Djerba. Reportage.
Keywords: Emigration – Djerba – Europe – 2000-....

Reportage. À Djerba, l’émigration fait le vide - Ben Nacer, Teycir (Courrier international, 2022)
En Tunisie, le rêve migratoire est ancré dans les esprits. Sur l’île de Djerba, ce sont des villages entiers qui sont vidés de leur jeunesse, sans espoir et att...
Keywords: Emigration – Djerba – France

مركز ذاكرة عُمان ⁦ sur Twitter (Twitter, 2022)
“في زيارتهم لمركز ذاكرة عمان، الاستاذ سليمان بن عمر تونسي، من المكتبة الوطنية الفرنسي، ورئيس إيباديكا بباريس، والأستاذ سفيان مستاوي مدير معهد إيباديكا، والشيخ ساسي بن يحياتن الجربي من بلجيكا”

‏سليمان باشا الباروني لجهودها الإصلاحية في عمان خلال الفترة 1343-1359هـ/1924-1940م - الصقري, سعيد (هيئة الوثائق والمحفوظات الوطنية, 2022)
Don (Mascate, novembre 2022)
Keywords: Bārūnī; Sulaymān al- (1870-1940)

‏نظام انتقال الحكم ونهضة عمان الحديثة المتجدده دراسة تحليلية - الضوياني, حمد بن محمد بن ضويحي بن خلفان (هيئة الوثائق والمحفوظات الوطنية, 2022)
Don (Mascate, novembre 2022)

La situation de l’ibadisme et des ibadites en Libye post-Kadhafi - Mazek, Ayoub (Qawami, 2022)
La Libye est un État musulman sunnite et connu historiquement pour suivre le rite malikite. Toutefois, il existe en Libye une autre école juridique musulmane appelée l’école ibadite. Cette école juridique (d’après certaines sources ibadites) se répand en Libye depuis le début du deuxième siècl...
Keywords: Ibadisme – Djebel Nefousa

Parlez-nous de… l’ibadisme : histoire d’un islam méconnu - Aillet, Cyrille (Ecole normale supérieure de Lyon, 2022)
En dehors du sunnisme et du chiisme, on connaît rarement l’existence d’une autre branche de l’islam, dont l’ibadisme constitue désormais le seul témoignage vivant. Cette école religieuse, présente à Oman et au Maghreb, est aujourd’hui très minoritaire, mais ses bibliothèques conservent un patrimoine aussi riche que méconnu. En effet, à l’époque médiévale les ibadites ont eu un rôle actif dans ces régions, notamment au Maghreb où ils se sont puissamment implantés parmi les Berbères. En lutte contre l’autorité centrale du califat, ils y ont fondé l’un des premiers États autonomes, à Tahert en Algérie, avant de contribuer à la diffusion de l’islam jusqu’en Afrique grâce au développement du commerce transsaharien. Cependant, l’ibadisme se démarque avant tout par sa vision singulière du pouvoir politique : hostile à la théorie sunnite du califat, il cultive l’idéal d’un pouvoir élu, révocable et collégial. Un islam démocratique ? L’examen des sources nous en dira plus. Rencontre avec Cyrille Aillet, professeur à l'université Lumière Lyon 2, CIHAM (UMR 5648) Animée par Frédéric Abécassis, maître de conférences en histoire moderne à l'ENS de Lyon et membre du LARHRA (UMR 5190) Autour de l'ouvrageL’archipel ibadite : une histoire des marges du Maghreb médiéval
Keywords: Ibadisme – thèmes et motifs

L’ancrage territorial de l’intelligence économique : Développement et expérimentation d’un outil d’aide à la décision – Cas de la commune Houmet Essouk Djerba Tunisie - Mizen, Farah; Henchiri, Sarra (Alternatives Managériales Economiques, 2022)
Les territoires deviennent des « décideurs à part entière » suite à la décentralisation et la mise en place de la gouvernance locale. Ce qui pousse les territoires à veiller à l’efficacité des décisions à travers un minimum de performances leur permettant de s’offrir un pouvoir concurrentiel dans un monde changeant. C’est dans l’exploitation des informations offerts par l’Intelligence économique que les territoires doivent s’investir pour bâtir des systèmes d’intelligence territoriale permettant de subvenir aux exigences de l’optimalité des décisions. Nous essayons de revenir théoriquement sur les notions de l’intelligence économique et territoriale ensuite nous proposons une architecture du système d’intelligence territoriale dédiée au territoire objet de l’étude et portant sur le thème de prise de décision, ce système est conçu par capitalisation de l’expérience des parties prenantes portant sur l’évaluation des projets débouchant sur la formulation d’une grille d’évaluation et une cartographie mettant en relief leurs intérêts. Nous procédons enfin à un essai pratique de l’outil proposé afin d’expérimenter sa validité pratique. Notre travail a permis l’obtention d’un modèle d’évaluation utile avant ou après réalisation des projets compte tenu des principes de la bonne gouvernance auxquels les acteurs territoriaux se sont mis en accord.
Number: 4
Keywords: Développement local – Djerba

Entre lignée savante et lignée militante : la construction d’une mémoire des origines dans l’ibadisme médiéval omanais - Baptiste, Enki (2022)

Décryptage. À Oman, une tolérance de façade (Courrier international, 2022)
Les femmes, les homosexuels et les athées sont dans le collimateur des autorités et du grand mufti, qui prêchent uniquement la modération intermusulmane, entre ibadites et sunnites, explique ce mensuel spécialisé sur les questions de citoyenneté et de libertés dans le Golfe et le monde arabe.
Section: Société
Keywords: Tolérance religieuse – Oman

الواجهة الدينية لعمان.. السلام الطائفي وإرهاب السلطة على لسان المفتي (مواطن, 2022)
تحتل عمان المرتبة الأولى بين دول الخليج في تمثيل الأقليات، حسب مؤشر المشاركة السياسية في الخليج الصادر عن مركز البيت
Section: قصصنا
Keywords: Tolérance religieuse – Oman

The echoes of fitna: accumulated meaning and performative historiography in the first Muslim civil war - Hagler, Aaron M. (Brill, 2022)
"In The Echoes of Fitna, Aaron M. Hagler engages in a close reading of the fitna narratives of three related texts: al-Tabari's Tarikh al-rusul wa-l-muluk, Ibn al-Athir's al-Kamil fi al-tarikh, and Ibn Kathir's Kitab al-bidaya wa-l-nihaya. Because the latter two texts' presentations of the fitna follow al-Tabari's so closely, moments of divergence in the texts are understood as clear markers of the later historians' goals, perspectives, and literary-narrative strategies. The analysis of these changes demonstrates that the desire to reframe the meaning of Karbala is central to Ibn al-Athir's and Ibn Kathir's narrative construction, and that-while they left al-Tabari's versions of key events intact-small, even minute changes to contextual expository moments fundamentally change their meaning"
Keywords: Fitnah

Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019 - Ritter, Stefan; Ben Tahar, Sami (Reichert, 2022)
Dans l'Antiquité, Meninx était le chef-lieu de l'île de Djerba qui a donné son nom à l'île. Cette vaste ville portuaire, située dans un golfe protégé, était l'un des plus importants centres de production de pourpre en Méditerranée et devint l'une des plus grandes métropoles d'Afrique du Nord romaine. En 2015, un projet de recherche archéologique a été initié en coopération entre l'Institut d'archéologie classique de l'Université de Munich et l'Institut national du patrimoine, Tunisie, afin d'explorer le développement urbain de ce site antique jusqu'alors peu connu. Dans un premier temps, une prospection géophysique à grande échelle a permis de clarifier la structure du site urbain. Lors de deux campagnes de recherche sur le terrain en 2017 et 2018, des fouilles ciblées ont été menées, qui ont permis, grâce à leur riche matériel, de jeter un regard exemplaire sur différents domaines de la vie urbaine à toutes les périodes de l'histoire de l'habitat, de l'époque punique à l'Antiquité tardive (IVe siècle av. J.-C. à VIIe siècle après J.-C.). De plus, des recherches archéologiques sous-marines ont permis d'obtenir pour la première fois des informations sur les installations portuaires de Meninx. Le présent ouvrage propose une synthèse des multiples résultats de ces recherches. Il en ressort que Méninx, avec ses contacts économiques régionaux et suprarégionaux, jouait un rôle central pour l'île, qui faisait office de carrefour entre les réseaux commerciaux maritimes méditerranéens et le continent tout proche, avec ses routes commerciales menant au Sahara. Dans son rôle de centre de production et de commerce, Meninx se distinguait nettement des autres métropoles côtières tripolitaines, Sabratha et Lepcis Magna, par le fait que la vie urbaine était entièrement centrée sur la mer et ses ressources.
Keywords: Archéologie – Djerba

Oman: Constitutionalism Unrealized - Said, Basma Mubarak (Al-Abhath, 2022)
This chapter analyzes the development of constitutionalism in Oman over three historic phases. It examines the establishment of the modern Omani state, and sheds light on the power struggle between the absolutist ruler, Sultan Saʿid bin Taimur al-Saʿid, and his reformist brother, Tariq bin Taimur al-Saʿid, the first serious attempt to introduce constitutionalism in Oman calling for limiting the Sultan’s power and transforming Oman into a constitutional monarchy. It details first how British authorities intervened as intermediaries in this power struggle, bolstering the Sultan’s powers and entrenching absolutist monarchy in Oman. The chapter then examines the events surrounding the late Sultan Qaboos’s issuance of the Basic Law – enacted during his twenty-sixth year in power – and situates it as a response to internal and external pressures within Oman and in the Gulf region in the mid-1990s. The chapter moves then to describe a movement for greater power-sharing emerging as part of Arab Spring-inspired protests in 2011 and describes some of the minor constitutional amendments enacted by Sultan Qaboos that year, which did little to alter the status quo. Finally, it examines the Sultan’s passing away in January 2020, the appointment of Sultan Haitham as successor, and his enactment of a new constitutional document intended to stabilize governance in Oman and devolve some authority to his inner circle, while largely avoiding a larger disruption of power dynamics.
Keywords: Vie politique – Oman – 1970-2020

The declaration of His Majesty Sultan Qaboos : Towards a Harmonous Human Community - Zdanowski, Jerzy; Ziaka, Angeliki (Georg Olms Verlag, 2022)
Keywords: Tolérance religieuse – Oman

Looking over the builders’ work: foreign architects, artisans, and marble at Meninx (Djerba) - Lipps, Johannes (Libyan Studies, 2022)
Throughout the second century AD, the civic centres of the wealthy coastal cities of Africa Proconsularis underwent deep-rooted changes. Up to this point local stone had been largely employed for their buildings, but from the Hadrianic period onwards there was an increasing use of marbles, which were imported with considerable efforts and at great expense. These marbles came primarily from Italy, Greece, and Asia Minor, and brought with them new architectural concepts, as well as architects and artisans who have been generally identified as ‘Italian’ and ‘Eastern’ in past scholarship. This article will examine a temple, a structure presumed to be a portico, and a basilica from the harbour city of Meninx, located in southern Djerba (Tunisia). The exceptionally good preservation of these buildings’ architectural components and the documentation produced during their on-site recording in 2017–18 allow for a detailed understanding of their original building processes. This will show how mobile the building industry of the Roman Empire was during the second century AD, which in turn challenges any attempts of an overly schematic territorial placement of architectural concepts, building traditions, and the provenance of the artisans themselves., إلقاء نظرة على أعمال البنائين : المهندسين المعماريين والحرفيين الأجانب والرخام في مننكس (جربة), يوهانس ليبس, خلال القرن الثاني الميلادي، خضعت المراكز المدنية للمدن الساحلية الغنية في أفريقيا بروكونسولاريس لتغييرات عميقة الجذور. وحتى تلك اللحظة، كان الحجر المحلي مستخدماً إلى حد كبير في مبانيها، ولكن منذ عصر هادريان وما بعده كان هناك استخدام متزايد للرخام، والذي تم استيراده بجهد وتكلفة كبيرين . جاءت هذه الكتل الرخامية بشكل أساسي من إيطاليا واليونان وآسيا الصغرى، وجلبت معها مفاهيم معمارية جديدة، بالإضافة إلى مهندسين معماريين وحرفيين تم تحديدهم في الدراسات السابقة عموماً على أنهم ”إيطاليون “ و ”شرقيون “. ستفحص هذه المقالة معبداً، ومعلم يُفترض أنه رواق، و باسيليكا من مدينة المرفأ مننكس الواقعة في جنوب جربة (تونس ). حيث سمح الحفظ الاستثنائي الجيد على المكونات المعمارية لهذه المباني والوثائق التي تم إنتاجها أثناء التوثيق في الموقع في 2017–2018 على فهم تفصيلي لعمليات البناء الأصلية. و سيوضح هذا كيف كانت صناعة البناء في الإمبراطورية الرومانية متحركة خلال القرن الثاني الميلادي، و التي بدورها تتحدى أي محاولات مفرطة لوضع اطار إقليمي تخطيطي لمفاهيم معمارية، وتقاليد بناء، و موطن الحرفيين أنفسهم .
Keywords: Archéologie – Djerba

Literary Kharijism and Ibadi Identity - Poole, Terron (2022)
In the world of Islamic terminologies “Khawarij” is truly one of the most infamous. Historically it denotes one of the most notorious factions to ever exist in all of Islamic history. And considering the way the term “Khawarij” (or “Khariji” in the singular) has been used, and how it is still in use today—in polemically charged and heresiographical writings—it only paints a picture of extremism, brutally, and deviance, such that most Muslims know only this contrived negative image. For modern Ibadis, Khawarij as an identity marker concerning their origins is highly disputable. And given the portrayal of the Kharijites in Muslim literature, it is completely understandable as to why they have chosen to distance themselves from such a label. But are what we deem to be characteristics of Kharijism, based on descriptors found in Islamic literature, historically sound? Or does the information for what we believe to be the intrinsic hallmark of Kharijite behavior, tell us more about the author's intentions rather than the historicity of Kharijism? And are allegations of Ibadis being from the Kharijites, or having a Kharijite origin, a gross lie used to slander members of that community. Or is there any truth to such a claim, and that the Ibadi attempt to disentangle themselves from the Kharijites is nothing more than a sleight of hands to say the least?
Keywords: Kharijisme

Early Ibāḍī Historiography: The Case of the Khawārij - Gaiser, Adam R.; Baptiste, Enki (2022)
Keywords: Kharijisme

Poet, Scholar, Khārijite? Navigating Rebellion with ʿImrān b. Ḥiṭṭān (d. 703 CE)’ - Hagemann, Hannah-Lena (2022)
Keywords: Kharijisme

We Did Not Pull Our Hand from Obedience”: The Rebellion of the jund against al-Faḍl ibn Rawḥ ibn Ḥātim al-Muhallabī (794 CE) - Dar, Alon (2022)
Keywords: Révoltes – Histoire

Ibn aṣ-Ṣaġīr: eine Chronik der Rustamiden - Ibn al-Ṣaġīr (Harrassowitz Verlag, 2022)
Don de l'auteur
Keywords: Dynastie rustumide

Introduction to Ibadi legal sources: pre-classical and classical period - Francesca, Ersilia (2022)
Keywords: Fiqh

Ibadi Theological sources - Ziaka, Angeliki (2022)

The Ibadi tafsir of Hūd b. Muḥakkam al-Hawwārī - Shah, Megan (2022)
Keywords: Coran – Commentaires – 9e siècle; Hawwārī; Hūd b. Muḥkim al-

Khalifah and the Concept of Mahdi in Ibāḍiyya and ahl as-sunna wa-l-ǧamāʿah - Shavarani, Masoud (2022)

Kitāb al-adillah wa-l-bayān and its Context - Alabbas, Belal (2022)

The Concept of al-rajāʾ in Ibāḍī Theology: A Cultural Bridge between Ibadism and Universal Hope - Morajevi, Mahdi (2022)

Purity and Impurity in the Qur'an: Terminology and Context - Zellentin, Holger (2022)

Évolution de l'habitat oasien à M’zab : de l'habitat vernaculaire aux nouveaux ksours (Ghardaia, Algérie) - Bouali-Messahel, Mounia; Guerrouche, Kheir-Eddine (2022)
L’habitat vernaculaire des ksour et des palmeraies a connu de profonds changements et la ville oasienne actuelle plusieurs étapes de croissances. Dans la vallée du M’Zab, au nord du Sahara algérien, une expérience originale a donné lieu à l’émergence d’une série de nouvelles extensions urbaines nommées « nouveaux ksour ». Quel est leur impact sur la protection de l’écosystème oasien, la valorisation du patrimoine matériel et immatériel de la région, et la préservation du mode de vie mozabite ?
Keywords: Urbanisme – Mzab

Consuls Honoraires (2022)
Par arrêté royal du 23 février 2022 : 1. Est établi un poste consulaire honoraire de Belgique à Djerba avec comme circonscription le gouvernorat de Médenine. 2. Monsieur Arbi DARDOUMI est nommé Consul honoraire de Belgique à Djerba pour une période de cinq ans.
SERVICE PUBLIC FEDERAL AFFAIRES ETRANGERE

Sultan Qaboos and modern Oman, 1970-2020 - Fromherz, Allen James; Salimi, Abdulrahman al- (Edinburgh University Press, 2022)
This is the first, timely account of the modern Oman over the entire reign of Sultan Qaboos (1970-2020). The book provides unique, wide-ranging interdisciplinary and international perspectives on modern Oman by specialists in a variety of fields from Oman, Europe and North America. Utilising a range of perspectives, all chapters connect to the theme of rebirth, of the connections between the past and the future pursued by Sultan Qaboos and his government in fields as diverse as health, religion, law, economy, heritage and diplomacy. Not overlooking the many challenges faced during Sultan Qaboos' reign and still faced by Oman, the book engages various theories and perspectives about Oman's economic, religious, educational and cultural transformations under Qaboos (d. 2020 CE)
Keywords: Vie politique – Oman – 1970-2020

Une anthropologie de la vie intellectuelle dans la péninsule Arabique : le cas du Sultanat d'Oman - Ayachi, Mehdi (2022)
Keywords: Vie intellectuelle – Oman

L’île de Djerba : crise territoriale et enjeux de gouvernance - Ben Jebara Boussaada, Sarra (2022)
Keywords: Urbanisme – Djerba

Love and distance geographies in Muscat, Oman - Breteau, Marion (2022)

Écrire et réécrire l’histoire des ibadites au Maghreb central - Lepinay, Zélie (2022)

البحث الصادق للبرادي - التيواجني, مهني بن عمر (2022)

تقديم عام لحومة جعبيرة - الفصيلي, فتحي (2022)

رسالة في علماء جربة للحيلاتي - القلاع, لزهر (2022)
Keywords: Prosopographie – Djerba

مستقبل الامازيغ في شمال افريقيا - الهمامي, بادية (2022)
Keywords: Berbérisme – Afrique du Nord

تجربة تدريب اللغة الامازيغية الجزائر نموذجا - قرادا, مهيب (2022)

واجباتنا نحو المؤلفات - مصلح, أحمد بن مهني (2022)

الصحافة والاعلام الامازيغي في المغرب الكبير ليبيا نموذجا - ولد الطاهر, نادية (2022)

رسالة الزواغي وقصيدته - بن حريز, ميلاد (2022)
Keywords: Poésie – Djerba

رسالة الحقائق للبرادي - بن عمر, عمر (2022)

Uṣūl al-Dīn (The Fundamentals of the Faith). By Tibghūrīn b. īsā al-Malshūṭī. Edited by 'Amr Khalifa Ennami and translated into English by Trevor Le Gassick - Gaiser, Adam R. (Journal of the American Oriental Society, 2022)
Keywords: Foi – Traité – 12e siècle; Malshūṭī; Tibghūrīn b. ʿĪsā al-; Recension

Hannah-Lena Hagemann: The Khārijites in Early Islamic Historical Tradition: Heroes and Villains. (Edinburgh Studies in Classical Islamic History and Culture.) xii, 328 pp. Edinburgh: Edinburgh University Press, 2021. £85. ISBN 978 1 4744 5088 1. - Kenney, Jeffrey T. (Bulletin of the School of Oriental and African Studies, 2022)
Keywords: Recension

Le mauvais prénom - Ben Abdallah, Oussama (Les Éditions du Panthéon, 2022)
Ce témoignage touchant est celui d’Oussama, jeune homme de 30 ans, qui a longtemps hésité avant de dévoiler ce portrait. Doté d’une force de caractère peu commune, ce fils d’un homme puissant va, sur un coup de tête, échapper en 2016 à l’emprise paternelle pour tracer sa route loin du cocon familial, à Paname. Oussama nous fait vivre sa descente aux enfers, sa confrontation à l’impuissance des institutions ainsi que sa difficile remontée pour devenir le maître de son destin avec l’intelligence et la culture comme seules armes. Les trois années les plus sombres de sa vie sont ici racontées, sans artifices. Dans cet autoportrait, qui aborde aussi bien l’amour que les sujets d’actualité, il nous amène au-delà des clichés habituels à la rencontre de la paix et de la liberté tant recherchées. Avec « Le Mauvais prénom », Oussama Ben Abdallah souhaite redonner foi en la vie et prouver que, malgré l’adversité, tout parcours bancal peut se transformer en réussite ! (4e de couv.)
Keywords: Emigration – Djerba – France

Mukhtār b. ʿAwf al-Azdī, Abū Ḥamza - Gaiser, Adam R. (Encyclopaedia of Islam, 2022)
Keywords: Biographies

al-Mazātī - Love Jr, Paul M. (Encyclopaedia of Islam, 2022)
Keywords: Biographies

Islam, réforme et colonisation: Une histoire de l’ibadisme en Algérie (1882–1962) - Chih, Rachida (The Journal of North African Studies, 2022)
_eprint: https://doi.org/10.1080/13629387.2022.2108250
Keywords: Recension

Circuit I: Le Sahara, refuge ibadite - Chérid, Houria; Lakhdar, Drias; Benouis, Farida (Une architecture de lumière : Les arts de l'Islam en Algérie, 2022)
Keywords: Architecture – Mzab

Ibadis - Gaiser, Adam R. (Routledge Handbook of Islamic Ritual and Practice, 2022)
Num Pages: 6

‏الحاج محمد بن سليمان قراس نموذج تربوي ودعوي وصورة من تحديات المجتمع المزابي بالمجهر - الشيخ صالح, أبو القاسم بن عمر (2022)

مواقف تربوية من سيرة الشيخ عبدالله بن إبراهيم التونسي - باعمارة, بكير بن سليمان (2022)

‏الشيخ محمد بن بابا الشيخ بالحاج ‏مربيا وفقيها - الشيخ بالحاج, عيسى بن محمد (2022)

الشيخ أحمد بن عمر اوبكة ومنهجه في الدعوة والافتاء والتاليف - باباواعمر, خضير بن بكير (2022)

‏أثر دراسة جهود الأعلام في تشيد القيم والخلفية وعلمية - الشيهاني, حمو بن عيسى (2022)

المرشدة عويشي بنت محمد بابكر ودورها في الإرشاد الديني والإصلاح الاجتماعي - مصباح, إبراهيم بن بنوح; بابكر, عبد الله بن بيوض (2022)
Keywords: Réformisme – Mzab

‏الدكتور عمر بن اسماعيل ال حكيم حياة في سبيل العلم - باباواعمر, خضير بن بكير (2022)
Keywords: Biographies – Mzab – 20e siècle

‏الكتابة التاريخية عند الشيخ صالح بن طالب عمر اسماوي - بحاز, إبراهيم بن بكير (2022)

‏جهود الشيخ إبراهيم بن محمد طلاي في خدمة التراث - كروم, أحمد بن حمو (2022)
Keywords: Ṭallāy; Ibrāhīm b. Muḥammad (1929-2021)

Ibadism in Arabia: Converging Faith and Practice - Terron Poole (2022)
Check out the article behind the discussion: The Development of an Ibadi Textual Tradition https://www.academia.edu/75743815/The... For more of Prof. Hoffman's work, please visit the links below: https://illinois.academia.edu/Valerie... https://religion.illinois.edu/directo... https://www.amazon.com/Valerie-J-Hoff...
Keywords: Ibadisme – Oman

Islam, réforme et colonisation: une histoire de l'ibadisme en Algérie, 1882–1962 by Augustin Jomier - Brower, Benjamin Claude (Arab Studies Journal, 2022)
Keywords: Recension

Succéder à l’imam dans l’ibadisme médiéval: sources de légitimité et contestation du modèle dynastique - Baptiste, Enki (2022)

ومن یبتغ غري الاسلام دينا - عومير, مولود (البصائر, 2022)

ملامح من الكتابة التاريخية الإباضية ببلاد المغرب ما بين القرنين (3 -10هـ/ 9-16م) - الزرويل, صالح; بحاز, إبراهيم بن بكير (مجلة المعارف للبحوث والدراسات التاريخية, 2022)
أولى مؤرخو الإباضية في بلاد المغرب، اهتماما جليا بالتدوين التاريخي، والذي عرف تطورا ملحوظا منذ القرن الأول الهجري السابع للميلاد، وقد احتضنته مختلف حواضره التي صارت بمثابة مدارس تاريخية قائمة بذاتها، تميزها عن غيرها، بدءا بمدرسة نفوسة، وانتهاء بمدرسة ورجلان، ونروم من خلال هذا المقال التعرف على أهمّ المؤرخين الإباضيين المغاربة، ومؤلفاتهم ومنهجهم وأسلوب كتاباتهم التاريخية، بدءا بالشيخ ابن سلام في القرن 2ه/8م، وإلى غاية الشيخ أبي العباس الشماخي في القرن 10ه/16م، إذ لم يبق التأليف التاريخي حبيس المشرق فحسب، بل سالت أقلام المغاربة تدوينا ونسخا، وتدريسا له. تميّزت الكتابة التاريخية لدى المؤرخين الإباضيين عن أقرانهم المغاربة من حيث الأسلوب والمنهج، وحتى في توجهاتهم وأفكارهم وميولاتهم، فقد جمعوا في مؤلفاتهم السيرية بين شتى أصناف العلوم النقلية، وانتقلوا من التقليد إلى التجديد، تقليد طريقة المحدّثين، وتجديد على طريقة السير والسنين. وهذا الانتقال قد ظهر جليا بعد الزحف الهلالي في القرن5ه/11م. Ibadi historiens in the maghreb have given a clear interest in historical codification ,which has known a remarkable development since the seventh century AH, and has been embraced by the various metropolitan areas that have become independent historical schools, distinguishing them from others, starting with the Nafusa school, and ending with a school and two men, and we are through This article introduces the most important Moroccan Ibadhi historians, their approach and the style of their historical writings, starting with Sheikh Ibn Salam in the 2nd century AH/8 AD, and ending with Sheikh Abi Al-Abbas Shammakhi in the 10th AH / 16th century AD. He copied, and taught him. The historiography of Ibadi historians was distinguished from their Moroccan peers in terms of style and approach, and even in their orientations, ideas and inclinations. This transition has been evident after the crescent crawl in the 5th / 11th century AD

Al-Salimi, Abdulrahman: On the Reception of Early Ibadi Theology. A Commentary on the Book on Monotheism by ‘Abd Allāh b. Yazīd al-Fazārī (2nd/8th Century). - Metzler, Berenike (Orientalistische Literaturzeitung, 2022)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Recension

حواضر وادي مزاب عبر التاريخ - طاعة, مصطفى (مجلة المواقف, 2022)

Quelques remarques sur la diffusion du minaret-escalier et son lien avec les ibadites - Prevost, Virginie (Connected Stories: Contacts, Traditions and Transmissions in Premodern Mediterranean Islam, 2022)
Keywords: Archéologie – Djerba

Quand les musulmans et les juifs chantent le patrimoine liturgique de Djerba - Ghrab, Mohamed (2022)
Keywords: Judaïsme – Djerba

La synagogue Pariente à Houmt Souk - Achouch, Ishak (2022)
Keywords: Judaïsme – Djerba

L'église catholique Saint Joseph - Lando, Matteo (2022)
Keywords: Christianisme – Djerba

L'église grecque Saint-Nicolas et cimetière des étrangers de Djerba - Elouati, Mehdi (2022)
Keywords: Emigration – Grèce – Djerba

من تقالد نساخة المخطوطات وتاريخ مجموعة جامع الترك بجربة: مقارنة كوديكولوجية وبينية - السلامي, صدق (2022)
Keywords: Manuscrits – Djerba

دراسة تحليلية مقارنة لأوراق المخطوط المتفرقة في خزانة مهني الباروني - الباروني, سناء مهني (2022)
Keywords: Manuscrits – Djerba

المخطوط الإباضي في مكتبتي العائلية البارونية بجربة - تغلات, زهير (2022)
Keywords: Bibliothèques – Djerba

انتقال مخطوط عدد ARA 911 للمكتبة الجامعية للغات والحضارات بباريس (BULAC) من ملك سالم بالحاج يحيى الباسي إلى سليمان الحرايري سنة 1845 - عبد الجواد, المهدي (2022)
Keywords: Manuscrits – Paris

واقع الكتاب المخطوط ورهاناته: مخطوطات خزائن للمدن التاريخية أنموذجا - بن يوسف, زهير (2022)

ملح المخطوطات وطرئف النساخ من خلال مجموعات المخطوطات العائلية بجزيرة جربة - البوجديدي, علي (2022)
Keywords: Manuscrits – Djerba

نحو قاعدة بينات وطنية للمخطوطات العائلية بتونس - غراب, أنس (2022)
Keywords: Manuscrits

مخطوطات المكتبة الآحمدية بدار الكتب الوطنية بتونس - السمين, رشيدة (2022)
Keywords: Manuscrits – Tunis

Quand les musulmans et les juifs chantaient le patrimoine liturgique de Djerba - Davis, Ruth Frances (2022)
Keywords: Judaïsme – Djerba

Témoignage sur la musique juive à djerba en 1978 - Davis, Ruth Frances (2022)
Keywords: Judaïsme – Djerba; Musique – Djerba

Une mémoire sicilienne dans l'île de Djerba - Ciscardi, Jean-Jacques (2022)
Keywords: Emigration – Sicile – Djerba

Permanence de la littérature judéo-arabe en Tunisie : les bulletins hebdomadaires de la communauté juive de Djerba - Taïeb, Yohann (2022)
Keywords: Judaïsme – Djerba

Le patrimoine immatériel des Juifs de Djerba - Hammi, Yosr (2022)
Keywords: Judaïsme – Djerba

Les traces de la présence grecque à Djerba - Elouati, Mehdi (2022)
Keywords: Emigration – Grèce – Djerba

L'ibadhisme à Djerba - Merimi, Mohamed (2022)
Keywords: Ibadisme – Djerba

جهود الشيخ سليمان الباروني في الفترة ما بين 1906-1940م - أيمليكة, حمو أبو الصديق; زندوح, منير محمد خليفة (2022)
Keywords: Bārūnī; Sulaymān al- (1870-1940)

حركة المقاومة الوطنية فى مدينة زوارة وما حولها ضد الاستعمار الإيطالى فى الفترة ما بين 1911-1913م - قري, ذهبية عاشور (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

سليمان عبد الله البارونى (1870-1940م) عضو مجلس المبعوثات العثماني عن ولاية طرابلس الغرب من خلال بعض الوثائق - الدويبي, خليفة محمد; نوارى, دلال (2022)
Keywords: Bārūnī; Sulaymān al- (1870-1940)

رحلات سليمان باشا البارونى بين المحن والمنح تأملات فى مراسلاته مع الشيخ إبراهيم أبو اليقظان - حاج أمحمد, يحيى بن بهون (2022)
Keywords: Bārūnī; Sulaymān al- (1870-1940)

دور جبل نفوسة وزوارة في الجهاد ضد المستعمر - جادالله, كريمة محمد; قدير, سعد إدريس (2022)
Keywords: Relations – Djebel Nefousa – Zouara

عمرو بن عيسى الثنذميرتي حياته وملامح من شعره - ساسي, محمد رمضان (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

رمزية التجريد في الشعر الشعبي قصيدة الدكتور عمرو خليفة النامي رحمه الله العصفور التائه أنموذجا . دراسة وصفيه تحليلية - جبران, رضا محمد (2022)
Keywords: Ennami; Amr (1939-198X); Poésie – Djebel Nefousa; Vie intellectuelle – Djebel Nefousa

معجم الغزل عند زجالى حاضرة زوارة فى ضوء الحقول الدلالية زايد صمامة أنموذجا - غزالة, عبد الجليل ابو بكر (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

جهود المرآة النفوسية في التعليم والدعوة بين القرنين الثاني والرابع الهجريين - المقدمي, نادية عيسى خليفة (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

الحضور النفوس بوادى الجريد وإسهاماته (آل التيميجارى نموذجا) - الدبلي, صلاح مسعود (2022)
Keywords: Relations – Djebel Nefousa – Djerid

الحياة الاقتصادية بجبل نفوسة من خلال كتاب السير للشماخي ت 928هـ/1522م) - سميو, علي محمد (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

المذهب الاباضي وبعض علمائه - الزريقي, جمعة محمود (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

الحياة السياسية لعامة جبل نفوسة (من خلال كتاب السير للشماخي ت: 92هـ/1522م) - زايد, أسماء موسى علي (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

الدكتور عمر النامي وجهوده الدعوية - الخذراوي, عبد العاطي أبو العيد (2022)
Keywords: Ennami; Amr (1939-198X)

(سير وتراجم) بعض علماء نالوت في العهدين التركي والإيطالي - مزيدة, عيسى سعيد (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

اضاءات على فكر و إبداع الشيخ على يحيي معمر من خلال كتابيه (الهة من الحلوى والفتاة الليبية ومشاكل الحياة - اوشن, زهرة (2022)
Keywords: Muʿammar; Ali Yahya (19XX-1984); Vie intellectuelle – Djebel Nefousa

السيرة الذاتية لعلماء نفوسة: الشيخ العمروس نموذجا - برقيق, سالمة عمر (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

نظرة إلى التراث التعريف بأبي سهل اللآلوتي دراسة وتحقيق - الخمائسي, أحمد سالم (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

أعلام جبل نفوسة عمروس بن فتح النفوسي المساكني ت283-896م - عتيق, سميرة سالم أحمد (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

مشاهير علماء جبل نفوسة وزوارة "سير وتراجم" - الكوشلي, مسعود (2022)
Keywords: Vie intellectuelle – Djebel Nefousa; Vie intellectuelle – Zouara

المنهج الاجتهادي للجناوني : كتاب الوضع أنموذجا - بنعمر, عمر بن صالح (2022)
Keywords: Fiqh – Libye; Ijtihad – Djebel Nefousa

الآراء التربوية للشيخ على يحيى معمر من خلال كتاب سامر أسرة مسلمة - بورقيبة, فاطمة بنت صالح (2022)
Keywords: Muʿammar; Ali Yahya (19XX-1984); Vie intellectuelle – Djebel Nefousa

رحلات بعض علماء نفوسة إلى البلدان المجاورة وأثرها في توجيه الحركة العلمية بالمغرب الكبير - كروم, أحمد بن حمو (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

جهود البدر الشماخى فى خدمة السنة وعلومها - جودة, أحمد حسين; السيابي, حاتم بن رشيد (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

الحضور النفوس فى خزائن مخطوطات وادي مزاب - الجزائر - حاج أمحمد, عيسى (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

الشيخ مقرين بن محمد البغطوري النفوسي (حي في 599هـ/1202م) - سيرة ومسيرة - - الزرويل, صالح (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

شهادة جبل نفوس على العصر (في المدونة الاستعراضية) - قرفال, نجاة الطاهر (2022)
Keywords: Orientalisme – France

ملامح العلاقة بين نفوسة ومزاب فى القرن 10هـ/16م من خلال رسالتين مصدريتين - تقديم وتعليق - - امعيز الحاج أحمد, باحمد بن داود (2022)
Keywords: Relations – Djebel Nefousa – Mzab

القاضى عمروس بن فتح المساكنى ودوره فى إنقاذ المذهب الإباضي من الاندثار - بوصيقع, سامية (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

النشاط العلمى والدعوى لعلماء نفوسة فى المجال المغاربي والأفريقى - مزهودي, مسعود (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

ملامح الدور الإصلاحي لعلماء جبل نفوسة فى المجتمع النفوس الحياة الاجتماعية نموذجا - الشريف, شريفة عبدالرزاق محمد (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

رحلة بعض علماء الجبل وزوارة للمدن والبلدان المجاورة خلال العصر العباس وحتى انتقال الدولة الفاطمية إلى مصر (361-140هـ/758-971م) - حدود, منى علی (2022)
Keywords: Emigration – Djebel Nefousa – Egypte; Vie intellectuelle – Djebel Nefousa

الرحلات واللقاءات العلمية بين علماء عمان وعلماء جبل نفوسة - الندابي, ناصر بن علي (2022)
Keywords: Relations – Djebel Nefousa – Oman

خلف علماء جبل نفوسة (اتصال وتواصل) - العزابى, مسعود عيسى (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

مصطلحات حديثية من خلال كتاب العدل ومختصره وشرحه دراسة استقرائية تحليلية للمصطلحات الحديثية عند العلامة الشماخى - الكندي, أحمد بن يحيى بن أحمد (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

العلاقة العلمية بين علماء الجبل وغيرهم علاقات الشيخ عبد الله بن يحيى الباروني نموذجا - مصلح, أحمد بن مهني (2022)
Keywords: Vie intellectuelle – Djebel Nefousa

نظرية المعرفة، والتعارف والاعتراف عند الشيخ على يحي معمر - تفوشيت, خالد سعيد (2022)
Keywords: Muʿammar; Ali Yahya (19XX-1984)

آراء عبد اللّه بن يزيد الفزاري الكلامية - الصخراوي, فوزي (دار المسيرة, 2022)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

الإباضية المستاوية إلى القرن السادس الهجري - الصخراوي, فوزي (دار المسيرة, 2022)
Keywords: Nukkarisme

Ibadi Muslim schools in post-revolutionary Zanzibar - Wortmann, Kimberly T. (Africa, 2022)
Cet article examine comment les écoles de la diaspora ibadite omanaise ont eu un impact sur l’éducation religieuse et les relations afro-arabes dans le Zanzibar post-révolutionnaire. L’essentiel de la littérature existante consacrée à l’ibadisme et à la diaspora omanaise à Zanzibar est axé sur l’histoire économique de l’île, sur les histoires des élites arabes sous le sultanat et sur la politique de la révolution de 1964. Peu de travaux explorent comment les ibadites à Zanzibar aujourd’hui se distinguent d’autres musulmans en se mariant au sein de la communauté omanaise, en servant de leaders d’Istiqama, en portant des vêtements omanais, en fréquentant des mosquées ibadites et en inscrivant leurs enfants dans des écoles ibadites. Cette étude offre une nouvelle perspective sur l’ibadisme et les relations entre Oman et Zanzibar sous le néolibéralisme à travers les expériences vécues d’ibadites et non-ibadites affiliés aux écoles de la communauté musulmane Istiqama.
Keywords: Zanzibar

تاريخ التجارة بجربة - عمامو, عبد الستار (2022)
بمقار الجمعية القرآنية

Ismail Albayrak, Approaches to Ibāḍī Exegetical Tradition - Baptiste, Enki (Bulletin critique des Annales islamologiques, 2022)
Ismail Albayrak is Professor at the Australian Catholic University in Melbourne. He has been studying Islamic theology and exegesis for two decades. This present book deals with the little-known field of Ibadi studies. Scholars are increasingly beginning to appreciate Ibadi materials as these sources offer new perspectives to understand the formative period of Islam. The texts produced by the communities either in North Africa or in Arabian Peninsula are better known and most of them are now ...
Number: 36
Keywords: Recension

دراسة مصادر الإمام الربيع في الفقه الإسلامي في ضوء الموسوعات الشرعية العمانية - السامرائي, عبد الغفور اغام عبد الغفور (2022)

مصادر الإمام الربيع بن حبيب في الفقه الإسلامي - الهنائي, أيوب بن سالم بن خليفة (2022)

الفلسفة المقاصدية في بناء الأمة الإسامية من خلال فقه الأحوال الشخصسة: كتاب الضياء للعوتبي أنموذجا - الصادق, ياسين بن أحمد (2022)

مجلس القضاء في عمان من خلال كتاب المصنف للشيخ أحمد بن عبد الله الكندي (ت:٥٥٧ه/ ١١٦٢م) خلال القرون الثاثة الهجرية الأولى - الخاطرية, خلود بنت حمدان; العلوي, بدر بن هلال (2022)

الأهمية التاريخية والحضارية موسوعة "فواكه العلوم في طاعة الحي القيوم" ق11هـ/17م - البراشدي, موسى بن سالم (2022)

علم الدعوة من خلال مباحث العقيدة والدعوة في الموسوعات الشرعية العمانية - شولح, امرسي محمود إبراهيم (2022)

أدلة وجود الله عند الإمام العوتبي من خلال كتابه الضياء - الخزيري, قيس بن خليفة بن عبد الله (2022)

منهج الرد على المخالفين في الفكر العقدي الإباضي (منهج الطالبين للشقصي أنموذجً) - القاسمية, نجية بنت عامر بن حمدان (2022)

غريب ألفاظ الحديث والأثر من خلال كتاب المصنف للعلامة أبي بكر الكندي: دراسة وتحليل - الكندي, أحمد بن يحيى بن أحمد; الجهوري, راشد بن حميد; المنصوري, المبروك الشيباني (2022)

آراء الشيخ الشقصي في علم الحديث ومصطلحه موسوعة منهج الطالبين أنموذجا - السيابي, حاتم بن رشيد (2022)

صورة الهند والصين من خلال مصنف الضياء للعوتبي - البرطمانية, مريم بنت سعيد (2022)

دور قواعد البيانات في تصنيف وفهرسة الموسوعات الشرعية العمانية: كتاب منهج الطالبين وبلاغ الراغبين - النيل, حسن عبد الله; المجاهد, محمد سعيد (2022)

الصناعة الحديثية في كتاب قاموس الشريعة للعامة جميل بن خميس السعدي - البوسعيدي, صالح بن أحمد; ابوحماد, زياد عواد; المنصوري, المبروك الشيباني (2022)

مشكل القرآن عند العوتبي في موسوعته الضياء - أسعد, علي محمد; الصوافي, سعيد بن راشد (2022)

القراءات القرآنية وتوجيهها عند العوتبي في موسوعته )كتابه الضياء( - الصوافي, سعيد بن راشد; أسعد, علي محمد (2022)

الاستدلال العقلي عند العوتبي من خلال كتابه الضياء: الإلهيات أنموذجا - الراشدية, كريمة بنت علي بن سعيد (2022)

جهود المحقق الشيخ سعيد بن خلفان الخليلي (ت1287هـ) في القراءات والتجويد من خلال موسوعة تمهيد قواعد الإيمان - الهنائي, عبد الله بن سالم بن حمد (2022)

علم الناسخ والمنسوخ في الموسوعات الشرعية العمانية سلاسل الذهب في الأصول والفروع والأدب أنموذجا - الرواحي, سعيد بن أحمد بن سيف (2022)

تعامل الإمام العوتبي مع الحديث النبوي الشريف في كتابه الضياء، دراسة نماذج - تمزغين, محمد (2022)

كتاب مكنون الخزائن وعيون المعادن ومصادره - الهاشمي, سعيد بن محمد (2022)

القواعد الأصولية في كتاب الضياء للعوتبي - الغماري, إبراهيم بن راشد بن سيف (2022)

كتاب )شفاء القلوب من داء الكروب للشيخ خمبس بن راشد العبري( وعاقته باموسوعات العمانية - العبري, سعيد بن عبد الله (2022)

جهود الشيخ يحيى بن خلفان الخروصي في نشر كتاب (قاموس الشريعة للعامة جميل السعدي) وحفظه وطباعته - الخروصي, خالد بن عبد الله (2022)

القواعد الفقهية في موسوعة قاموس الشريعة باب الأحوال الشخصية« دراسة استقرائية تطبيقية« - السعدي, طالب بن علي (2022)

Chronologie indicative : de Magan à la Nahda - Maguer-Gillon, Sterenn le; Sebiane, Maho (Arabian Humanities, 2022)
IIIe millénaire av. J.-C. Ca. 3100 – 2700 av. J.-C. Culture de Hafit. Ca. 2700 – 2000 av. J.-C. Culture d’Umm an-Nar. Ca. 2400 av. J.-C. Le pays de Magan, identifié comme Oman, apparaît dans les textes cunéiformes sumériens. Commerce du cuivre, du bois et de la diorite. Échanges entre l’Inde et la Mésopotamie. Ca. 2000 – 1300 av. J.-C. Culture de Wādī Sūq. IIe millénaire av. J.-C. Ca. 1200 av. J.-C. Site de Salut. IIIe siècle av. J.-C. Fondation du port de Sumhuram, dans le Dhofar, comptoir ...
Number: 15
Keywords: Oman – Histoire

“To Everyone Who Told Zanzis That They Are Not Omani”: Young Swahili-speaking Omanis’ Belonging in Postdiaspora Oman - Fay, Franziska (Arabian Humanities, 2022)
In this article, I explore some of the contemporary forms of expression that young Swahili-speakers below the age of 35 turn to in Oman to make claims to Omani citizenship and belonging. Building on long-standing discussions of Zanzibari-Omani identity, I discuss how second and third generation Zanzibari-Omanis of mixed backgrounds negotiate a sense of being both ‘Swahili’ and ‘Arab’ as part of their broader understandings of what it means to be Omani. I propose that foregrounding young Swahili-speaking Omani people’s modes of blending belongings can contribute to conversations on what it means to be ‘young’, ‘Omani’, ‘Swahili-speaking’ and a second or third generation postdiasporan. The article builds on exploratory fieldwork conducted in Oman in 2018 and 2019. It examines young people’s creative expressions through digital social media and against the backdrop of the Oman Vision 2040. These additional sources shed further light on some of the meanings of being a young Swahili-speaker in present-day Oman.
Keywords: Emigration – Zanzibar – Oman

De l’exil à l’appareil d’État : trajectoires élitaires des « pionniers » de la modernité littéraire omanaise - Ayachi, Mehdi (Arabian Humanities, 2022)
La modernité littéraire et intellectuelle omanaise débute bien avant la nahḍa du sultan Qabous b. Said (r. 1970-2020), dont il s’agit de réévaluer la pertinence pour une histoire intellectuelle du Sultanat d’Oman. C’est plutôt sous le règne de Sa‘îd b. Taymûr (r. 1932-1970) que s’amorcent des changements – dans les pratiques d’écriture et les sociabilités littéraires – à l’origine de l’émergence de cette nouvelle figure de la modernité qu’est l’intellectuel (al-muthaqaf). On se propose ici d’étudier quelques moments-clés de la trajectoire historique de l’élite éduquée sous Sa‘îd, depuis son exil dans les pays voisins du Golfe et du Machrek à la recherche de nouvelles opportunités éducatives et professionnelles jusqu’à son retour et son intégration à l’État en 1970, à l’appel du sultan Qabous. On posera ainsi la question de la place des intellectuels au sein de cette élite éduquée et de leur rôle dans l’élaboration de projets nationalistes qui en font le seul groupe capable de renverser le sultan et de gouverner le pays. L’histoire de cette génération, dont les membres sont parfois qualifiés de « pionniers » (rawâd) de la modernité littéraire omanaise, mettra ainsi en lumière l’insertion précoce d’Oman dans le moment panarabe et anticolonialiste des décennies 1950-1960.
Number: 15
Keywords: Littérature – Oman

Baloch Mashkat (Muscat) and the Sultan Qaboos Era: Cultural Performance, Cosmopolitanism, and Translocal Consciousness - Murer, George (Arabian Humanities, 2022)
Baloch cultural life in Muscat is a vivid part of Oman's national landscape as it has evolved from the time the late Sultan Qaboos took power. Although often typecast as soldiers or police officers, Omani Baloch are deeply integrated into a broad spectrum of professions and social milieus. These include communities of arts and letters at the heart of the Omani cultural renaissance championed by the late Sultan and embodied in institutions such as Royal Opera House, the Muscat International Film Festival, and the Oud Hobbyists Association. The many nuances to Baloch identity have led to a plurality of social spaces, from literary forums intertwined with South Asian intellectual spheres to ceremonial contexts in which Omanis of Baloch, Peninsular Arab, and East African heritage converge. Networks of patronage and transnational circulations of songs and poetry among Baloch attest to the longevity of Western Indian Ocean circuits of cultural exchange.
Number: 15
Keywords: Vie politique – Oman – 1970-2020

Jouer du sorûd en Oman dans le cadre cérémoniel du damâl, parcours d'un musicien baloutche à Mascate - Mascagni, Romain (Arabian Humanities, 2022)
Les Baloutches vivent de part et d’autre de la frontière entre l’Iran et le Pakistan. Ils sont cependant présents au Sultanat d'Oman depuis plusieurs siècles. Certains éléments historiques seront présentés pour comprendre comment ils sont actuellement répartis à Mascate. Nous nous intéresserons principalement à une pratique musicale baloutche courante dans cette ville. À travers le parcours d’Abdulrazaq, nous aborderons les enjeux que représente de jouer du sorûd (vièle baloutche) en Oman. Cet instrument est lié à la réalisation du damâl, une cérémonie fréquentée par les Baloutches omanais. Nous mettrons en évidence l’importance qu’Abdulrazaq représente pour la sphère sociale dans laquelle il est inclus, ainsi que son rôle en tant que gestionnaire d'un ensemble musical. Le damâl décrit ici fait écho à des rituels qui ont été observés au Baloutchistan. Nous amorcerons un premier dialogue entre ces différentes pratiques culturelles sans pour autant statuer sur une assimilation omanaise du damâl asiatique.
Number: 15
Keywords: Musique – Oman

Muscat and the Portuguese: economic and political dynamics in the early 16th century (1507-1529) - Couto, Dejanirah (Arabian Humanities, 2022)
Based on recently published literature, this article examines the relationship between Oman’s coastal towns and the Portuguese in the early decades of the 16th century. He takes as an example the port of Muscat, whose remarkable natural conditions had favored, from medieval times, its supremacy as a bridgehead for the hinterland regions and leader of the commercial networks of the West Indian Ocean, to the detriment of other Omani ports. This superiority, which also rest on its ability to orient its economy on several fronts, was reinforced by the presence of the Portuguese, who, following their attack in 1507, appointed Muscat as a stopover of their fleets and established there a factory. In addition, the progressive involvement of the Portuguese in the economic life of Muscat was accompanied by a growing political interference in the internal affairs of the city, symbolized by an implication in the conflicts which opposed the urban elites of Muscat to those of the other cities of Oman and also to Hormuz, which, while exercising its authority over the towns on the Omani side, had become, after the double conquest of Afonso de Albuquerque (1507 and 1515), protectorate of the Portuguese.
Number: 15
Keywords: Relations – Oman – Portugal

Oman au fil du temps : Une nation de la Nahda à l’Oman Vision 2040 - Sebiane, Maho; Breteau, Marion; Maguer-Gillon, Sterenn le (Arabian Humanities, 2022)
L’ambition de ce dossier thématique est d’esquisser un état des lieux pluridisciplinaire de la période contemporaine du Sultanat d’Oman. Il a été envisagé comme une invitation à faire dialoguer des réflexions de recherche issues d’horizons divers portant sur l’histoire de ce pays, mais également sur les grandes mutations sociales et culturelles qui ont traversé sa société. L’appel à contribution a été lancé au début de l’année 2020 dans un contexte qui ne présageait pas de la crise du coronav...
Number: 15
Keywords: Oman – Histoire

Des vallées du pays ibadite aux littoraux du sultanat : une histoire patrimoniale des manuscrits ibadites omanais - Baptiste, Enki (Arabian Humanities, 2022)
Cet article se penche sur l’histoire de la conservation des manuscrits ibadites à Oman. Nous montrerons que la nahḍa des années 1970 a été un moment de renouveau dans l’édition de sources et dans la promotion de l’histoire d’Oman. Avec la fondation du Ministère du Patrimoine, le sultanat s’est doté d’une institution de référence pour la mise en valeur de son héritage ibadite. Autour du Ministère gravitent d’autres institutions ou fondations pieuses investies dans cette politique de promotion des manuscrits. En revenant sur les différentes nahḍa ibadites, notre texte montre que cette politique d’ouverture promue par le sultanat s’inscrit dans une longue tradition lettrée ibadite dans laquelle des familles ont joué un rôle fondamental. Notre article note en conclusion que cette sultanisation des activités d’édition et de conservation des manuscrits a été rendue possible par une intégration des familles ibadites dans les institutions intellectuelles engagées dans ces politiques de préservation des documents.
Number: 15
Keywords: Manuscrits – Oman

L'archipel ibadite : Une histoire des marges du Maghreb médiéval - Aillet, Cyrille (Ciham éditions, 2022)
Cette enquête inédite revisite l’évolution du Maghreb médiéval à partir de ses marges. Elle dévoile l’histoire de l’ibadisme, une minorité aujourd’hui invisible dans l’océan du sunnisme, mais qui a puissamment façonné le Maghreb. Héritiers des dissidents kharijites soulevés contre le califat, les Ibadites animent les révoltes qui détachent la région de l’Empire. Ils jouent un rôle crucial dans l’émergence d’un discours en faveur des Berbères, chez qui ils recrutent en masse. Ces contestataires développent une doctrine politique singulière, hostile à la tyrannie et favorable à une souveraineté fondée sur l’élection, la consultation et la collégialité. Pour les Ibadites, cet idéal s’incarne dans l’État qu’ils fondent vers 761 près de Tiaret, dans l’Algérie actuelle. Dirigé par une dynastie d’imams persans, il symbolise pour eux un véritable âge d’or. Sa disparition brutale sous les coups des Fatimides en 909 constitue un traumatisme collectif. Elle oblige les fidèles à se redéployer sous la forme d’un archipel de communautés autonomes, dispersées entre la Méditerranée et le nord du Sahara. Après l’échec des derniers soulèvements berbères face à l’Empire, la nécessité de coexister avec les pouvoirs dominants s’impose. L’autorité des notables et des oulémas se substitue localement à l’État pour assurer la cohésion collective. Le commerce transsaharien tisse des relations entre ces communautés et assure la fortune des marchands- lettrés qui traversent le désert jusqu’à Ghana, Gao ou au lac Tchad. Ils en rapportent de l’or et des convois d’esclaves, revendus dans les oasis et les cités de Méditerranée. La poussée des intérêts rivaux et l’expansion religieuse du malikisme et du soufisme achèvent toutefois d’éroder, puis de désarticuler, l’archipel ibadite. À la fin du Moyen Âge, il n’en subsiste que les bastions actuels du Mzab, de Tripolitaine et de Djerba. La mémoire de cette communauté oubliée nous plonge au cœur même de la genèse de l’Islam et du Maghreb.
Keywords: Commerce transsaharien; Dynastie rustumide; Ibadisme – Afrique du Nord

Un M’Zab en fragmentation : Premiers constats à la suite des derniers conflits de Ghardaïa - Gueliane, Nora (Conseil Arabe pour les Sciences Sociales, 2022)
L’objet de cette contribution est une interrogation sur les fragmentations socio-spatiales qui marquent le M’Zab, une région du sud algérien. Cela à travers les premiers constats et observations soulevés sur le terrain cinq ans après le dernier conflit intercommunautaire (2013-2015) qui a touché la région. Dans ce document il est question, dans un premier temps, de décrire le contexte de notre travail de terrain, les contraintes rencontrées et les mécanismes adoptés pour les contourner. Dans un deuxième temps, nous allons illustrer le contexte de l’étude : le conflit de Ghardaïa de 2013-2015 et les groupes concernés. Pour enfin conclure avec une mise en lumière sur le langage adopté par les informateurs afin de décrire et témoigner d’un sujet aussi sensible – surtout si on prend en considération le contexte algérien actuel, post-Hirak, marqué par une répression policière sans précédent.
Keywords: Urbanisme – Mzab

فضاءات الاحتجاج وأنساقها الرمزية" مقاربة انتروبولوجية تأويلية لإباضية وادي مزاب - بوفريخة, أسامة (زينب للنشر و التوزيع‎, 2022)
Keywords: Moeurs et coutumes – Mzab

التكوين الذاتي للأقلية: الميزابيون وأداء الاختلاف في الجزائر المستعمرة - غزال, أمل (2022)
سيمنار #المركز_العربي، بعنوان "التكوين الذاتي للأقلية: الميزابيون وأداء الاختلاف في الجزائر المستعمرَة"، من تقديم أمل غزال، يدير الجلسة مراد دياني.

Que doit l’ibadisme au kharijisme ? - Aillet, Cyrille (2022)
Des trois branches de l’islam, on connaît généralement le sunnisme et le chiisme. La troisième, le kharijisme, constitue une catégorie beaucoup plus difficile à cerner, mais son image dans les sources majoritaires est celle de la dissidence, voire de la déviance, politique et religieuse. Les Kharijites sont très présents dans la littérature arabe pour incarner un anti-modèle, celui du chaos politique, de la révolte permanente, de l’excès de zèle religieux et dévotionnel. A tel point que leurs leaders, qui défièrent à plusieurs reprises l’Empire omeyyade, puis abbasside, sont dépeints tantôt comme des rebelles insaisissables, tantôt comme des desperados, des bandits de grand chemin ou des fous de Dieu. Nous analyserons et déconstruirons tout d’abord cet imaginaire de la dissidence, qui participe à la construction de cet islam hégémonique que devint le sunnisme au cours des premiers siècles. Occasion pour nous de revisiter quelques récits qui structurent la narration historique en islam : le règne d’Uthmân, calife de la discorde, la bataille de Siffîn, matrice symbolique des trois branches que se reconnaît l’islam, le meurtre d’Ali, qui met en jeu la question du meurtre politique… Les Kharijites ont constitué une nébuleuse dont nous tenterons aussi de cerner les caractéristiques, de comprendre le programme politique et religieux. Mais pour cela, il faudra tenter de passer de l’autre côté du miroir en essayant d’identifier les textes et les témoignages qui documentent ce courant au plus juste. Nous nous appuierons pour cela sur la production écrite des Ibadites, leurs lointains héritiers idéologiques.
Keywords: Kharijisme

Les Ṣufrites, de l’Orient au Maghreb - Aillet, Cyrille (2022)
Des trois branches de l’islam, on connaît généralement le sunnisme et le chiisme. La troisième, le kharijisme, constitue une catégorie beaucoup plus difficile à cerner, mais son image dans les sources majoritaires est celle de la dissidence, voire de la déviance, politique et religieuse. Les Kharijites sont très présents dans la littérature arabe pour incarner un anti-modèle, celui du chaos politique, de la révolte permanente, de l’excès de zèle religieux et dévotionnel. A tel point que leurs leaders, qui défièrent à plusieurs reprises l’Empire omeyyade, puis abbasside, sont dépeints tantôt comme des rebelles insaisissables, tantôt comme des desperados, des bandits de grand chemin ou des fous de Dieu. Nous analyserons et déconstruirons tout d’abord cet imaginaire de la dissidence, qui participe à la construction de cet islam hégémonique que devint le sunnisme au cours des premiers siècles. Occasion pour nous de revisiter quelques récits qui structurent la narration historique en islam : le règne d’Uthmân, calife de la discorde, la bataille de Siffîn, matrice symbolique des trois branches que se reconnaît l’islam, le meurtre d’Ali, qui met en jeu la question du meurtre politique… Les Kharijites ont constitué une nébuleuse dont nous tenterons aussi de cerner les caractéristiques, de comprendre le programme politique et religieux. Mais pour cela, il faudra tenter de passer de l’autre côté du miroir en essayant d’identifier les textes et les témoignages qui documentent ce courant au plus juste. Nous nous appuierons pour cela sur la production écrite des Ibadites, leurs lointains héritiers idéologiques.
Keywords: Sufrisme

Lectures kharijites du Coran - Khelifa, Ahmed (2022)
Des trois branches de l’islam, on connaît généralement le sunnisme et le chiisme. La troisième, le kharijisme, constitue une catégorie beaucoup plus difficile à cerner, mais son image dans les sources majoritaires est celle de la dissidence, voire de la déviance, politique et religieuse. Les Kharijites sont très présents dans la littérature arabe pour incarner un anti-modèle, celui du chaos politique, de la révolte permanente, de l’excès de zèle religieux et dévotionnel. A tel point que leurs leaders, qui défièrent à plusieurs reprises l’Empire omeyyade, puis abbasside, sont dépeints tantôt comme des rebelles insaisissables, tantôt comme des desperados, des bandits de grand chemin ou des fous de Dieu. Nous analyserons et déconstruirons tout d’abord cet imaginaire de la dissidence, qui participe à la construction de cet islam hégémonique que devint le sunnisme au cours des premiers siècles. Occasion pour nous de revisiter quelques récits qui structurent la narration historique en islam : le règne d’Uthmân, calife de la discorde, la bataille de Siffîn, matrice symbolique des trois branches que se reconnaît l’islam, le meurtre d’Ali, qui met en jeu la question du meurtre politique… Les Kharijites ont constitué une nébuleuse dont nous tenterons aussi de cerner les caractéristiques, de comprendre le programme politique et religieux. Mais pour cela, il faudra tenter de passer de l’autre côté du miroir en essayant d’identifier les textes et les témoignages qui documentent ce courant au plus juste. Nous nous appuierons pour cela sur la production écrite des Ibadites, leurs lointains héritiers idéologiques.
Keywords: Coran – Commentaires – 9e siècle

Azraqites et Najdites, entre légende noire et faits historiques - Aillet, Cyrille (2022)
Des trois branches de l’islam, on connaît généralement le sunnisme et le chiisme. La troisième, le kharijisme, constitue une catégorie beaucoup plus difficile à cerner, mais son image dans les sources majoritaires est celle de la dissidence, voire de la déviance, politique et religieuse. Les Kharijites sont très présents dans la littérature arabe pour incarner un anti-modèle, celui du chaos politique, de la révolte permanente, de l’excès de zèle religieux et dévotionnel. A tel point que leurs leaders, qui défièrent à plusieurs reprises l’Empire omeyyade, puis abbasside, sont dépeints tantôt comme des rebelles insaisissables, tantôt comme des desperados, des bandits de grand chemin ou des fous de Dieu. Nous analyserons et déconstruirons tout d’abord cet imaginaire de la dissidence, qui participe à la construction de cet islam hégémonique que devint le sunnisme au cours des premiers siècles. Occasion pour nous de revisiter quelques récits qui structurent la narration historique en islam : le règne d’Uthmân, calife de la discorde, la bataille de Siffîn, matrice symbolique des trois branches que se reconnaît l’islam, le meurtre d’Ali, qui met en jeu la question du meurtre politique… Les Kharijites ont constitué une nébuleuse dont nous tenterons aussi de cerner les caractéristiques, de comprendre le programme politique et religieux. Mais pour cela, il faudra tenter de passer de l’autre côté du miroir en essayant d’identifier les textes et les témoignages qui documentent ce courant au plus juste. Nous nous appuierons pour cela sur la production écrite des Ibadites, leurs lointains héritiers idéologiques.
Keywords: Azraqisme; Najdiyya

The Kharijites in Early Islamic Historical Tradition - Hagemann, Hannah-Lena (2022)
Des trois branches de l’islam, on connaît généralement le sunnisme et le chiisme. La troisième, le kharijisme, constitue une catégorie beaucoup plus difficile à cerner, mais son image dans les sources majoritaires est celle de la dissidence, voire de la déviance, politique et religieuse. Les Kharijites sont très présents dans la littérature arabe pour incarner un anti-modèle, celui du chaos politique, de la révolte permanente, de l’excès de zèle religieux et dévotionnel. A tel point que leurs leaders, qui défièrent à plusieurs reprises l’Empire omeyyade, puis abbasside, sont dépeints tantôt comme des rebelles insaisissables, tantôt comme des desperados, des bandits de grand chemin ou des fous de Dieu. Nous analyserons et déconstruirons tout d’abord cet imaginaire de la dissidence, qui participe à la construction de cet islam hégémonique que devint le sunnisme au cours des premiers siècles. Occasion pour nous de revisiter quelques récits qui structurent la narration historique en islam : le règne d’Uthmân, calife de la discorde, la bataille de Siffîn, matrice symbolique des trois branches que se reconnaît l’islam, le meurtre d’Ali, qui met en jeu la question du meurtre politique… Les Kharijites ont constitué une nébuleuse dont nous tenterons aussi de cerner les caractéristiques, de comprendre le programme politique et religieux. Mais pour cela, il faudra tenter de passer de l’autre côté du miroir en essayant d’identifier les textes et les témoignages qui documentent ce courant au plus juste. Nous nous appuierons pour cela sur la production écrite des Ibadites, leurs lointains héritiers idéologiques.
Keywords: Kharijisme

Une nébuleuse de mouvements difficile à identifier - Aillet, Cyrille (2022)
Des trois branches de l’islam, on connaît généralement le sunnisme et le chiisme. La troisième, le kharijisme, constitue une catégorie beaucoup plus difficile à cerner, mais son image dans les sources majoritaires est celle de la dissidence, voire de la déviance, politique et religieuse. Les Kharijites sont très présents dans la littérature arabe pour incarner un anti-modèle, celui du chaos politique, de la révolte permanente, de l’excès de zèle religieux et dévotionnel. A tel point que leurs leaders, qui défièrent à plusieurs reprises l’Empire omeyyade, puis abbasside, sont dépeints tantôt comme des rebelles insaisissables, tantôt comme des desperados, des bandits de grand chemin ou des fous de Dieu. Nous analyserons et déconstruirons tout d’abord cet imaginaire de la dissidence, qui participe à la construction de cet islam hégémonique que devint le sunnisme au cours des premiers siècles. Occasion pour nous de revisiter quelques récits qui structurent la narration historique en islam : le règne d’Uthmân, calife de la discorde, la bataille de Siffîn, matrice symbolique des trois branches que se reconnaît l’islam, le meurtre d’Ali, qui met en jeu la question du meurtre politique… Les Kharijites ont constitué une nébuleuse dont nous tenterons aussi de cerner les caractéristiques, de comprendre le programme politique et religieux. Mais pour cela, il faudra tenter de passer de l’autre côté du miroir en essayant d’identifier les textes et les témoignages qui documentent ce courant au plus juste. Nous nous appuierons pour cela sur la production écrite des Ibadites, leurs lointains héritiers idéologiques.
Keywords: Kharijisme

Views of the Khārijites: Historiography and Textual Issues - Gaiser, Adam R.; Baptiste, Enki (2022)
Des trois branches de l’islam, on connaît généralement le sunnisme et le chiisme. La troisième, le kharijisme, constitue une catégorie beaucoup plus difficile à cerner, mais son image dans les sources majoritaires est celle de la dissidence, voire de la déviance, politique et religieuse. Les Kharijites sont très présents dans la littérature arabe pour incarner un anti-modèle, celui du chaos politique, de la révolte permanente, de l’excès de zèle religieux et dévotionnel. A tel point que leurs leaders, qui défièrent à plusieurs reprises l’Empire omeyyade, puis abbasside, sont dépeints tantôt comme des rebelles insaisissables, tantôt comme des desperados, des bandits de grand chemin ou des fous de Dieu. Nous analyserons et déconstruirons tout d’abord cet imaginaire de la dissidence, qui participe à la construction de cet islam hégémonique que devint le sunnisme au cours des premiers siècles. Occasion pour nous de revisiter quelques récits qui structurent la narration historique en islam : le règne d’Uthmân, calife de la discorde, la bataille de Siffîn, matrice symbolique des trois branches que se reconnaît l’islam, le meurtre d’Ali, qui met en jeu la question du meurtre politique… Les Kharijites ont constitué une nébuleuse dont nous tenterons aussi de cerner les caractéristiques, de comprendre le programme politique et religieux. Mais pour cela, il faudra tenter de passer de l’autre côté du miroir en essayant d’identifier les textes et les témoignages qui documentent ce courant au plus juste. Nous nous appuierons pour cela sur la production écrite des Ibadites, leurs lointains héritiers idéologiques.
Keywords: Kharijisme

Le meurtre d’Ali et la question de la violence politique - Aillet, Cyrille (2022)
Des trois branches de l’islam, on connaît généralement le sunnisme et le chiisme. La troisième, le kharijisme, constitue une catégorie beaucoup plus difficile à cerner, mais son image dans les sources majoritaires est celle de la dissidence, voire de la déviance, politique et religieuse. Les Kharijites sont très présents dans la littérature arabe pour incarner un anti-modèle, celui du chaos politique, de la révolte permanente, de l’excès de zèle religieux et dévotionnel. A tel point que leurs leaders, qui défièrent à plusieurs reprises l’Empire omeyyade, puis abbasside, sont dépeints tantôt comme des rebelles insaisissables, tantôt comme des desperados, des bandits de grand chemin ou des fous de Dieu. Nous analyserons et déconstruirons tout d’abord cet imaginaire de la dissidence, qui participe à la construction de cet islam hégémonique que devint le sunnisme au cours des premiers siècles. Occasion pour nous de revisiter quelques récits qui structurent la narration historique en islam : le règne d’Uthmân, calife de la discorde, la bataille de Siffîn, matrice symbolique des trois branches que se reconnaît l’islam, le meurtre d’Ali, qui met en jeu la question du meurtre politique… Les Kharijites ont constitué une nébuleuse dont nous tenterons aussi de cerner les caractéristiques, de comprendre le programme politique et religieux. Mais pour cela, il faudra tenter de passer de l’autre côté du miroir en essayant d’identifier les textes et les témoignages qui documentent ce courant au plus juste. Nous nous appuierons pour cela sur la production écrite des Ibadites, leurs lointains héritiers idéologiques.
Keywords: Idées politiques – Ibadisme

Les mythes fondateurs de Ṣiffīn et Nahrāwān - Aillet, Cyrille (2022)
Des trois branches de l’islam, on connaît généralement le sunnisme et le chiisme. La troisième, le kharijisme, constitue une catégorie beaucoup plus difficile à cerner, mais son image dans les sources majoritaires est celle de la dissidence, voire de la déviance, politique et religieuse. Les Kharijites sont très présents dans la littérature arabe pour incarner un anti-modèle, celui du chaos politique, de la révolte permanente, de l’excès de zèle religieux et dévotionnel. A tel point que leurs leaders, qui défièrent à plusieurs reprises l’Empire omeyyade, puis abbasside, sont dépeints tantôt comme des rebelles insaisissables, tantôt comme des desperados, des bandits de grand chemin ou des fous de Dieu. Nous analyserons et déconstruirons tout d’abord cet imaginaire de la dissidence, qui participe à la construction de cet islam hégémonique que devint le sunnisme au cours des premiers siècles. Occasion pour nous de revisiter quelques récits qui structurent la narration historique en islam : le règne d’Uthmân, calife de la discorde, la bataille de Siffîn, matrice symbolique des trois branches que se reconnaît l’islam, le meurtre d’Ali, qui met en jeu la question du meurtre politique… Les Kharijites ont constitué une nébuleuse dont nous tenterons aussi de cerner les caractéristiques, de comprendre le programme politique et religieux. Mais pour cela, il faudra tenter de passer de l’autre côté du miroir en essayant d’identifier les textes et les témoignages qui documentent ce courant au plus juste. Nous nous appuierons pour cela sur la production écrite des Ibadites, leurs lointains héritiers idéologiques.
Keywords: Idées politiques – Ibadisme

La succession du Prophète à la lumière du kharijisme - Aillet, Cyrille (2022)
Des trois branches de l’islam, on connaît généralement le sunnisme et le chiisme. La troisième, le kharijisme, constitue une catégorie beaucoup plus difficile à cerner, mais son image dans les sources majoritaires est celle de la dissidence, voire de la déviance, politique et religieuse. Les Kharijites sont très présents dans la littérature arabe pour incarner un anti-modèle, celui du chaos politique, de la révolte permanente, de l’excès de zèle religieux et dévotionnel. A tel point que leurs leaders, qui défièrent à plusieurs reprises l’Empire omeyyade, puis abbasside, sont dépeints tantôt comme des rebelles insaisissables, tantôt comme des desperados, des bandits de grand chemin ou des fous de Dieu. Nous analyserons et déconstruirons tout d’abord cet imaginaire de la dissidence, qui participe à la construction de cet islam hégémonique que devint le sunnisme au cours des premiers siècles. Occasion pour nous de revisiter quelques récits qui structurent la narration historique en islam : le règne d’Uthmân, calife de la discorde, la bataille de Siffîn, matrice symbolique des trois branches que se reconnaît l’islam, le meurtre d’Ali, qui met en jeu la question du meurtre politique… Les Kharijites ont constitué une nébuleuse dont nous tenterons aussi de cerner les caractéristiques, de comprendre le programme politique et religieux. Mais pour cela, il faudra tenter de passer de l’autre côté du miroir en essayant d’identifier les textes et les témoignages qui documentent ce courant au plus juste. Nous nous appuierons pour cela sur la production écrite des Ibadites, leurs lointains héritiers idéologiques.
Keywords: Idées politiques – Ibadisme

Aux origines de l’architecture sectaire de l’islam - Aillet, Cyrille (2022)
Des trois branches de l’islam, on connaît généralement le sunnisme et le chiisme. La troisième, le kharijisme, constitue une catégorie beaucoup plus difficile à cerner, mais son image dans les sources majoritaires est celle de la dissidence, voire de la déviance, politique et religieuse. Les Kharijites sont très présents dans la littérature arabe pour incarner un anti-modèle, celui du chaos politique, de la révolte permanente, de l’excès de zèle religieux et dévotionnel. A tel point que leurs leaders, qui défièrent à plusieurs reprises l’Empire omeyyade, puis abbasside, sont dépeints tantôt comme des rebelles insaisissables, tantôt comme des desperados, des bandits de grand chemin ou des fous de Dieu. Nous analyserons et déconstruirons tout d’abord cet imaginaire de la dissidence, qui participe à la construction de cet islam hégémonique que devint le sunnisme au cours des premiers siècles. Occasion pour nous de revisiter quelques récits qui structurent la narration historique en islam : le règne d’Uthmân, calife de la discorde, la bataille de Siffîn, matrice symbolique des trois branches que se reconnaît l’islam, le meurtre d’Ali, qui met en jeu la question du meurtre politique… Les Kharijites ont constitué une nébuleuse dont nous tenterons aussi de cerner les caractéristiques, de comprendre le programme politique et religieux. Mais pour cela, il faudra tenter de passer de l’autre côté du miroir en essayant d’identifier les textes et les témoignages qui documentent ce courant au plus juste. Nous nous appuierons pour cela sur la production écrite des Ibadites, leurs lointains héritiers idéologiques.
Keywords: Architecture – Sources

Le kharijisme dans la culture islamique et l’historiographie - Aillet, Cyrille (2022)
Des trois branches de l’islam, on connaît généralement le sunnisme et le chiisme. La troisième, le kharijisme, constitue une catégorie beaucoup plus difficile à cerner, mais son image dans les sources majoritaires est celle de la dissidence, voire de la déviance, politique et religieuse. Les Kharijites sont très présents dans la littérature arabe pour incarner un anti-modèle, celui du chaos politique, de la révolte permanente, de l’excès de zèle religieux et dévotionnel. A tel point que leurs leaders, qui défièrent à plusieurs reprises l’Empire omeyyade, puis abbasside, sont dépeints tantôt comme des rebelles insaisissables, tantôt comme des desperados, des bandits de grand chemin ou des fous de Dieu. Nous analyserons et déconstruirons tout d’abord cet imaginaire de la dissidence, qui participe à la construction de cet islam hégémonique que devint le sunnisme au cours des premiers siècles. Occasion pour nous de revisiter quelques récits qui structurent la narration historique en islam : le règne d’Uthmân, calife de la discorde, la bataille de Siffîn, matrice symbolique des trois branches que se reconnaît l’islam, le meurtre d’Ali, qui met en jeu la question du meurtre politique… Les Kharijites ont constitué une nébuleuse dont nous tenterons aussi de cerner les caractéristiques, de comprendre le programme politique et religieux. Mais pour cela, il faudra tenter de passer de l’autre côté du miroir en essayant d’identifier les textes et les témoignages qui documentent ce courant au plus juste. Nous nous appuierons pour cela sur la production écrite des Ibadites, leurs lointains héritiers idéologiques.
Keywords: Kharijisme

“Berbers”, “Kharijites” and “Knowledge Bearers”: How the Ibadis Shaped a Counter-Memory of the Islamic Conquest of North Africa - Aillet, Cyrille (2022)
Keywords: Idées politiques – Ibadisme

Libraries of the Nafusa. A pilot project to document and digitize material heritage in the Jebel Nafusa, Libya - Love Jr, Paul M. (2022)
Keywords: Bibliothèques – Djebel Nefousa; Manuscrits – Djebel Nefousa